Imposter phenomenon and basic psychological needs predict self-evaluations of knowledge and ability relative to others - Biblekaj, Viktoria; Kahlbaugh, Patricia (International Journal of Personality Psychology, 2026)
Imposter Phenomenon (IP) is a set of psychological experiences characterized by self-doubt, attributing success to external causes, and a constant fear of being perceived as a phony (Clance & Imes, 1978), which may be suggestive of dissatisfaction with basic psychological needs of competence, autonomy, and relatedness. Amazon Mechanical Turk (MTurk) workers (N = 325, 61% men, 39% women) ranked their self-identified knowledge and abilities relative to others, completed the Clance Imposter Phenomenon Scale (CIPS) assessing IP, and the Balanced Measure of Psychological Needs (BMPN) assessing competence, autonomy, and relatedness. We hypothesized that IP and dissatisfaction in basic psychological needs would predict underestimation of knowledge and abilities relative to those of other people. However, we found imposter phenomenon and basic psychological needs predicted positive self-evaluations. Inflated self-evaluations may be strategically used to defend against IP feelings and against a sense of “ill-being” associated with thwarted psychological needs. Thus, a positive, confident presentation may be compensatory or defensive in nature. Future research could explore specific defense mechanisms that may mediate this positive self-evaluation of knowledge and ability relative to others as well as the role of styles of perfectionism.
Keywords: Basic needs; Feeling; Need theory; Phenomenon; Scale (ratio); Set (abstract data type); dept.psy

Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (Zenodo (CERN European Organization for Nuclear Research), 2026)
(1) Understanding the thermal sensitivity of reproductive interactions is crucial given global warming. Previous studies have almost exclusively focused on interactions before mating, even though important interactions between the sexes also occur after mating (e.g., gamete interactions), which are likely affected by temperature. (2) Thus, it remains unknown how temperature affects the influence of female reproductive fluid on sperm performance, thereby altering female control over fertilization (cryptic female choice). This gap limits our understanding of how sexual selection changes with seasonal temperature fluctuations and temperatures outside the range of historical norms. (3) We tested how temperatures relevant to current conditions and climate change projections influence the mechanisms underlying cryptic female choice in a marine fish, Symphodus ocellatus. Under typical thermal conditions, female reproductive fluid enhances sperm velocity and biases fertilization dynamics to favor preferred, dominant males over sneaker males. (4) We find that warmer temperatures decrease female influence on sperm velocity, especially for dominant males. This results in dominant males having slower sperm than sneaker males at warmer temperatures, reducing the expected paternity of preferred, dominant males. (5) Our results highlight that considering the thermal sensitivity of female-male interactions that occur after mating will be essential for understanding how seasonal variation and climate change can influence fertility, reproduction, and sexual selection.
Keywords: Climate change; Gamete; Mate choice; Mating; Mating system; Operational sex ratio; Sexual selection; Sperm; dept.psy

Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (2026)
(1) Understanding the thermal sensitivity of reproductive interactions is crucial given global warming. Previous studies have almost exclusively focused on interactions before mating, even though important interactions between the sexes also occur after mating (e.g., gamete interactions), which are likely affected by temperature. (2) Thus, it remains unknown how temperature affects the influence of female reproductive fluid on sperm performance, thereby altering female control over fertilization (cryptic female choice). This gap limits our understanding of how sexual selection changes with seasonal temperature fluctuations and temperatures outside the range of historical norms. (3) We tested how temperatures relevant to current conditions and climate change projections influence the mechanisms underlying cryptic female choice in a marine fish, Symphodus ocellatus. Under typical thermal conditions, female reproductive fluid enhances sperm velocity and biases fertilization dynamics to favor preferred, dominant males over sneaker males. (4) We find that warmer temperatures decrease female influence on sperm velocity, especially for dominant males. This results in dominant males having slower sperm than sneaker males at warmer temperatures, reducing the expected paternity of preferred, dominant males. (5) Our results highlight that considering the thermal sensitivity of female-male interactions that occur after mating will be essential for understanding how seasonal variation and climate change can influence fertility, reproduction, and sexual selection.
Publication Title: DRYAD
Keywords: Climate change; Gamete; Mate choice; Mating; Mating system; Operational sex ratio; Sexual selection; Sperm; dept.psy

Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (bioRxiv (Cold Spring Harbor Laboratory), 2025)
Abstract Reproduction is often more thermally sensitive than survival. Thus, understanding the thermal sensitivity of reproductive interactions is crucial given global warming. However, it is unknown how temperature influences female control over fertilization after mating ( i.e., cryptic female choice). We tested how temperatures relevant to current conditions and climate change projections influence cryptic female choice in a marine fish, Symphodus ocellatus . Under typical conditions, females bias fertilization dynamics to favor dominant males. We find that warmer temperatures decrease female influence on sperm velocity and reduce the expected paternity of dominant males. Our results demonstrate that temperatures relevant to climate change can shift the balance between mate choice and male-male competition. Thus, climate change may influence sexual selection, leading to evolutionary changes in reproductive traits.
Keywords: Geology; Oceanography; dept.psy

Role of an Intermediary Organization and State Government Partnership to Advance Practice and Policy in Children’s Behavioral Health - Lang, Jason; Randall, Kellie; Kelly, A.; Bracey, Jeana; Bridges-Hightower, Jenny; Newkirk, Katie; Lu, Jack; Gregory, Francis; Duran, Tracy; Geib, Catherine; Bozak, Stephanie; Mackey, Jocelyn; et al. (Prevention Science, 2026)
Keywords: Behavioral health; Bridge (graph theory); Diversity (politics); General partnership; Government (linguistics); Intermediary organization; Partnership; Plan (archaeology); Policy; Public policy; Research; State (computer science); System development; Workforce; Workforce development; dept.psy

Actigraphy-based sleep outcomes in substance use disorders: A systematic review and meta-analysis - Naveda, Alisson; Oliva, Henrique; Pulido-Saavedra, Alejandra; Ghadimi, Delaram; Moore, James; Morgan, Peter; Potenza, Marc; Angarita, Gustavo (Sleep Medicine Reviews, 2026)
Keywords: MEDLINE; Polysomnography; Sleep (system call); Substance use; Systematic review; dept.psy

Thinking differently: neurodivergent traits and responses to thought experiments in philosophers and the general population - McKee, Paul; Boulhadi, Khaoula; Weymouth, Helena; Nadelhoffer, Thomas (Philosophical Psychology, 2026)
Philosophers have long speculated that individual differences in temperament influence philosophical thinking, yet empirical research has rarely explored the role of neurodivergent traits in this domain. In this large online study (N = 1,254), we investigated whether participants with training in philosophy differ from the general population when it comes to six psychological traits–autism, ADHD, aphantasia, anendophasia, anauralia, and representational manipulation–and also whether these traits correlate with responses to two widely studied philosophical thought experiments: the “trolley problem” and the “rollback deterministic universe.” Compared to the general population, participants with training in philosophy had higher scores on measures of ADHD, internal verbalization, and representational manipulation, but lower scores on measures of visual imagery. These cognitive traits were also correlated with participants’ moral and metaphysical judgments (independent of their level of philosophical training)–e.g. participants who scored higher in visualization were less likely to judge that hitting the switch in the trolley problem is permissible but not obligatory, and also less likely to attribute free will and moral responsibility to agents in the rollback universe. Finally, we employed machine learning to develop predictive models that classify a randomly selected participant as either a philosopher or a non-philosopher. Models trained solely on responses to measures for neurodivergent traits achieved better performance than models trained solely on responses to philosophical thought experiments. This suggests that stable, trait-level neurodivergent characteristics may be more diagnostic of philosophical interest, aptitude, or training than judgments philosophers make on domain-relevant problems. © 2026 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Neurodiversity; dept.psy; experimental philosophy; free will beliefs; general population; moral judgment; philosophers

Investigating the analytical robustness of the social and behavioural sciences - Aczel, Balazs; Szaszi, Barnabas; Clelland, Harry T.; Kovacs, Marton; Holzmeister, Felix; van Ravenzwaaij, Don; Schulz-Kümpel, Hannah; Hoffmann, Sabine; Nilsonne, Gustav; Kosa, Livia; Torma, Zoltan A.; Abdelfatah, Yousuf; et al. (Nature, 2026)
The same dataset can be analysed in different justifiable ways to answer the same research question, potentially challenging the robustness of empirical science1-3. In this crowd initiative, we investigated the degree to which research findings in the social and behavioural sciences are contingent on analysts' choices. We examined a stratified random sample of 100 studies published between 2009 and 2018, in which, for one claim per study, at least five reanalysts independently reanalysed the original data. The statistical appropriateness of the reanalyses was assessed in peer evaluations, and the robustness indicators were inspected along a range of research characteristics and study designs. We found that 34% of the independent reanalyses yielded the same result (within a tolerance region of ±0.05 Cohen's d) as the original report; with a four times broader tolerance region, this indicator increased to 57%. Of the reanalyses conducted, 74% reached the same conclusion as the original investigation, 24% yielded no effects or inconclusive results and 2% reported the opposite effect. This exploratory study indicates that the common single-path analyses in social and behavioural research should not be simply assumed to be robust to alternative analyses4. Therefore, we recommend the development and use of practices to explore and communicate this neglected source of uncertainty. © 2026. The Author(s), under exclusive licence to Springer Nature Limited.
Keywords: Behavioural sciences; Empirical research; Exploratory research; Robustness (evolution); Sample size determination; Statistical analysis; dept.psy

General trait and workplace fear of missing out (FoMO) and the neurodiverse mind: Exploring autism, ADHD, and internal representation profiles - McKee, Paul; Boulhadi, Khaoula; Nadelhoffer, Thomas (Personality and Individual Differences, 2026)
Keywords: Mental representation; Psychometrics; Representation (politics); Social perception; Trait; dept.psy

Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (Functional Ecology, 2026)
Abstract Understanding the thermal sensitivity of reproductive interactions is crucial given global warming. Previous studies have almost exclusively focused on interactions before mating, even though important interactions between the sexes also occur after mating (e.g. gamete interactions), which are likely also affected by temperature. Thus, it remains unknown how temperature affects the influence of female reproductive fluid on sperm performance, thereby altering female control over fertilization (cryptic female choice). This gap limits our understanding of how sexual selection changes with seasonal temperature fluctuations and temperatures outside the range of historical norms. We tested how temperatures relevant to current conditions and climate change projections influence the mechanisms underlying cryptic female choice in a marine fish, Symphodus ocellatus . Under typical, cooler thermal conditions, female reproductive fluid enhances sperm velocity and biases fertilization dynamics to favour preferred, dominant males over sneaker males. We find that warmer temperatures decrease female influence on sperm velocity, especially for dominant males. This results in dominant males having slower sperm than sneaker males at warmer temperatures, reducing the expected paternity of preferred, dominant males. Our results highlight that considering the thermal sensitivity of female–male interactions that occur after mating will be essential for understanding how seasonal variation and climate change can influence fertility, reproduction and sexual selection. Read the free Plain Language Summary for this article on the Journal blog.
Keywords: Gamete; Mating; Mating system; Reproduction; Reproductive success; Sexual selection; Sperm; Sperm competition; alternative reproductive tactics; climate change; dept.psy; mating systems; ovarian fluid; sexual selection; sperm competition; thermal ecology

Actigraphy-based sleep outcomes in substance use disorders: A protocol for a systematic review and meta-analysis - Naveda, Alisson; Oliva, Henrique; Ghadimi, Delaram; Angarita, Gustavo (PLoS ONE, 2026)
INTRODUCTION: Individuals with substance use disorders (SUDs) are at increased risk for sleep disturbances, creating a bidirectional relationship that may heighten relapse risk. While polysomnography is the gold standard for measuring sleep, many studies have used actigraphy, a noninvasive, wrist-worn device that estimates rest-activity patterns and sleep-wake characteristics. Despite its utility, the use of actigraphy in populations with SUDs remains limited, and findings vary across substances and methodologies. This protocol outlines a systematic review and meta-analysis aiming to synthesize evidence on actigraphy-derived sleep outcomes across various substances. METHOD AND ANALYSIS: We will include peer-reviewed observational or interventional studies involving individuals aged 18 or older with a diagnosis of substance use (e.g., alcohol, benzodiazepines, cannabis, cocaine, opioids, methamphetamine, or nicotine) who use actigraphy to assess sleep compared to matched controls. Studies will be excluded during screening if they do not use actigraphy, do not include populations with SUDs, or focus on participants younger than 18. There will be no restrictions on location, setting, or language. Databases to be searched include PubMed, Scopus, Web of Science, ProQuest, ClinicalTrials.gov, CINAHL, PsycINFO, and Embase. Titles and abstracts will be screened in the first phase, followed by full-text screening using eligibility criteria. At least two independent reviewers will assess risk of bias using the Risk Of Bias In Non-randomized Studies of Exposures (ROBINS-E) tool. A synthesis will summarize key findings, including study characteristics, population differences, and methodological variations. DISCUSSION: This review will offer a clear and comprehensive assessment of the current literature on actigraphy to examine sleep in SUD and to inform future research to study sleep and its implications in SUD populations. PROTOCOL REGISTRATION NUMBER: International Prospective Register for Systematic Reviews (PROSPERO) number CRD420251072028.
Keywords: MEDLINE; Prospective cohort study; Protocol (science); Substance use; Systematic review; dept.psy

Conflict and cooperation in male–male partnerships alter paternal care behavior in the ocellated wrasse - Hellmann, Jennifer; Stiver, Kelly; Marsh‐Rollo, Susan; Alonzo, Suzanne (Behavioral Ecology, 2025)
Keywords: Biology; Fish; Fishery; Genetics; Paternal care; Symphodus ocellatus; Wrasse; Zoology; dept.psy; parental care; plasticity; reproduction; sexual selection; temperature

Breaking the truth bias: the impact of comparable truth baselines and reality interview on veracity judgments by laypeople and police officers - Bogaard, Glynis; Nieuwkamp, Veerle; Colwell, Kevin (Police Practice and Research, 2025)
This study examined whether embedding baselining within the Reality Interview (RI) protocol enhances intuitive veracity judgments. Baselining involves using a person's truthful verbal behavior as a reference point for evaluating the veracity of subsequent statements. We hypothesized that access to a comparable truth baseline (CTB) would improve veracity judgment accuracy. Eyewitnesses of a mock crime were interviewed with the RI and instructed to respond either honestly or deceptively. Laypeople (Experiment 1) and police officers (Experiment 2) evaluated these statements with or without a CTB. With a CTB, laypeople showed significantly higher accuracy in detecting deception and a reduced truth bias. However, police officers showed no improvement, maintaining chance-level performance regardless of statement veracity. These findings suggest that CTBs enhance lie detection in laypeople but not in trained professionals. Future research should explore tailored approaches to improving veracity judgments, perhaps incorporating specific guidelines on how to best use available cues.
Keywords: Baseline (sea); Comparable Truth Baseline; Deception; Interview; Lie detection; Point (geometry); Protocol (science); Reality Interview; Statement (logic); Trustworthiness; dept.psy; lie detection; verbal cues

Pharmacotherapies for stimulant use disorder and co-occurring attention deficit hyperactivity disorder: protocol for a systematic review and a meta-analysis - Oliva, Henrique; Pulido-Saavedra, Alejandra; Paredes-Naveda, Alisson; Forselius, Emerson; Potenza, Marc; Jegede, Oluwole; Angarita, Gustavo (Frontiers in Psychiatry, 2025)
Background Stimulant use disorder (StUD) and attention-deficit/hyperactivity disorder (ADHD) frequently co-occur. This comorbidity complicates treatment and worsens clinical outcomes. Despite the high prevalence, shared vulnerability and clinical relevance of this comorbidity, evidence on effective pharmacotherapies among individuals with this dual diagnosis remains limited. Materials and methods This systematic review protocol is reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) statement and will include randomized controlled trials involving adults with comorbid StUD (cocaine, amphetamines, or methamphetamines) and ADHD. The following databases will be searched: PubMed, Embase, Scopus, and Web of Science. Covidence will be used to support independent screening and data extraction. Two reviewers will independently screen studies (title/abstract and full text). One author will extract data, which will be independently verified by a second reviewer. Quality assessment of included articles will be assessed using the Cochrane Risk of Bias instrument, and certainty of the evidence for each outcome will be assessed using Grading of Recommendations, Assessment, Development and Evaluations (GRADE) methodology. Primary outcomes include duration of continuous abstinence, odds of stimulant-negative urine samples, ADHD symptom changes, and medication adverse events. Where feasible, meta-analyses will be conducted using random-effects models. Significance and dissemination This review will synthesize existing evidence on the efficacy of pharmacotherapies (stimulants and non-stimulants) for individuals with co-occurring StUD and ADHD. The results of this study will likely inform clinical practice by evaluating outcomes such as reduction in stimulant use and abstinence, and improvement in ADHD symptoms. Findings will be disseminated through peer-reviewed publication and presentations to reach both clinical and academic audiences. Systematic review registration PROSPERO, CRD420250655356.
Keywords: Alternative medicine; Atomoxetine; Attention deficit hyperactivity disorder; Clinical psychology; Internal medicine; Medicine; Meta-analysis; Methylphenidate; Protocol (science); Psychiatry; Psychology; Stimulant; attention deficit hyperactivity disorder; co-occurring disorder; cocaine; dept.psy; methamphetamine; stimulant use disorder

Masked-Speech Recognition and Self-Reported Functional Listening in Autistic Young Adults - Wasiuk, Peter; Cook, Barbara; Irwin, Julia (Journal of Speech Language and Hearing Research, 2025)
Keywords: Active listening; Audiology; Autism; Cognitive psychology; Communication; Developmental psychology; Medicine; Perception; Psychology; Speech perception; dept.cmd; dept.psy

Assessment criteria indicative of deception (ACID): Replication and gender differences - Suckle-Nelson, Jessica A.; Colwell, Kevin; Hiscock-Anisman, Cheryl; Florence, Samantha; Youschak, Kimberly E.; Duarte, Arianne (The Open Criminology Journal, 2010)
Keywords: dept.psy

Writing Wisdom, Reviewing Identity: Positive Outcomes of Participating in a Memoir Course for Older Adults - Bivona, Marissa A.; Kahlbaugh, Patricia E.; Budnick, Christopher J. (The International Journal of Reminiscence and Life Review, 2020)
Constructing a personal narrative and consolidating identity is an ongoing process that becomes pressing in the face of mortality. The current pilot study examined the process of life review in a sample of older people, specifically examining the effects of participation in a memoir course on wisdom, identity, and well-being. We hypothesized that wisdom, identity fidelity and coherence, and subjective well-being would increase for those in the memoir group compared to a control. Eighteen elderly individuals from two senior retirement communities were randomly assigned to participate in weekly classes, for four weeks, either to work on a memoir or discuss films (control group). After engaging in the process of organizing their life story and writing about important memories, the nine individuals in the memoir group scored significantly higher on self-report measures of wise reminiscence, identity fidelity, and subjective well-being compared to those in the control group. Furthermore, exploratory analyses found that wise reminiscence statistically mediated relationships between the memoir condition and the outcome measures of identity fidelity, identity coherence, and subjective well-being. These findings point to the benefits of memoir writing for positive aging as well as potential mechanisms underlying its effectiveness.
Number: 1
Keywords: Identity; Life Review; Narrative; Subjective Well-Being; Wisdom; dept.psy

Normal Probability Distributions - Hauselt Jr, William J (Statistics for Social Science | Top Hat, 2016)
Keywords: dept.psy

Turning molehills into mountains: Sleepiness increases workplace interpretive bias - Barber, Larissa K.; Budnick, Christopher J. (Journal of Organizational Behavior, 2015)
Three studies draw from evolutionary theory to assess whether sleepiness increases interpretive biases in workplace social judgments. Study 1 established a relationship between sleepiness and interpretive bias using ambiguous interpersonal scenarios from a measure commonly used in personnel selection (N = 148). Study 2 explored the boundary conditions of the sleepiness–interpretive bias link via an experimental online field survey of U.S. adults (N = 433). Sleepiness increased interpretive bias when social threats were clearly present (unfair workplace) but did not affect bias in the absence of threat (fair workplace). Study 3 replicated and extended findings from the previous two studies using objective measures of sleep loss and a quasi-experimental manipulation of minor sleep loss (N = 175). Negative affect, ego depletion, or personality variables did not influence the observed relationships. Overall, results suggest that a self-protection/evolutionary perspective best explains the effects of sleepiness on workplace interpretive biases. These studies advance the current research on sleep in organizations by adding a cognitive “threat interpretation” bias approach to past work examining the emotional reaction/behavioral side of sleep disruption. Interpretive biases due to sleepiness may have significant implications for employee health and counterproductive behavior. Copyright © 2015 John Wiley & Sons, Ltd.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/job.1992
Keywords: Conditional Reasoning Test of Aggression; dept.psy; fairness; interpretive bias; sleep; work perceptions

Behind sleepy eyes: Implications of sleep loss for organizations and employees - Budnick, Christopher J.; Barber, Larissa K. (Translational Issues in Psychological Science, 2015)
Sleep loss and daytime sleepiness are common experiences for employees across many occupations. Although researchers commonly focus on the detrimental effects of sleep issues for attention and vigilance during task performance, we review research that examines how sleep issues influence interpretations of, and interactions in, the work environment. This review begins by differentiating between sleep loss and sleepiness. We then highlight how sleep issues can negatively bias the interpretation of environmental information and result in aggressive responding. We also examine how sleep issues impair self-regulatory ability and contribute to workplace deviance. After each section, we discuss the implications of these findings for the work environment. A closer examination of sleep’s influence on workplace interactions can spur a beneficial discussion for researchers across a variety of disciplines and employees across all organizational levels. (PsycInfo Database Record (c) 2022 APA, all rights reserved)
Place: US
Keywords: Aggressive Behavior; Employee Productivity; Health; Occupations; Organizations; Personnel; Self-Control; Sleep Deprivation; Sleepiness; Stress; Working Conditions; dept.psy

Attitudes About Aging and Beliefs About When you Have Been or Will be Your Best Self - Kahlbaugh, Patricia; Biblekaj, Viktoria; Shortell, Malori (The International Journal of Aging and Human Development, 2025)
Keywords: Anxiety; Clinical psychology; Developmental psychology; Gerontology; Healthy aging; Internalization; Medicine; Psychiatry; Psychology; Successful aging; dept.psy; peer-reviewed

Fear of Missing Out’s (FoMO) relationship with moral judgment and behavior - McKee, Paul C.; Senthilnathan, Ithika; Budnick, Christopher J.; Bind, Marie-Abèle; Antonios, Imad; Sinnott-Armstrong, Walter (PLOS ONE, 2024)
Across three online studies, we examined the relationship between the Fear of Missing Out (FoMO) and moral cognition and behavior. Study 1 (N = 283) examined whether FoMO influenced moral awareness, judgments, and recalled and predicted behavior of first-person moral violations in either higher or lower social settings. Study 2 (N = 821) examined these relationships in third-person judgments with varying agent identities in relation to the participant (agent = stranger, friend, or someone disliked). Study 3 (N = 604) examined the influence of recalling activities either engaged in or missed out on these relationships. Using the Rubin Causal Model, we created hypothetical randomized experiments from our real-world randomized experimental data with treatment conditions for lower or higher FoMO (median split), matched for relevant covariates, and compared differences in FoMO groups on moral awareness, judgments, and several other behavioral outcomes. Using a randomization-based approach, we examined these relationships with Fisher Tests and computed 95% Fisherian intervals for constant treatment effects consistent with the matched data and the hypothetical FoMO intervention. All three studies provide evidence that FoMO is robustly related to giving less severe judgments of moral violations. Moreover, those with higher FoMO were found to report a greater likelihood of committing moral violations in the past, knowing people who have committed moral violations in the past, being more likely to commit them in the future, and knowing people who are likely to commit moral violations in the future.
Keywords: Behavior; Interpersonal relationships; Machine learning; Memory recall; Moral philosophy; Personality; Religion; Social media; dept.csc; dept.psy; peer-reviewed

Using the Listening2Faces App with Three Young Adults with Autism: A Feasibility Study - Baron, Alisa; Harwood, Vanessa; Woodard, Cooper; Anderson, Kaitlyn; Fernandes, Barbara; Sullivan, Jessica; Irwin, Julia (Advances in Neurodevelopmental Disorders, 2024)
Abstract Objectives Listening2Faces (L2F) is a therapeutic, application-based training program designed to improve audiovisual speech perception for persons with communication disorders. The purpose of this research was to investigate the feasibility of using the L2F application with young adults with autism and complex communication needs. Methods Three young adults with autism and complex communication needs completed baseline assessments and participated in training sessions within the L2F application. Behavioral supports, including the use of cognitive picture rehearsal, were used to support engagement with the L2F application. Descriptive statistics were used to provide (1) an overview of the level of participation in L2F application with the use of behavioral supports and (2) general performance on L2F application for each participant. Results All three participants completed the initial auditory noise assessment (ANA) as well as 8 or more levels of the L2F application with varying accuracy levels. One participant completed the entire L2F program successfully. Several behavioral supports were used to facilitate participation; however, each individual demonstrated varied levels of engagement with the application. Conclusions The L2F application may be a viable intervention tool to support audiovisual speech perception in persons with complex communication needs within a school-based setting. A review of behavioral supports and possible beneficial modifications to the L2F application for persons with complex communication needs are discussed.
Keywords: dept.psy; peer-reviewed

Sleep Health among Children Adopted from Foster Care: The Moderating Effect of Parent–Child Sleep Interactions - Cifre, Anthony B.; Budnick, Christopher J.; Bick, Johanna; McGlinchey, Eleanor L.; Ripple, Carol H.; Wolfson, Amy R.; Alfano, Candice A. (Behavioral Sleep Medicine, 2024)
Keywords: dept.psy; peer-reviewed

A review of the kappa opioid receptor system in opioid use - Cayir, Salih; Zhornitsky, Simon; Barzegary, Alireza; Sotomayor-Carreño, Esteban; Sarfo-Ansah, Wonder; Funaro, Melissa C.; Matuskey, David; Angarita, Gustavo (Neuroscience & Biobehavioral Reviews, 2024)
The kappa opioid receptor (KOR) system is implicated in dysphoria and as an “anti-reward system” during withdrawal from opioids. However, no clear consensus has been made in the field, as mixed findings have been reported regarding the relationship between the KOR system and opioid use. This review summarizes the studies to date on the KOR system and opioids. A systematic scoping review was reported following PRISMA guidelines and conducted based on the published protocol. Comprehensive searches of several databases were done in the following databases: MEDLINE, Embase, PsycINFO, Web of Science, Scopus, and Cochrane. We included preclinical and clinical studies that tested the administration of KOR agonists/antagonists or dynorphin and/or measured dynorphin levels or KOR expression during opioid intoxication or withdrawal from opioids. One hundred studies were included in the final analysis. Preclinical administration of KOR agonists decreased drug-seeking/taking behaviors and opioid withdrawal symptoms. KOR antagonists showed mixed findings, depending on the agent and/or type of withdrawal symptom. Administration of dynorphins attenuated opioid withdrawal symptoms both in preclinical and clinical studies. In the limited number of available studies, dynorphin levels were found to increase in cerebrospinal fluid (CSF) and peripheral blood lymphocytes (PBL) of opioid use disorder subjects (OUD). In animals, dynorphin levels and/or KOR expression showed mixed findings during opioid use. The KOR/dynorphin system appears to have a multifaceted and complex nature rather than simply functioning as an anti-reward system. Future research in well-controlled study settings is necessary to better understand the clinical role of the KOR system in opioid use.
Keywords: Dynorphins; Opioid use disorder; Opioids; dept.psy; peer-reviewed; κ-opioid receptor

Best Darn Statistics Workbook Ever - Hauselt, William J.; Mugno, Raymond (Kendall Hunt Publishing, 2021)
Keywords: dept.mat; dept.psy

Age differences in emotional reactions to ageist memes and changes in age of one's Best Self - Kahlbaugh, Patricia; Ramos-Arvelo, Jacklyn; Brenning, Madison; Huffman, Loreen (Journal of Aging Studies, 2024)
Memes on social media can carry ageist messages and can elicit reactions that are both emotional and self-evaluative. The present study investigates age-related differences in nine discrete emotions and in the evaluation of when individuals have been or will be their best selves. Participants (n = 360) representing young (m = 26 years), middle-aged (m = 39 years) and older adults (m = 63 years) were randomly assigned to view either non-ageist (animals) or ageist (e.g., incompetent older people) memes. After viewing memes, we assessed nine emotional reactions (i.e., fear, anger, sadness, happiness, anxiety, discomfort, disgust, surprise, enjoyment) and Best Self evaluations. Younger and middle-aged people reported more intense emotional reactions to memes than older people, with the exception that older people reported more discomfort and disgust in response to ageist versus non-ageist memes. Younger adults were less surprised by ageist memes (vs. non-ageist) and for all age groups ageist memes (vs. non-ageist) elicited less happiness and enjoyment and were less likely to be shared. With respect to evaluations of one's Best Self, older individuals were more likely to report being their best selves in the past, while after viewing ageist memes, younger individuals were more likely to report being their best selves in the future. Emotions of disgust and discomfort were related to identifying one's Best Self as further in the past. The current study adds to the literature on the impact of ageism by examining age-related differences in the emotions and self-evaluations experienced when confronted with memes on social media.
Keywords: Ageism; Emotions; Self-evaluations; Social media/memes; dept.psy; peer-reviewed

Assessing the efficacy of baselining in deception detection: A comparative analysis of the reality interview and structured interview - Bogaard, Glynis; van de Bovekamp, Anne Margreet; Colwell, Kevin (Acta Psychologica, 2024)
Detecting deception is challenging; there exists no universal cue that gives away deceit and people vary greatly in how they communicate. One way to potentially improve deception detection is by comparing multiple responses of the same individual to identify verbal deviations – a method known as baselining. This study examined the impact of baselining embedded in a specific interview protocol to improve lie detection. Participants (N = 179) viewed mock crimes and were instructed to lie or tell the truth about what they witnessed. Next, they were interviewed including a truthful baseline (Reality Interview Modified: RIM), or no baseline (Reality Interview: RI; Structured Interview: SI). Results showed that truth tellers in the SI and RI conditions provided more details than liars during free recall, while no detail differences emerged for the RIM condition. Follow-up questions in all conditions showed truth tellers offered more details than liars. Surprisingly, we found no evidence that verbal deviations from a baseline can be used as effective indicators of deception. In sum, further research is needed to explore the best application of baselining for lie detection purposes.
Keywords: Baselining; Deception detection; Reality interview; Verbal cues; dept.psy; peer-reviewed

Preliminary Findings From the Hearing Assessment in Response to Noise Screener: A New Pediatric Tool for Measuring Speech Identification in Noise - Irwin, Julia; Sullivan, Jessica; Fernandes, Barbara; Lotto, Alyssa (Perspectives of the ASHA Special Interest Groups, 2023)
Purpose: As part of the development of a speech-in-noise screener, speech recognition was measured in quiet and in an interrupted noise for 59 children with typical development according to parent report. Method: There were 39 monolingual and 20 bilingual participants. A corpus of 107 words were presented by a male and female speaker and present in the following conditions: +3 dB signal-to- noise ratio (SNR), −3 dB SNR, and quiet. Results: The participants showed increasing difficulty with speech identification as the SNR decreased. Additionally, age-related differences in accuracy were observed at each noise level. Conclusion: Our findings provide preliminary support for the utility and efficacy of a speech-in-noise screener for use with children.
Keywords: SCSU-student; dept.psy

The role of combat exposure on drinking behavior and subjective well-being: A Rubin Causal Model approach. - McKee, Paul; Budnick, Christopher J.; Walters, Kenneth S.; Bind, Marie-Abèle (Psychological Trauma: Theory, Research, Practice, and Policy, 2024)
Keywords: dept.psy; peer-reviewed

Social Environment Influences the Temporal Dynamics of Sneak-Spawning in a Fish with Alternative Reproductive Tactics - Kustra, Matthew C.; Stiver, Kelly A.; Marsh-Rollo, Susan; Hellmann, Jennifer K.; Alonzo, Suzanne H. (The American Naturalist, 2023)
Several predictions of sperm competition theory are not well supported empirically. One potential reason is that most current theory and empirical research ignore how the social environment influence the temporal dynamics of mating. We propose that understanding these dynamics is key to understanding sexual selection and improving the predictive power of theory. To demonstrate the importance of these dynamics, we quantify how males’ social role, interactions among males, and current social environment influence the timing of mating in Symphodus ocellatus, a species with three alternative male reproductive tactics. Nesting males spawn synchronously with females; sneakers and satellites sneak-spawn with some time delay. Satellites also cooperate with nesting males. We found that satellites have shorter sneak-spawning delays than sneakers, a benefit of their cooperation with nesting males. Sneak-spawning delays decreased with increasing nest activity for sneakers but not for satellites, suggesting that sneakers may benefit from increased sperm competition intensity. Current sperm competition models ignore this potential benefit, which may be why the prediction that males should decrease investment when sperm competition involves more than two males is not well supported. Our study provides insight into mechanisms that drive variation in the timing of spawning, which could explain mismatches between theoretical and empirical results.
Keywords: alternative mating tactics; cooperation; dept.psy; peer-reviewed; reproductive competition; sexual selection; sneak-spawning; sperm competition

Developmental Themes in the Narrative of Adults with Early International Experiences - Abe, Jo Ann A. (Journal of Adult Development, 2023)
This study extends research on adult narrative identity in two major ways. First, it focuses on Adult Third Culture Kids (ATCKs), which refer to individuals who spent a part of their early developmental years abroad. In spite of the fact that they are an important demographic to study in this rapidly globalizing world, they have tended to be neglected in the field of psychology. Second, this study incorporates the cutting-edge tools of automated language analysis to extract developmental themes from autobiographical narratives using a bottom-up exploratory approach, as well as to identify psychological patterns and processes associated with the themes. The participants (N = 350; 18–80 + years old) were recruited from an alumni office of an international school and asked to write a narrative about the impact their international experiences had on their development. The meaning extraction method (MEM) yielded four developmental themes, which were remarkably consistent with the recurring themes that emerge from past research on adult narrative identity as well as ATCKs: past focus, communion, agency, and global focus. These four developmental themes, in turn, showed theoretically coherent patterns of relations with the demographic variables, linguistic markers of psychological patterns and processes, as well as self-reports of dimensions of well-being.
Keywords: Adult third culture kids (ATCKs); LIWC; MEH; Meaning extraction method; Narrative identity; dept.psy; peer-reviewed

Event-Related Potentials in Assessing Visual Speech Cues in the Broader Autism Phenotype: Evidence from a Phonemic Restoration Paradigm - Harwood, Vanessa; Baron, Alisa; Kleinman, Daniel; Campanelli, Luca; Irwin, Julia; Landi, Nicole (Brain Sciences, 2023)
Audiovisual speech perception includes the simultaneous processing of auditory and visual speech. Deficits in audiovisual speech perception are reported in autistic individuals; however, less is known regarding audiovisual speech perception within the broader autism phenotype (BAP), which includes individuals with elevated, yet subclinical, levels of autistic traits. We investigate the neural indices of audiovisual speech perception in adults exhibiting a range of autism-like traits using event-related potentials (ERPs) in a phonemic restoration paradigm. In this paradigm, we consider conditions where speech articulators (mouth and jaw) are present (AV condition) and obscured by a pixelated mask (PX condition). These two face conditions were included in both passive (simply viewing a speaking face) and active (participants were required to press a button for a specific consonant–vowel stimulus) experiments. The results revealed an N100 ERP component which was present for all listening contexts and conditions; however, it was attenuated in the active AV condition where participants were able to view the speaker’s face, including the mouth and jaw. The P300 ERP component was present within the active experiment only, and significantly greater within the AV condition compared to the PX condition. This suggests increased neural effort for detecting deviant stimuli when visible articulation was present and visual influence on perception. Finally, the P300 response was negatively correlated with autism-like traits, suggesting that higher autistic traits were associated with generally smaller P300 responses in the active AV and PX conditions. The conclusions support the finding that atypical audiovisual processing may be characteristic of the BAP in adults.
1 citations (Crossref) [2023-10-31] Number: 7
Keywords: audiovisual; dept.psy; event-related potentials; peer-reviewed; phonemic restoration; speech perception

Dwight Neighborhood Study Area Report: A Center for Urban Studies Project - Levi, Benjamin N.; Muller, Bruce P.; Gonzales, J. Ernest (Southern Connecticut State College)
Keywords: Cities and towns; Connecticut; New Haven; New Haven (Conn.); New Haven; Urban policy; Study and teaching; dept.psy; faculty_collection

Lifespan Development. - Anthis, Kristine (2007)
Keywords: dept.psy; faculty_collection; sabbatical_report

EdPsych Modules. - Durwin, Cheryl C. (2007)
Keywords: dept.psy; faculty_collection; sabbatical_report

Re-Examining the Long-Term Effects of Experiencing Parental Death in Childhood on Adult Psychopathology. - Jacobs, John R. (2006)
Keywords: dept.psy; faculty_collection

Learning and Behavior. - Mazur, James E. (2004)
Keywords: dept.psy; faculty_collection; sabbatical_report

Resource Manual for Psychology and Law. - Tolchin, Gerald (Fall;Psychology., 2000)
Keywords: dept.psy; faculty_collection; sabbatical_report

Animal Choice Behavior. - Mazur, James (Fall ; Psychology., 1995)
Keywords: dept.psy; faculty_collection; sabbatical_report

Psychology and the Law. - Tolchin, Gerald (1991)
Keywords: dept.psy; faculty_collection; sabbatical_report

Guide for Psychology Majors: A Student Handbook. - Flannelly, Linda (1990)
Keywords: dept.psy; faculty_collection; sabbatical_report

Revision of an Interactive Computer Program. - Harmon, Duane (1990)
Keywords: dept.psy; faculty_collection; sabbatical_report

(MMPI and Rorschach) - Muller, Bruce (1990)
Keywords: dept.psy; faculty_collection; sabbatical_report

Extending the Developmental Interpretation of Delusions and Hallucinations.. - Glick, Marion (1988)
Keywords: dept.psy; faculty_collection; sabbatical_report

Neural and Behavioral Differences in Speech Perception for Children With Autism Spectrum Disorders Within an Audiovisual Context - Irwin, Julia; Harwood, Vanessa; Kleinman, Daniel; Baron, Alisa; Avery, Trey; Turcios, Jacqueline; Landi, Nicole (Journal of Speech, Language, and Hearing Research, 2023)
Purpose: Reduced use of visible articulatory information on a speaker's face has been implicated as a possible contributor to language deficits in autism spectrum disorders (ASD). We employ an audiovisual (AV) phonemic restoration paradigm to measure behavioral performance (button press) and event-related potentials (ERPs) of visual speech perception in children with ASD and their neurotypical peers to assess potential neural substrates that contribute to group differences. Method: Two sets of speech stimuli, /ba/–“/a/” (“/a/” was created from the /ba/ token by a reducing the initial consonant) and /ba/–/pa/, were presented within an auditory oddball paradigm to children aged 6–13 years with ASD (n = 17) and typical development (TD; n = 33) within two conditions. The AV condition contained a fully visible speaking face; the pixelated (PX) condition included a face, but the mouth and jaw were PX, removing all articulatory information. When articulatory features were present for the /ba/–“/a/” contrast, it was expected that the influence of the visual articulators would facilitate a phonemic restoration effect in which “/a/” would be perceived as /ba/. ERPs were recorded during the experiment while children were required to press a button for the deviant sound for both sets of speech contrasts within both conditions. Results: Button press data revealed that TD children were more accurate in discriminating between /ba/–“/a/” and /ba/–/pa/ contrasts in the PX condition relative to the ASD group. ERPs in response to the /ba/–/pa/ contrast within both AV and PX conditions differed between children with ASD and TD children (earlier P300 responses for children with ASD). Conclusion: Children with ASD differ in the underlying neural mechanisms responsible for speech processing compared with TD peers within an AV context.
0 citations (Crossref) [2023-10-31]
Keywords: dept.psy; peer-reviewed

Longitudinal Effects of Early Reading Interventions on Normed, Standardized Reading Outcome Measures. - Carroll, Deborah A. (2019)
Keywords: dept.psy; faculty_collection; sabbatical_report

Learning and Behavior - Mazur, James E. (Pearson, 2013)
Keywords: Learning; Psychology of; Conditioned response; Behavior modification; Psychology; Comparative; dept.psy

Mrs. Job - Affinito, Mona Gustafson (iUniverse Inc, 2009)
"Beautiful, feisty Dara, rising from nomad to princess, experiences joy, spiritual and marital conflict, and unspeakable trials, without surrendering her love for Job and for her best friend Adah"–p. 4 of Cover.
Keywords: Christianity; Fiction; Religious fiction; American; Fiction; Suffering; Fiction; Wives; Job (Biblical figure); Religious aspects; dept.psy; faculty_collection

Forgiving One Page at a Time: The Diary of Your Journey to Restoration and Confidence - Affinito, Mona Gustafson (AuthorHouse, 2007)
Keywords: Forgiveness; dept.psy; faculty_collection

Learning and Behavior - Mazur, James E. (Pearson/Prentice Hall, 2006)
Keywords: Learning; Psychology of; Textbooks; Textbooks; Behavior modification; Textbooks; Conditioned response; Textbooks; Psychology; Comparative; dept.psy; faculty_collection

Sabbatical Leave Report - Sherman, William M. (2005)
Sabbatical leave report outlining time spent revising the textbook, "Behavior modification", conducting a research project entitled "Motherhood ideology, role balance, and health-promoting behaviors of non-tenured academic mothers with preschool children", and working on course proposals for the Department of Psychology.
Keywords: dept.psy; faculty_collection; sabbatical_report

The Roles of Vasopressin and Oxytocin in Memory Processing - McEwen, Barbara B. (Elsevier Academic Press, 2004)
Keywords: Physiological aspects; Research; Memory; Research; Neuropeptides; Research; Oxytocin; Vasopressin; dept.psy; faculty_collection

Emergence of Uncertainty: A Microgenetic Study of the Preschool Period, Sabbatical Leave Report - Kahlbaugh, Patricia (2003)
Keywords: dept.psy; faculty_collection; sabbatical_report

When to Forgive - Affinito, Mona Gustafson (New Harbinger Publications, 1999)
Keywords: Forgiveness; dept.psy; faculty_collection

Helping with Forgiveness Decisions: A Brief Guide for Counselors - Affinito, Mona Gustafson (Manisses Communications Group, Inc., 1998)
Keywords: Forgiveness; dept.psy; faculty_collection

The Nature of Visual Illusion - Fineman, Mark B. (Dover Publications, 1996)
Keywords: Problems; exercises; etc; Visual perception; Visual perception; dept.psy; faculty_collection

Learning and Behavior - Mazur, James E. (Prentice Hall, 1994)
Keywords: Learning; Psychology of; Conditioned response; Behavior modification; Psychology; Comparative; dept.psy; faculty_collection

Behavior Modification - Sherman, William M. (Harper & Row, 1990)
Keywords: Behavior modification; dept.psy; faculty_collection

The Copts Since the Arab Invasion: Strangers in Their Land - Karas, Shawky F. (American, Canadian, and Australian C. Coptic Associations, 1985)
Keywords: 1952-1970; Copts; Egypt; Ethnic relations; Egypt; Politics and government; dept.psy

The Inquisitive Eye - Fineman, Mark B. (Oxford University Press, 1981)
Keywords: Problems; exercises; etc; Visual perception; Visual perception; dept.psy; faculty_collection

Parent Conferences in the Schools: Procedures for Developing Effective Partnership - Losen, Stuart M.; Diament, Bert; Losen, Joyce Garskof (Allyn and Bacon, 1978)
Keywords: Parent-teacher conferences; dept.psy; faculty_collection

Where on the face do we look during phonemic restoration: An eye-tracking study - Baron, Alisa; Harwood, Vanessa; Kleinman, Daniel; Campanelli, Luca; Molski, Joseph; Landi, Nicole; Irwin, Julia (Frontiers in Psychology, 2023)
Face to face communication typically involves audio and visual components to the speech signal. To examine the effect of task demands on gaze patterns in response to a speaking face, adults participated in two eye-tracking experiments with an audiovisual (articulatory information from the mouth was visible) and a pixelated condition (articulatory information was not visible). Further, task demands were manipulated by having listeners respond in a passive (no response) or an active (button press response) context. The active experiment required participants to discriminate between speech stimuli and was designed to mimic environmental situations which require one to use visual information to disambiguate the speaker’s message, simulating different listening conditions in real-world settings. Stimuli included a clear exemplar of the syllable /ba/ and a second exemplar in which the formant initial consonant was reduced creating an /a/−like consonant. Consistent with our hypothesis, results revealed that the greatest fixations to the mouth were present in the audiovisual active experiment and visual articulatory information led to a phonemic restoration effect for the /a/ speech token. In the pixelated condition, participants fixated on the eyes, and discrimination of the deviant token within the active experiment was significantly greater than the audiovisual condition. These results suggest that when required to disambiguate changes in speech, adults may look to the mouth for additional cues to support processing when it is available.
0 citations (Crossref) [2023-10-31]
Keywords: dept.psy; peer-reviewed

Motivation states to move, be physically active and sedentary vary like circadian rhythms and are associated with affect and arousal - Budnick, Christopher J.; Stults-Kolehmainen, Matthew; Dadina, Cyrus; Bartholomew, John B.; Boullosa, Daniel; Ash, Garret I.; Sinha, Rajita; Blacutt, Miguel; Haughton, Adrian; Lu, Tom (Frontiers in Sports and Active Living, 2023)
IntroductionMotivation to be physically active and sedentary is a transient state that varies in response to previous behavior. It is not known: (a) if motivational states vary from morning to evening, (b) if they are related to feeling states (arousal/hedonic tone), and (c) whether they predict current behavior and intentions. The primary purpose of this study was to determine if motivation states vary across the day and in what pattern. Thirty adults from the United States were recruited from Amazon MTurk.MethodsParticipants completed 6 identical online surveys each day for 8 days beginning after waking and every 2–3 h thereafter until bedtime. Participants completed: (a) the CRAVE scale (Right now version) to measure motivation states for Move and Rest, (b) Feeling Scale, (c) Felt Arousal Scale, and (d) surveys about current movement behavior (e.g., currently sitting, standing, laying down) and intentions for exercise and sleep. Of these, 21 participants (mean age 37.7 y; 52.4% female) had complete and valid data.ResultsVisual inspection of data determined that: a) motivation states varied widely across the day, and b) most participants had a single wave cycle each day. Hierarchical linear modelling revealed that there were significant linear and quadratic time trends for both Move and Rest. Move peaked near 1500 h when Rest was at its nadir. Cosinor analysis determined that the functional waveform was circadian for Move for 81% of participants and 62% for Rest. Pleasure/displeasure and arousal independently predicted motivation states (all p's < .001), but arousal had an association twice as large. Eating, exercise and sleep behaviors, especially those over 2 h before assessment, predicted current motivation states. Move-motivation predicted current body position (e.g., laying down, sitting, walking) and intentions for exercise and sleep more consistently than rest, with the strongest prediction of behaviors planned for the next 30 min.DiscussionWhile these data must be replicated with a larger sample, results suggest that motivation states to be active or sedentary have a circadian waveform for most people and influence future behavioral intentions. These novel results highlight the need to rethink the traditional approaches typically utilized to increase physical activity levels.
2 citations (Crossref) [2023-10-31]
Keywords: dept.psy; peer-reviewed

Qualitative and quantitative evidence of motivation states for physical activity, exercise and being sedentary from university student focus groups - Stults-Kolehmainen, Matthew A.; Gilson, Todd A.; SantaBarbara, Nicholas; McKee, Paul C.; Sinha, Rajita; Bartholomew, John B.; Boullosa, Daniel; Budnick, Christopher J.; Bueno, Fabio Amador; Haughton, Adrian; Barker, Jessica L.; Ash, Garrett I. (Frontiers in Sports and Active Living, 2023)
Motivation for physical activity and sedentary behaviors (e.g., desires, urges, wants, cravings) varies from moment to moment. According to the WANT model, these motivation states may be affectively-charged (e.g., felt as tension), particularly after periods of maximal exercise or extended rest. The purpose of this study was to examine postulates of the WANT model utilizing a mixed-methods approach. We hypothesized that: (1) qualitative evidence would emerge from interviews to support this model, and (2) motivation states would quantitatively change over the course of an interview period. Seventeen undergraduate students (mean age = 18.6y, 13 women) engaged in focus groups where 12 structured questions were presented. Participants completed the “right now” version of the CRAVE scale before and after interviews. Qualitative data were analyzed with content analysis. A total of 410 unique lower-order themes were classified and grouped into 43 higher order themes (HOTs). From HOTs, six super higher order themes (SHOTs) were designated: (1) wants and aversions, (2) change and stability, (3) autonomy and automaticity, (4) objectives and impulses, (5) restraining and propelling forces, and (6) stress and boredom. Participants stated that they experienced desires to move and rest, including during the interview, but these states changed rapidly and varied both randomly as well as systematically across periods of minutes to months. Some also described a total absence of desire or even aversion to move and rest. Of note, strong urges and cravings for movement, typically from conditions of deprivation (e.g., sudden withdrawal from exercise training) were associated with physical and mental manifestations, such as fidgeting and feeling restless. Urges were often consummated with behavior (e.g., exercise sessions, naps), which commonly resulted in satiation and subsequent drop in desire. Importantly, stress was frequently described as both an inhibitor and instigator of motivation states. CRAVE-Move increased pre-to-post interviews (p < .01). CRAVE-Rest demonstrated a trend to decline (p = .057). Overall, qualitative and quantitative data largely corroborated postulates of the WANT model, demonstrating that people experience wants and cravings to move and rest, and that these states appear to fluctuate significantly, especially in the context of stress, boredom, satiety, and deprivation.
2 citations (Crossref) [2023-10-31]
Keywords: dept.psy; peer-reviewed

Consumer choices with variations in item price, delay, and opportunity cost - McKerchar, Todd L.; Mazur, James E. (Journal of the Experimental Analysis of Behavior)
Tversky and Kahneman (1981) told participants to imagine they were at a store about to purchase an item. They were asked if they would be willing to drive 20 min to another store to receive a $5 discount on the item's price. Most participants were willing, but only when the original price of the item was small ($15); when the original price was relatively large ($125), most said they would not drive 20 min for a $5 discount. We examined this framing effect in 296 participants, but instead used a psychophysical-adjustment procedure to obtain quantitative estimates of the discount required with different (a) item prices, (b) delays until the item's receipt, and (c) opportunity costs (in “driving” vs. “delivery” tasks). We systematically replicated Tversky and Kahneman's results, but also extended them by showing a substantial influence of opportunity costs on the consumer discounts required. A behavioral model of delay discounting—additive-utility theory—accounted for 97% of the variance in these consumer discounts.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/jeab.806
Keywords: additive-utility theory; consumer choice; dept.psy; discounting; humans; opportunity cost; peer-reviewed

College student Fear of Missing Out (FoMO) and maladaptive behavior: Traditional statistical modeling and predictive analysis using machine learning - McKee, Paul C.; Budnick, Christopher J.; Walters, Kenneth S.; Antonios, Imad (PLOS ONE, 2022)
This paper reports a two-part study examining the relationship between fear of missing out (FoMO) and maladaptive behaviors in college students. This project used a cross-sectional study to examine whether college student FoMO predicts maladaptive behaviors across a range of domains (e.g., alcohol and drug use, academic misconduct, illegal behavior). Participants (N = 472) completed hard copy questionnaire packets assessing trait FoMO levels and questions pertaining to unethical and illegal behavior while in college. Part 1 utilized traditional statistical analyses (i.e., hierarchical regression modeling) to identify any relationships between FoMO, demographic variables (socioeconomic status, living situation, and gender) and the behavioral outcomes of interest. Part 2 looked to quantify the predictive power of FoMO, and demographic variables used in Part 1 through the convergent approach of supervised machine learning. Results from Part 1 indicate that college student FoMO is indeed related to many diverse maladaptive behaviors spanning the legal and illegal spectrum. Part 2, using various techniques such as recursive feature elimination (RFE) and principal component analysis (PCA) and models such as logistic regression, random forest, and Support Vector Machine (SVM), showcased the predictive power of implementing machine learning. Class membership for these behaviors (offender vs. non-offender) was predicted at rates well above baseline (e.g., 50% at baseline vs 87% accuracy for academic misconduct with just three input variables). This study demonstrated FoMO’s relationships with these behaviors as well as how machine learning can provide additional predictive insights that would not be possible through inferential statistical modeling approaches typically employed in psychology, and more broadly, the social sciences. Research in the social sciences stands to gain from regularly utilizing the more traditional statistical approaches in tandem with machine learning.
4 citations (Crossref) [2023-10-31]
Keywords: Alcohol consumption; Behavior; Cannabis; Drug interactions; Forecasting; Machine learning; Machine learning algorithms; Principal component analysis; dept.csc; dept.psy; peer-reviewed

Preparing Children for Reading Success: Hands-On Activities for Librarians, Educators, and Caregivers - Irwin, Julia; Moore, Dina (Rowman & Littlefield Publishers, 2014)
Designed to familiarize anyone who reads to young children with the essentials of promoting early and emerging literacy. Irwin and Moore share activities that can be used to foster this critical skill development, and have linked these activities to popular children's books.–
Keywords: Books and reading; Creative activities and seat work; Reading; Literacy; Children; dept.psy; faculty_collection

Empowering Young Readers: Dialogic Reading with Integrated Vocabulary Enrichment - Moore, Dina; Durwin, Cheryl C. (Rowman & Littlefield Publishers, 2022)
Keywords: dept.psy

Urges to Move and Other Motivation States for Physical Activity in Clinical and Healthy Populations: A Scoping Review Protocol - Stults-Kolehmainen, Matthew A.; Blacutt, Miguel; Bartholomew, John B.; Boullosa, Daniel; Janata, Petr; Koo, Brian B.; McKee, Paul C.; Casper, Regina; Budnick, Christopher J.; Gilson, Todd A.; Blakemore, Rebekah L.; Filgueiras, Alberto; et al. (Frontiers in Psychology, 2022)
Motivation for bodily movement, physical activity and exercise varies from moment to moment. These motivation states may be “affectively-charged,” ranging from instances of lower tension (e.g., desires, wants) to higher tension (e.g., cravings and urges). Currently, it is not known how often these states have been investigated in clinical populations (e.g., eating disorders, exercise dependence/addiction, Restless Legs Syndrome, diabetes, obesity) vs. healthy populations (e.g., in studies of motor control; groove in music psychology). The objective of this scoping review protocol is to quantify the literature on motivation states, to determine what topical areas are represented in investigations of clinical and healthy populations, and to discover pertinent details, such as instrumentation, terminology, theories, and conceptual models, correlates and mechanisms of action. Iterative searches of scholarly databases will take place to determine which combination of search terms (e.g., “motivation states” and “physical activity”; “desire to be physically active,” etc.) captures the greatest number of relevant results. Studies will be included if motivation states for movement (e.g., desires, urges) are specifically measured or addressed. Studies will be excluded if referring to motivation as a trait. A charting data form was developed to scan all relevant documents for later data extraction. The primary outcome is simply the extent of the literature on the topic. Results will be stratified by population/condition. This scoping review will unify a diverse literature, which may result in the creation of unique models or paradigms that can be utilized to better understand motivation for bodily movement and exercise.
9 citations (Crossref) [2023-10-31]
Keywords: dept.psy; peer-reviewed

Cognitive-Affective Styles of Biden and Trump Supporters: An Automated Text Analysis Study - Abe, Jo Ann A. (Social Psychological and Personality Science, 2022)
Are conservatives more simple-minded and happier than liberals? To revisit this question, 1,518 demographically diverse participants (52% females) were recruited from an online participant-sourcing platform and asked to write a narrative about the upcoming 2020 U.S. Presidential Election as well as complete self and candidates’ ratings of personality. The narratives were analyzed using three well-validated text analysis programs. As expected, extremely enthusiastic Trump supporters used less cognitively complex and more confident language than both their less enthusiastic counterparts and Biden supporters. Trump supporters also used more positive affective language than Biden supporters. More simplistic and categorical modes of thinking as well as positive emotional tone were also associated with positive perceptions of Trump’s, but not Biden’s personality. Dialectical complexity and positive emotional tone accounted for significant unique variance in predicting appraisals of Trump’s trustworthiness/integrity even after controlling for demographic variables, self-ratings of conscientiousness and openness, and political affiliation.
2 citations (Crossref) [2023-10-31]
Keywords: AutoIC; FFM; LIWC; cognitive-affective styles; dept.psy; peer-reviewed; political preferences

"Facilitation of Stereoscopic Depth Perception by a Relative-Size Cue in Ambiguous Disparity Stereograms": Erratum - Fineman, M.B. (Journal of Experimental Psychology, 1972)
Reports an error in the original article by Mark B. Fineman (Journal of Experimental Psychology, 1971[Oct], 90[2]], 215-221). Fig. 1 and Fig. 2 on pp. 216 and 217 were shown inverted. This mistake made it appear that Stimulus 1 was Stimulus 2, and that Stimulus 3 was Stimulus 4, and that the four stimuli were upside down. (The following abstract of this article originally appeared in record.) Proposed that the cue of relative size may facilitate depth perception in accordance with a crossed or uncrossed disparity in stereograms in which both tendencies are equally represented. A concurrent concept was that the latency associated with the perception of depth in random-dot stereograms may be due, in part, to a cue conflict between binocular disparity and relative size. 4 male and 2 female graduate students were given 8 presentations of 5 stereographic stimuli, in which disparity was ambiguous but relative size was systematically altered. Ss were tested for direction of depth preferences and response latency. Both the relative-size effects and an uncrossed disparity bias were evidenced in the data. The latter effect was attributed to binocular rivalry between dissimilar elements in the stereoscopic half-fields. It is concluded that depth cue relationships are more complex than had been suggested by simple dominance theories. (PsycINFO Database Record (c) 2006 APA, all rights reserved). © 1972 American Psychological Association.
0 citations (Crossref) [2023-10-31]
Keywords: ambiguous disparity stereograms; dept.psy; relative size cue; stereoscopic depth perception facilitation

The Need to Test Hypotheses About Paranoid Schizophrenia: Reply to Clementz and Sweeney - Glick, M.; Zigler, E. (American Psychologist, 1989)
0 citations (Crossref) [2023-10-31]
Keywords: Depressive Disorder; Diagnosis; Differential; Human; Psychiatric Status Rating Scales; Schizophrenia; Paranoid; article; depression; dept.psy; differential diagnosis; human; paranoid schizophrenia; psychological aspect; rating scale

Choice Behavior in Transition: Development of Preference With Ratio and Interval Schedules - Mazur, J.E. (Journal of Experimental Psychology: Animal Behavior Processes, 1992)
In Experiment 1, the choice responses of 8 pigeons were observed during 50 periods of transition. Each condition began with equal probabilities of reinforcement on 2 response keys and switched to unequal probabilities. With the ratio of the 2 probabilities held constant, preference for the higher probability developed more rapidly when the 2 probabilities were high than when they were low. In Experiment 2, each condition began with 2 equal variable-interval schedules, but later 1 key delivered 60%, 75%, or 90% of the reinforcers. The rate of approach to asymptotic performance was roughly the same with all 3 reinforcement percentages. These and previous results pose difficulties for some well-known models of acquisition, but the results are well described by a simple model that states that the strength of each response is independently increased by reinforcement and decreased by nonreinforcement.
30 citations (Crossref) [2023-10-31]
Keywords: Animal; Attention; Choice Behavior; Color Perception; Motivation; Orientation; Pigeons; Probability Learning; Problem Solving; Reinforcement Schedule; Support; U.S. Gov't; P.H.S.; animal; article; attention; color vision; decision making; dept.psy; learning; motivation; orientation; pigeon; problem solving; reinforcement

A profile analysis of psychopathology in clusters of depersonalization types - Jacobs, J.R.; Bovasso, G. (Dissociation, 1996)
Five types of depersonalization experiences based on scales developed by Jacobs and Bovasso (1992) were used to cluster subjects into six groups. Four relatively small groups which had regular depersonalization experiences were identified: the Derealized, the Self-negating, the Body-detached, and the Profoundly Depersonalized. The fifth group, the Fleetingly Depersonalized, and the sixth group, the Non-depersonalized, constituted 25% and 50% of the population, respectively. A profile analysis indicated qualitative differences between the six groups in their pathological traits, which fell along a continuum of pathological severity. The results support the validity of a multidimensional depersonalization construct which may clarify some of the contradictions and inconsistencies in the literature on depersonalization. Further, the results may facilitate clinicians' differentiation of their patients along a continuum of pathological severity based on the type and frequency of depersonalization experiences which they report.
Keywords: dept.psy; ⛔ No DOI found

Multiple Independent Identification Decisions: A Method of Calibrating Eyewitness Identifications - Pryke, S.; Lindsay, R.C.L.; Dysart, J.E.; Dupuis, P. (Journal of Applied Psychology, 2004)
Two experiments (N = 147 and N = 90) explored the use of multiple independent lineups to identify a target seen live. In Experiment 1, simultaneous face, body, and sequential voice lineups were used. In Experiment 2, sequential face, body, voice, and clothing lineups were used. Both studies demonstrated that multiple identifications (by the same witness) from independent lineups of different features are highly diagnostic of suspect guilt (G. L. Wells & R. C. L. Lindsay, 1980). The number of suspect and foil selections from multiple independent lineups provides a powerful method of calibrating the accuracy of eyewitness identification. Implications for use of current methods are discussed.
21 citations (Crossref) [2023-10-31]
Keywords: Decision Making; Humans; Recognition (Psychology); Visual Perception; article; decision making; dept.psy; human; recognition; vision

Possible selves in the lives of adult women: A short-term longitudinal study - Anthis, K. (Possible Selves: Theory, Res. and Appl., 2006)
The current study examined the number and content of possible selves in the lives of adult women over the course of a five-month interval. Based on previous empirical studies of possible selves, a variety of hypotheses were proposed that addressed cohort differences in possible selves, continuity and change in possible selves, and predicting changes in possible selves over time with ego-identity. The results indicated mixed support for the hypotheses, but basically replicated previous research findings on possible selves. The findings are discussed in terms of how they extend both descriptive and predictive knowledge of possible selves. © 2006 by Nova Science Publishers, Inc. All rights reserved.
Journal Abbreviation: Possible Selves: Theory, Res. and Appl.
Keywords: dept.psy

The test of malingered incompetence (TOMI): A forced-choice instrument for assessing cognitive malingering in competence to stand trial evaluations - Colwell, K.; Colwell, L.H.; Perry, A.T.; Wasieleski, D.; Billings, T. (American Journal of Forensic Psychology, 2008)
The TOMI consists of two 25-item, two-alternative, forced-choice scales - General Knowledge (TOMI-G) and Legal Knowledge (TOMI- L) - designed to detect malingered cognitive impairment in CST evaluations. The TOMI was derived and validated with a university sample (N = 242), with a cut score of < 21 providing maximum classification accuracy of hon est and dishonest respondents. Subsequently, the TOMI was administered to forensic inpatient residents (N = 30) and was compared to existing, well- established tests of malingering (the Rey-FIT and the TOMM). Results indi cated strong correlations and predictive agreement for both scales, and dis tinction between honest and probable dishonest respondents for the TOMI-L. A third study provided additional validation for the TOMI in distinguishing honest from dishonest student respondents (N = 120) and examined the ef fects of motivation on response style. For dishonest responders, those in the high motivation group scored significantly lower than those in the low moti vation group, further betraying their dishonesty. The utility of the TOMI as a useful, novel tool for forensic practitioners is discussed. Copyright 2008 American Journal of Forensic Psychology.
Keywords: adult; article; clinical evaluation; cognitive defect; controlled study; dept.psy; diagnostic and statistical manual of mental disorders; female; forced choice method; human; major clinical study; male; malingering; mental disease; mental performance; mental test; psychologic assessment; ⛔ No DOI found

The Tragedy of Child Care in America - Zigler, Edward; Marsland, Katherine W.; Lord, Heather (Yale University Press, 2009)
Why the United States has failed to establish a comprehensive high-quality child care program is the question at the center of this book. Edward Zigler has been intimately involved in this issue since the 1970s, and here he presents a firsthand history of the policy making and politics surrounding this important debate. Good-quality child care supports cognitive, social, and emotional development, school readiness, and academic achievement. This book examines the history of child care policy since 1969, including the inside story of America's one great attempt to create a comprehensive system of child care, its failure, and the lack of subsequent progress. Identifying specific issues that persist today, Zigler and his coauthors conclude with an agenda designed to lead us successfully toward quality care for America's children. © 2009 by Yale University. All rights reserved.
Keywords: Child care; Government policy; Services for; United States; United States; Child welfare; United States; Children; dept.psy; faculty_collection

Change in suspect's memory as a result of deception - Colwell, K.; Hiscock-Anisman, C.; Corbett, L.; Memon, A.; Hauselt, W.J.; Bonilla, Y. (American Journal of Forensic Psychology, 2011)
One hundred and eight participants either stole or replaced a stolen exam key from a professor's office. Half of the participants were instructed to respond honestly and to help with an investigation; the other half were instructed to distort their statement so they were not implicated. Participants did not know whether they would be asked to lie or report honestly during their time in the professor's office. After completing the task, participants again met with a research assistant, who instructed them whether to lie or respond honestly at a one-week follow-up. After the interview, participants completed a Likert-type post-event questionnaire. Deceivers reported significantly more anxiety and motivation not to get caught while in the office, even though there were no differences in the instructions given to the two groups until after participants left the office. Therefore, the act of deception changed their memory for their time in the office. This is important theoretically because it suggests that forming a lie script could be akin to other memories for counterfactual thinking. Practically, it is important to note that a deceptive perpetrator or detainee may never be able to actually provide an accurate account. Copyright 2011 American Journal of Forensic Psychology.
Keywords: anxiety; article; deception; dept.psy; female; follow up; honesty; human; human experiment; male; memory; motivation; normal human; offender; questionnaire; task performance; theft; thinking; ⛔ No DOI found

Forgiveness in Counseling: Caution, Definition, and Application - Affinito, M.G. (Before Forgiving: Cautionary Views of Forgiveness in Psychother., 2012)
This chapter highlights that forgiveness is a decision that clients should be helped to make and that advocacy has little place in the counseling session. It specifically confirms the value of forgiveness in the counseling setting and offers some guidelines for its effective application. There are at least three approaches to justice, altering in the extent to which they are proactive or reactive, past or future oriented, limited or general: (1) retributive justice, (2) restorative justice, and (3) pervasive justice. The pragmatic model needs an in-depth investigation of alternatives; their practical and moral costs and their benefits. It is concluded that there can be no relief unless the offender confesses and asks forgiveness, and argues that repentance is poor therapy and of questionable morality, because it leaves clients in a state of helpless dependence on the person or persons who offended them in the first place. © 2002 by Oxford University Press, Inc. All rights reserved.
Journal Abbreviation: Before Forgiving: Cautionary Views of Forgiveness in Psychother.
Keywords: Caution; Counseling; Forgiveness; Justice; Pervasive justice; Pragmatic model; Restorative justice; Retributive justice; dept.psy

Neurobiological and behavioral studies of skilled and impaired word reading - Frost, S.J.; Sandak, R.; Mencl, W.E.; Landi, N.; Moore, D.; Porta, G.D.; Rueckl, J.G.; Katz, L.; Pugh, K.R. (Single-Word Read.: Behavioral and Biological Perspectives, 2012)
Journal Abbreviation: Single-Word Read.: Behavioral and Biological Perspectives
Keywords: dept.psy

Affective awareness in parenting of fathers with co-occurring substance abuse and intimate partner violence - Gilchrist, G.; Smith Stover, C.; Spink, A. (Advances in Dual Diagnosis, 2012)
Few studies have examined the parenting of fathers with cooccurring substance abuse (SA) and intimate partner violence (IPV) problems. None have specifically interviewed men with these cooccurring issues using qualitative methods about their reflective functioning in relation to their children. This paper aims to provide evidence of the reflective capacity of fathers with cooccurring SA and IPV. To assess this, men were asked to describe examples of negative emotions they experienced as parents and how they perceived their children responded to those emotions. In total, 40 fathers with cooccurring SA and IPV were interviewed using the Revised Parent Development Interview. Interviews were coded for reflective functioning and for themes that emerged related to angry and guilty feelings these fathers experienced as parents. Overall, fathers in the sample had a very limited capacity to think about the thoughts and feelings of their children. The desire to spend more time with their child and an inability to provide financially were two common themes. Anger toward the child's mother for not providing adequate care and a focus on shielding the child from his anger were also reported frequently. Fathers did not report feelings of guilt related to their substance use or aggression in their relationships. This paper is one of the first to explore reflective functioning of fathers with cooccurring IPV and SA. These findings are discussed in relation to their implications for intervention with fathers with cooccurring SA and IPV issues. © 2012, Emerald Group Publishing Limited
23 citations (Crossref) [2023-10-31]
Keywords: Domestic violence; Drug addiction; Fathers; Intimate partner violence; Men; Parenting; Substance abuse; United States of America; dept.psy

Using acid to improve credibility assessments with written and audio statements - Montalvo, L.; Hallinan, C.; Hiscock-Anisman, C.; Morrissey, D.; Bonilla, Y.; Colwell, K. (American Journal of Forensic Psychology, 2013)
Investigators are continually faced with the task of detecting deception. Assessment Criteria Indicative of Deception (ACID) is a system of interviewing and credibility assessment that maximizes verbal cues to detect deception, and teaches content analysis that highlights attempts to withhold, distort, or manipulate information. The ACID technique has been successful in discriminating honest from deceptive statements when credibility determinations are made either by statistical methods or trained raters. Unfortunately, the training has required several hours and application has required the time-consuming process of transcription. The current study demonstrates the utility of ACID following a brief training, and compares the credibility ratings made from analysis of transcripts to the credibility ratings made from the analysis of audio recordings. Twenty-nine university undergraduate and graduate students read or listened to a series of eight transcripts. Raters were provided with accounts before training and 4 accounts after training. Prior to training, raters performed at 55% accuracy. Following training, raters performed at 71% accuracy. Additionally, there was an untrained control group that performed at 53% accuracy. Of note, the post-training performance was identical for accounts presented in written and audio formats. In sum, the ACID technique was reliable, valid, easy to train, and showed that accurate decisions can be made from simple audio recordings. Copyright 2013 American Journal of Forensic Psychology,.
Keywords: accuracy; adult; article; assessment criteria indicative of deception; audiology; clinical assessment tool; clinical decision making; clinical education; content analysis; controlled study; deception; dept.psy; human; human experiment; meaningful use criteria; reliability; statistical analysis; validity; written language; ⛔ No DOI found

Screening for reading disability in university students with phonological processing and working memory tasks - Broggi, Jr., M.; Ready, R.E.; Moore, D.L. (Dyslexia, 2019)
Many students in higher education have undiagnosed reading disabilities (RDs), but there are few measures to screen for RD in this population. The aim of this study was to determine the ability of tasks that are sensitive to RDs—such as measures of phonemic awareness and working memory—to differentiate university students previously diagnosed with RDs from controls. Participants were university students with an RD (n = 26), a clinical control group diagnosed with attention-deficit/hyperactivity disorder (n = 24), and neurotypical controls (n = 44). Participants completed brief phonological processing and working memory tasks. The RD group scored significantly lower on all tasks than both control groups. The phonological processing tasks alone—without the working memory task—discriminated participants with RDs from controls with excellent sensitivity and specificity. A brief battery of phonemic tasks could be an effective screening instrument for persons with RDs on university campuses. © 2019 John Wiley & Sons, Ltd.
2 citations (Crossref) [2023-10-31]
Keywords: Attention Deficit Disorder with Hyperactivity; Awareness; Dyslexia; Female; Humans; Learning Disorders; Male; Memory; Short-Term; Phonetics; Reading; Students; Task Performance and Analysis; Universities; Young Adult; attention deficit disorder; awareness; dept.psy; dyslexia; female; human; learning disorder; male; peer-reviewed; phonetics; phonological processing; psychology; reading; reading disability; screening test; short term memory; student; task performance; university; university students; working memory; young adult

Navigating Ethical Challenges for Pediatric Sickle Cell Pain Management in the Context of the Opioid Epidemic - Mulchan, Siddika S.; Wakefield, Emily O.; Martin, Sarah R.; Ayr-Volta, Lauren; Krenicki, Kayla; Zempsky, William T. (The Clinical Journal of Pain, 2022)
Objectives: The aim was to describe the impact of the opioid epidemic on pain management practices in pediatric sickle cell disease (SCD) and propose a conceptual framework for navigating ethical decision-making in pediatric sickle cell pain management. Methods: A review of the literature on ethical challenges in the management of sickle cell pain was conducted and considered in the context of the opioid epidemic and psychosocial factors affecting youth with SCD. The Integrated Ethical Framework for Pain Management (IEFPM) was applied to pediatric sickle cell pain management using a clinical case example. Results: Implicit bias, health-related stigma, and potential neurocognitive impairment all present unique challenges in ethical decision-making for youth with SCD. National guidelines for prescribing opioid medication may complicate providers’ clinical decision-making and affect their sickle cell pain management practices. The IEFPM was found to be applicable to ethical decision-making for pediatric sickle cell pain and captures both patient-related and provider-related aspects of clinical pain management. Discussion: The opioid epidemic has exacerbated existing ethical challenges for pain management among youth with SCD. The IEFPM provides a conceptual model that can be integrated into health care settings to facilitate ethical decision-making and promote greater health equity in the clinical management of pediatric sickle cell pain.
4 citations (Crossref) [2023-10-31]
Keywords: Adolescent; Analgesics; Anemia; Child; Humans; Opioid; Opioid Epidemic; Pain; Pain Management; Sickle Cell; adolescent; analgesia; child; complication; dept.psy; human; narcotic analgesic agent; pain; peer-reviewed; sickle cell anemia

Morpholino-mediated knockdown of the brain mineralocorticoid receptor affects glucocorticoid signaling and neuroplasticity in wild ocellated wrasse (Symphodus ocellatus) - Nugent, Bridget M.; Stiver, Kelly A.; Han, Jiawei; Kindsvater, Holly K.; Marsh-Rollo, Susan E.; Hofmann, Hans A.; Alonzo, Suzanne H. (BioRxiv, 2021)
0 citations (Crossref) [2023-10-31]
Keywords: dept.psy; ⛔ No DOI found

Ejaculate allocation and sperm characteristics differ among alternative male types in a species of fish with cooperation and competition among unrelated males. - Alonzo, Suzanne H.; Stiver, Kelly A.; Kindsvater, Holly K.; Marsh-Rollo, Susan E.; Nugent, Bridget; Kazancıoğlu, Erem (Cells, 2021)
Sexual selection arising from sperm competition has driven the evolution of immense variation in ejaculate allocation and sperm characteristics not only among species, but also among males within a species. One question that has received little attention is how cooperation among males affects these patterns. Here we ask how male alternative reproductive types differ in testes size, ejaculate production, and sperm morphology in the ocellated wrasse, a marine fish in which unrelated males cooperate and compete during reproduction. Nesting males build nests, court females and provide care. Sneaker males only “sneak” spawn, while satellite males sneak, but also help by chasing away sneakers. We found that satellite males have larger absolute testes than either sneakers or nesting males, despite their cooperative role. Nesting males invested relatively less in testes than either sneakers or satellites. Though sneakers produced smaller ejaculates than either satellite or nesting males, we found no difference among male types in either sperm cell concentration or sperm number, implying sneakers may produce less seminal fluid. Sperm tail length did not differ significantly among male types, but sneaker sperm cells had significantly larger heads than either satellite or nesting male sperm, consistent with past research showing sneakers produce slower sperm. Our results highlight that social interactions among males can influence sperm and ejaculate production. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.
7 citations (Crossref) [2023-10-31]
Keywords: Animals; Fishes; Male; Reproduction; Spermatozoa; Testis; adult; animal; article; controlled study; court; dept.psy; female; fish; human cell; male; metabolism; nesting; nonhuman; peer-reviewed; phenotypic plasticity; reproduction; seminal plasma; sexual selection; social interaction; sperm competition; sperm count; spermatozoon; spermatozoon tail; testis

Positive psychology: Exploring a mindful approach to online learning in higher education - DeLucia, Christine A. (Emerging Realities and the Future of Technology in the Classroom, 2021)
Keywords: dept.psy

Contributions of Sahgal and colleagues: the "vasopression central arousal theory". - McEwen, Barbara B (Advances in pharmacology (San Diego, Calif.), 2004)
Place: United States Barbara B McEwen. Department of Psychology, Southern Connecticut State University, New Haven, USA.
Keywords: *Arousal/ph [Physiology]; *Central Nervous System/ph [Physiology]; *Vasopressins/ph [Physiology]; Animals; Learning/de [Drug Effects]; Learning/ph [Physiology]; Memory/de [Drug Effects]; Memory/ph [Physiology]; Rats; Vasopressins/pd [Pharmacology]; dept.psy; ⛔ No DOI found

De Wied and colleagues I: evidence for a VP and an OT influence on MP: launching the "VP/OT central memory theory". - McEwen, Barbara B (Advances in pharmacology (San Diego, Calif.), 2004)
1 citations (Crossref) [2023-10-31] Place: United States McEwen, Barbara B. Department of Psychology, Southern Connecticut State University, New Haven, USA.
Keywords: *Memory/ph [Physiology]; *Oxytocin/ph [Physiology]; *Vasopressins/ph [Physiology]; Amnesia/pp [Physiopathology]; Animals; Avoidance Learning/ph [Physiology]; Humans; Learning/ph [Physiology]; dept.psy

De Wied and colleagues II: further clarification of the roles of vasopressin and oxytocin in memory processing. - McEwen, Barbara B (Advances in pharmacology (San Diego, Calif.), 2004)
2 citations (Crossref) [2023-10-31] Place: United States McEwen, Barbara B. Department of Psychology, Southern Connecticut State University, New Haven, USA.
Keywords: *Memory/ph [Physiology]; *Oxytocin/ph [Physiology]; *Vasopressins/ph [Physiology]; Animals; Arousal/ph [Physiology]; Pituitary Gland; Posterior/ph [Physiology]; Rats; Rats; Brattleboro; dept.psy

De Wied and colleagues III: brain sites and transmitter systems involved in the vasopressin and oxytocin influence on memory processing. - McEwen, Barbara B (Advances in pharmacology (San Diego, Calif.), 2004)
1 citations (Crossref) [2023-10-31] Place: United States McEwen, Barbara B. Department of Psychology, Southern Connecticut State University, New Haven, USA.
Keywords: *Brain/ph [Physiology]; *Memory/ph [Physiology]; *Neurotransmitter Agents/ph [Physiology]; *Oxytocin/ph [Physiology]; *Vasopressins/ph [Physiology]; Animals; Brain Chemistry/ph [Physiology]; Catecholamines/ph [Physiology]; Humans; dept.psy

De Wied and colleagues IV: research into mechanisms of action by which vasopressin and oxytocin influence memory processing. - McEwen, Barbara B (Advances in pharmacology (San Diego, Calif.), 2004)
3 citations (Crossref) [2023-10-31] Place: United States McEwen, Barbara B. Department of Psychology, Southern Connecticut State University, New Haven, USA.
Keywords: *Memory/ph [Physiology]; *Oxytocin/ph [Physiology]; *Vasopressins/ph [Physiology]; Animals; Brain/ph [Physiology]; Hippocampus/ph [Physiology]; Humans; Receptors; Oxytocin/ph [Physiology]; Receptors; Vasopressin/ph [Physiology]; dept.psy

General introduction to vasopressin and oxytocin: structure/metabolism, evolutionary aspects, neural pathway/receptor distribution, and functional aspects relevant to memory processing. - McEwen, Barbara B (Advances in pharmacology (San Diego, Calif.), 2004)
22 citations (Crossref) [2023-10-31] Place: United States McEwen, Barbara B. Department of Psychology, Southern Connecticut State University, New Haven, USA.
Keywords: *Biological Evolution; *Memory/ph [Physiology]; *Neural Pathways/ph [Physiology]; *Oxytocin/ph [Physiology]; *Receptors; Oxytocin/ph [Physiology]; *Receptors; Vasopressin/ph [Physiology]; *Vasopressins/ph [Physiology]; Adrenal Medulla/pp [Physiopathology]; Animals; Glucose/ph [Physiology]; Humans; Oxytocin/ch [Chemistry]; Oxytocin/me [Metabolism]; Pituitary Gland; Anterior/pp [Physiopathology]; Stress; Psychological/pp [Physiopathology]; Vasopressins/ch [Chemistry]; Vasopressins/me [Metabolism]; dept.psy

Research studies of Koob and colleagues: the "vasopressin dual action theory". - McEwen, Barbara B (Advances in pharmacology (San Diego, Calif.), 2004)
0 citations (Crossref) [2023-10-31] Place: United States McEwen, Barbara B. Department of Psychology, Southern Connecticut State University, New Haven, USA.
Keywords: *Memory/ph [Physiology]; *Vasopressins/ph [Physiology]; Animals; Avoidance Learning/de [Drug Effects]; Avoidance Learning/ph [Physiology]; Humans; Maze Learning/de [Drug Effects]; Maze Learning/ph [Physiology]; Memory/de [Drug Effects]; Vasopressins/pd [Pharmacology]; dept.psy

Brain-fluid barriers: relevance for theoretical controversies regarding vasopressin and oxytocin memory research. - McEwen, Barbara B (Advances in pharmacology (San Diego, Calif.), 2004)
40 citations (Crossref) [2023-10-31] Place: United States McEwen, Barbara B. Department of Psychology, Southern Connecticut State University, New Haven, USA.
Keywords: *Blood-Brain Barrier/ph [Physiology]; *Memory/ph [Physiology]; *Oxytocin/ph [Physiology]; *Vasopressins/ph [Physiology]; Animals; Arginine Vasopressin/pd [Pharmacology]; Humans; Oxytocin/cf [Cerebrospinal Fluid]; Oxytocin/pd [Pharmacology]; Vasopressins/cf [Cerebrospinal Fluid]; Vasopressins/pd [Pharmacology]; dept.psy

Closing remarks: review and commentary on selected aspects of the roles of vasopressin and oxytocin in memory processing. - McEwen, Barbara B (Advances in pharmacology (San Diego, Calif.), 2004)
6 citations (Crossref) [2023-10-31] Place: United States McEwen, Barbara B. Department of Psychology, Southern Connecticut State University, New Haven, USA.
Keywords: *Memory/ph [Physiology]; *Oxytocin/ph [Physiology]; *Vasopressins/ph [Physiology]; Animals; Cognition/de [Drug Effects]; Cognition/ph [Physiology]; Humans; Learning/de [Drug Effects]; Learning/ph [Physiology]; Memory/de [Drug Effects]; Mice; Oxytocin/pd [Pharmacology]; Social Behavior; Vasopressins/pd [Pharmacology]; dept.psy

Expansion of olfactory-based social recognition memory research: the roles of vasopressin and oxytocin in social recognition memory. - McEwen, Barbara B (Advances in pharmacology (San Diego, Calif.), 2004)
1 citations (Crossref) [2023-10-31] Place: United States McEwen, Barbara B. Department of Psychology, Southern Connecticut State University, New Haven, USA.
Keywords: *Memory/ph [Physiology]; *Oxytocin/ph [Physiology]; *Smell/ph [Physiology]; *Social Behavior; *Vasopressins/ph [Physiology]; Animals; Behavior; Animal/de [Drug Effects]; Female; Humans; Male; Memory/de [Drug Effects]; Oxytocin/pd [Pharmacology]; Sex Characteristics; Vasopressins/pd [Pharmacology]; dept.psy

Expansion of vasopressin/oxytocin memory research I: peripheral administration. - McEwen, Barbara B (Advances in pharmacology (San Diego, Calif.), 2004)
1 citations (Crossref) [2023-10-31] Place: United States McEwen, Barbara B. Department of Psychology, Southern Connecticut State University, New Haven, USA.
Keywords: *Memory/de [Drug Effects]; *Oxytocin/pd [Pharmacology]; *Vasopressins/pd [Pharmacology]; Animals; Appetitive Behavior/de [Drug Effects]; Avoidance Learning/de [Drug Effects]; Discrimination Learning/de [Drug Effects]; Humans; Maze Learning/de [Drug Effects]; Oxytocin/ad [Administration & Dosage]; Vasopressins/ad [Administration & Dosage]; dept.psy

Expansion of vasopressin/oxytocin memory research II: brain structures and transmitter systems involved in the influence of vasopressin and oxytocin on memory processing. - McEwen, Barbara B (Advances in pharmacology (San Diego, Calif.), 2004)
1 citations (Crossref) [2023-10-31] Place: United States McEwen, Barbara B. Department of Psychology, Southern Connecticut State University, New Haven, USA.
Keywords: *Brain/ph [Physiology]; *Memory/ph [Physiology]; *Neurotransmitter Agents/ph [Physiology]; *Oxytocin/ph [Physiology]; *Vasopressins/ph [Physiology]; Animals; Humans; dept.psy

Expansion of vasopressin/oxytocin memory research III: research summary and commentary on theoretical and methodological issues. - McEwen, Barbara B (Advances in pharmacology (San Diego, Calif.), 2004)
2 citations (Crossref) [2023-10-31] Place: United States McEwen, Barbara B. Department of Psychology, Southern Connecticut State University, New Haven, USA.
Keywords: *Memory/ph [Physiology]; *Oxytocin/ph [Physiology]; *Vasopressins/ph [Physiology]; Animals; Humans; dept.psy

Research contributions of Dantzer, Bluthe, and colleagues to the study of the role of vasopressin in olfactory-based social recognition memory. - McEwen, Barbara B (Advances in pharmacology (San Diego, Calif.), 2004)
1 citations (Crossref) [2023-10-31] Place: United States McEwen, Barbara B. Department of Psychology, Southern Connecticut State University, New Haven, USA.
Keywords: *Memory/ph [Physiology]; *Smell/ph [Physiology]; *Social Behavior; *Vasopressins/ph [Physiology]; Animals; Brain/ph [Physiology]; Humans; dept.psy

Role of attentional processing in mediating the influence of vasopressin on memory processing. - McEwen, Barbara B (Advances in pharmacology (San Diego, Calif.), 2004)
0 citations (Crossref) [2023-10-31] Place: United States McEwen, Barbara B. Department of Psychology, Southern Connecticut State University, New Haven, USA.
Keywords: *Attention/ph [Physiology]; *Memory/ph [Physiology]; *Vasopressins/ph [Physiology]; Animals; Humans; Rats; dept.psy

Does the risk of sperm competition help explain cooperation between reproductive competitors? A study in the ocellated wrasse (Symphodus ocellatus). - Stiver, Kelly A; Alonzo, Suzanne H (The American naturalist, 2013)
Although cooperating individuals may gain benefits, they risk being cheated by their allies. Therefore, to understand the persistence of cooperation by mutual benefits, it is important to document both the potential benefits of cooperation and the risks of cheating. We experimentally examined evidence of cooperation in the ocellated wrasse (Symphodus ocellatus), a fish species with males that exercise three reproductive strategies: satellite and sneaker males attempt to parasitically spawn in the nests of nesting males. Nesting males have been hypothesized to tolerate satellites as a result of satellite aid in defense against sneaker males and help in courting females. Here, we provide evidence that cooperation between reproductive competitors may arise in response to sperm competition from other males. After we experimentally removed satellites, nesting males had more sneakers at their nest and experienced a higher rate of sneaking when they spawned (increased sperm competition risk). When we experimentally distracted nesting males to prevent their acting aggressively toward satellites, satellites spawned with females and ate eggs in the nest. Our results suggest that nesting males and satellites gain fitness benefits of reduced direct reproductive and sperm competition through cooperation. However, nesting males risk losing paternity, while satellites experience increased aggression and must invest in aggression themselves (i.e., they act aggressively toward sneakers).
17 citations (Crossref) [2023-10-31] Place: United States Stiver, Kelly A. Department of Psychology, Southern Connecticut State University, New Haven, CT 06515, USA. stiverk1@southernct.edu
Keywords: *Competitive Behavior/ph [Physiology]; *Cooperative Behavior; *Perciformes/ph [Physiology]; *Sexual Behavior; Animal/ph [Physiology]; *Spermatozoa/ph [Physiology]; Aggression; Alternative male tactics; Analysis of Variance; Animals; Competition; Competitive Behavior; Cooperation; Cooperative Behavior; Female; Fertility; Fertility/ph [Physiology]; Male; Models; Biological; Nesting Behavior; Nesting Behavior/ph [Physiology]; Perciformes; Sexual Behavior; Animal; Sneak-fertilization; Sperm competition; Spermatozoa; aggression; analysis of variance; animal; article; biological model; competitive behavior; cooperation; cooperative breeding; dept.psy; female; fertility; male; nesting; peer-reviewed; perciform; persistence; physiology; reproductive strategy; sexual behavior; sneak copulation; sperm competition; spermatozoon

The Promise of Automated Home-Cage Monitoring in Improving Translational Utility of Psychiatric Research in Rodents. - Mingrone, Alfred; Kaffman, Ayal; Kaffman, Arie (Frontiers in neuroscience, 2020)
Large number of promising preclinical psychiatric studies in rodents later fail in clinical trials, raising concerns about the efficacy of this approach to generate novel pharmacological interventions. In this mini-review we argue that over-reliance on behavioral tests that are brief and highly sensitive to external factors play a critical role in this failure and propose that automated home-cage monitoring offers several advantages that will increase the translational utility of preclinical psychiatric research in rodents. We describe three of the most commonly used approaches for automated home cage monitoring in rodents [e.g., operant wall systems (OWS), computerized visual systems (CVS), and automatic motion sensors (AMS)] and review several commercially available systems that integrate the different approaches. Specific examples that demonstrate the advantages of automated home-cage monitoring over traditional tests of anxiety, depression, cognition, and addiction-like behaviors are highlighted. We conclude with recommendations on how to further expand this promising line of preclinical research. Copyright © 2020 Mingrone, Kaffman and Kaffman.
19 citations (Crossref) [2023-10-31] Place: Switzerland Mingrone, Alfred. Department of Psychology, Southern Connecticut State University, New Haven, CT, United States. Kaffman, Ayal. Department of Psychiatry, Yale University School of Medicine, New Haven, CT, United States. Kaffman, Arie. Department of Psychiatry, Yale University School of Medicine, New Haven, CT, United States.
Keywords: Actual-HCA; Chora feeder; Intellicage system; PhenoTyper; Review; addiction; anxiety disorder; automated home cage monitoring; automation; behavioral science; cognition; depression; dept.psy; monitoring; nonhuman; peer-reviewed; preclinical study; psychiatry; rodent; rodents; translational research

Audiovisual speech perception in children with autism spectrum disorders: Evidence from visual phonemic restoration. - Irwin, Julia; Avery, Trey; Kleinman, Daniel; Landi, Nicole (Journal of autism and developmental disorders, 2021)
Children with autism spectrum disorders have been reported to be less influenced by a speaker’s face during speech perception than those with typically development. To more closely examine these reported differences, a novel visual phonemic restoration paradigm was used to assess neural signatures (event-related potentials [ERPs]) of audiovisual processing in typically developing children and in children with autism spectrum disorder. Video of a speaker saying the syllable /ba/ was paired with (1) a synthesized /ba/ or (2) a synthesized syllable derived from /ba/ in which auditory cues for the consonant were substantially weakened, thereby sounding more like /a/. The auditory stimuli are easily discriminable; however, in the context of a visual /ba/, the auditory /a/ is typically perceived as /ba/, producing a visual phonemic restoration. Only children with ASD showed a large /ba/-/a/ discrimination response in the presence of a speaker producing /ba/, suggesting reduced influence of visual speech. © 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC part of Springer Nature.
4 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85101748846
Keywords: Auditory Perception; Autism Spectrum Disorder; Child; Cues; Evoked Potentials; Humans; Speech; Speech Perception; Visual Perception; association; autism; child; dept.psy; evoked response; hearing; human; peer-reviewed; speech; speech perception; vision

The offspring of alcohol-exposed sires exhibit heightened ethanol intake and behavioral alterations in the elevated plus maze. - Koabel, Jennifer; McNivens, Meghan; McKee, Paul; Pautassi, Ricardo; Bordner, Kelly; Nizhnikov, Michael (Alcohol (Fayetteville, N.Y.), 2021)
Research suggests that addictive traits are indeed heritable, but very few preclinical studies have explored transgenerational effects of paternal alcohol exposure. The present study addressed this gap in knowledge. We explored whether offspring of ethanol-exposed sires would be more likely to accept ethanol than descendants of water-exposed and control sires. We also investigated whether the second generation of ethanol-exposed descendants would accept ethanol more than controls and were more or less likely to experience anxiety-like behavior in behavioral assessments. We exposed male rats to repeated binge doses of alcohol (4 g/kg/day across 8 days), water, or left them untreated and mated them with untreated females. We then bred the offspring of these rats to test transgenerational effects of paternal alcohol exposure. We tested 14-day-old offspring from the first and second filial generation for their acceptance of ethanol and water, and measured anxiety-like behavior in 38-day-old, second-generation offspring using an elevated plus maze. The results indicate that offspring of ethanol-exposed sires increase ethanol acceptance in the first generation compared to untreated controls, whereas in the second-generation increased ethanol acceptance vs. these controls is seen in descendants of both ethanol- and vehicle-treated sires. At adolescence, the second generation of rats derived from alcohol-exposed sires exhibited significantly more time spent in the open arms and significantly more arm entries than any other group. The present study suggests that parental ethanol exposure is associated with lingering effects in the infant and adolescent offspring. The second filial generation was also found to be affected, albeit similarly by grandparental ethanol exposure or by the stress of the vehicle administration. Copyright © 2021 Elsevier Inc. All rights reserved.
5 citations (Crossref) [2023-10-31] Place: United States Koabel, Jennifer. Stony Brook University, 100 Nicolls Road, Stony Brook, New York, 11794, United States. Electronic address: Jennifer.Koabel@stonybrook.edu. McNivens, Meghan. Stony Brook University, 100 Nicolls Road, Stony Brook, New York, 11794, United States. McKee, Paul. Southern Connecticut State University, 501 Crescent St., New Haven, CT, 06515, United States. Pautassi, Ricardo. Instituto de Investigaciones Medicas M. y M. Ferreyra (INIMEC-CONICET), Friuli 2434, Cordoba, Cba, 5016, Argentina. Bordner, Kelly. Southern Connecticut State University, 501 Crescent St., New Haven, CT, 06515, United States. Nizhnikov, Michael. Southern Connecticut State University, 501 Crescent St., New Haven, CT, 06515, United States.
Keywords: Addictive; Alcohol Drinking; Animals; Anxiety; Article; Behavior; Elevated Plus Maze Test; Ethanol; Male; Maze Learning; Rats; Sprague Dawley rat; addiction; adolescence; adolescent; adult; alcohol; alcohol consumption; animal; animal experiment; animal model; anxiety; behavior disorder; binge drinking; breeding; concentration (parameter); controlled study; dept.psy; drinking behavior; elevated plus maze test; experience; exposure; female; grandparent; inhibitory control; male; maze test; newborn; nonhuman; paternal exposure; peer-reviewed; progeny; rat; sire; vertical transmission; water

Measurement of Motivation States for Physical Activity and Sedentary Behavior: Development and Validation of the CRAVE Scale. - Stults-Kolehmainen, Matthew A; Blacutt, Miguel; Fogelman, Nia; Gilson, Todd A; Stanforth, Philip R; Divin, Amanda L; Bartholomew, John B; Filgueiras, Alberto; McKee, Paul C; Ash, Garrett I; Ciccolo, Joseph T; Brotnow Decker, Line; et al. (Frontiers in psychology, 2021)
Physical activity, and likely the motivation for it, varies throughout the day. The aim of this investigation was to create a short assessment (CRAVE: Cravings for Rest and Volitional Energy Expenditure) to measure motivation states (wants, desires, urges) for physical activity and sedentary behaviors. Five studies were conducted to develop and evaluate the construct validity and reliability of the scale, with 1,035 participants completing the scale a total of 1,697 times. In Study 1, 402 university students completed a questionnaire inquiring about the want or desire to perform behaviors "at the present moment (right now). " Items related to physical activity (e.g., "move my body") and sedentary behaviors (e.g., "do nothing active"). An exploratory structural equation model (ESEM) revealed that 10 items should be retained, loading onto two factors (5 each for Move and Rest). In Study 2, an independent sample (n = 444) confirmed these results and found that Move and Rest desires were associated with stage-of-change for exercise behavior. In Study 3, 127 community-residing participants completed the CRAVE at 6-month intervals over two years- two times each session. Across-session interclass correlations (ICC) for Move (ICC = 0.72-0.95) and Rest (ICC = 0.69-0.88) were higher than when they were measured across 24-months (Move: ICC = 0.53; Rest: ICC = 0.49), indicating wants/desires have state-like qualities. In Study 4, a maximal treadmill test was completed by 21 university students. The CRAVE was completed immediately pre and post. Move desires decreased 26% and Rest increased 74%. Changes in Move and Rest desires were moderately associated with changes in perceived physical fatigue and energy. In Study 5, 41 university students sat quietly during a 50-min lecture. They completed the CRAVE at 3 time points. Move increased 19.6% and Rest decreased 16.7%. Small correlations were detected between move and both perceived energy and tiredness, but not calmness or tension. In conclusion, the CRAVE scale has good psychometric properties. These data also support tenets of the WANT model of motivation states for movement and rest (Stults-Kolehmainen et al., 2020a). Future studies need to explore how desires to move/rest relate to dynamic changes in physical activity and sedentarism. Copyright © 2021 Stults-Kolehmainen, Blacutt, Fogelman, Gilson, Stanforth, Divin, Bartholomew, Filgueiras, McKee, Ash, Ciccolo, Brotnow Decker, Williamson and Sinha.
11 citations (Crossref) [2023-10-31] Place: Switzerland Stults-Kolehmainen, Matthew A. Digestive Health Multispecialty Clinic, Yale - New Haven Hospital, New Haven, CT, United States. Stults-Kolehmainen, Matthew A. Department of Biobehavioral Sciences, Teachers College, Columbia University, New York, NY, United States. Blacutt, Miguel. Department of Biobehavioral Sciences, Teachers College, Columbia University, New York, NY, United States. Fogelman, Nia. Yale Stress Center, Yale School of Medicine, New Haven, CT, United States. Gilson, Todd A. Department of Kinesiology and Physical Education, Northern Illinois University, DeKalb, IL, United States. Stanforth, Philip R. Department of Kinesiology and Health Education, The University of Texas at Austin, Austin, TX, United States. Divin, Amanda L. Department of Health and Human Performance, Northwestern State University, Natchitoches, LA, United States. Bartholomew, John B. Department of Kinesiology and Health Education, The University of Texas at Austin, Austin, TX, United States. Filgueiras, Alberto. Department of Cognition and Human Development, Rio de Janeiro State University, Rio de Janeiro, Brazil. McKee, Paul C. Department of Psychology, Southern Connecticut State University, New Haven, CT, United States. Ash, Garrett I. Pain, Research, Informatics, Medical Comorbidities and Education Center (PRIME), VA Connecticut Healthcare System, West Haven, CT, United States. Ash, Garrett I. Center for Medical Informatics, Yale School of Medicine, New Haven, CT, United States. Ciccolo, Joseph T. Department of Biobehavioral Sciences, Teachers College, Columbia University, New York, NY, United States. Brotnow Decker, Line. Yale Child Study Center, Yale School of Medicine, New Haven, CT, United States. Brotnow Decker, Line. Division of Mental Health, Akershus University Hospital, Lorenskog, Norway. Williamson, Susannah L. Department of Health and Kinesiology, Texas A&M University, College Station, TX, United States. Sinha, Rajita. Yale Stress Center, Yale School of Medicine, New Haven, CT, United States. Sinha, Rajita. Yale Child Study Center, Yale School of Medicine, New Haven, CT, United States.
Keywords: dept.psy; peer-reviewed

Defense against outside competition is linked to cooperation in male-male partnerships - Hellmann, Jennifer K.; Stiver, Kelly A.; Marsh-Rollo, Susan; Alonzo, Suzanne H. (Behavioral Ecology, 2020)
Male–male competition is a well-known driver of reproductive success and sexually selected traits in many species. However, in some species, males work together to court females or defend territories against male competitors. Dominant (nesting) males sire most offspring, but subordinate (satellite) males are better able to obtain fertilizations relative to unpartnered males. Because satellites only gain reproductive success by sneaking, there has been much interest in identifying the mechanisms enforcing satellite cooperation (defense) and reducing satellite sneaking. One such potential mechanism is outside competition: unpartnered satellites can destabilize established male partnerships and may force partnered satellites to restrain from cheating to prevent the dominant male from replacing them with an unpartnered satellite. Here, we manipulated perceived competition in the Mediterranean fish Symphodus ocellatus by presenting an “intruding” satellite male to established nesting and satellite male pairs. Focal satellite aggression to the intruder was higher when focal satellites were less cooperative, suggesting that satellites increase aggression to outside competitors when their social position is less stable. In contrast, nesting male aggression to the intruder satellite increased as spawning activity increased, suggesting that nesting males increase their defense toward outside competitors when their current relationship is productive. We found no evidence of altered spawning activity or nesting/satellite male interactions before and after the presentation. These results collectively suggest that response to outside competition is directly linked to behavioral dynamics between unrelated male partners and may be linked to conflict and cooperation in ways that are similar to group-living species.
8 citations (Crossref) [2023-10-31] WOS:000537266400017
Keywords: Satellites; Symphodus ocellatus; alternative reproductive tactics; biological market theory; cooperation; cooperative behavior; defense mechanism; dept.psy; interspecific competition; intraspecific interaction; outside options; peer-reviewed; satellite male; sneak

Big five, linguistic styles, and successful online learning - Abe, J. (Internet and Higher Education, 2020)
With the tremendous growth in online classes and programs at institutions of higher education, conflicting claims are increasingly being made on media and blog sites about the personality types that are compatible with this new learning format. The relations between the Five Factor Model of Personality (FFM) and linguistic styles with measures of academic performance in fully online asynchronous classes were examined. Consistent with findings based on research in face-to-face classes, Conscientiousness, Openness to Experience, and Analytic Thinking were associated with academic success. There was no support for the views propagated on the internet that extraversion, introversion, or anxiety hinder or foster online learning. The most robust predictor of academic performance throughout the semester, independent of the personality variables, was the number of words students contributed to the online discussions. These finding are interpreted within the Community of Inquiry framework (CoI; Garrison, 2003) and future lines of research are suggested. © 2020 Elsevier Inc.
31 citations (Crossref) [2023-10-31] tex.ids: abeBigFiveLinguistic2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85078113247 type: Article
Keywords: Academic performance; Community of Inquiry framework (CoI); Community of inquiry; E-learning; Education computing; Five Factor Model Of Personality (FFM); Five-factor model of personality; LIWC; Linguistic analysis; Linguistics; Online learning; dept.psy; peer-reviewed

Prediction of ethanol self-administration in pre-weanling, adolescent, and young adult rats. - Soledad Fernandez, Macarena; Edward Nizhnikov, Michael; Garcia Virgolini, Rodrigo; Marcos Pautassi, Ricardo (Developmental Psychobiology, 2021)
Alcohol (ethanol) use is almost normative by late adolescence, in most western countries. It is important to identify factors that distinguish those who progress from alcohol initiation to sustained use of the drug, from those that keep a controlled pattern of drinking. The factors precipitating this transition may change across development. This study analyzed associations between behavioral endophenotypes and ethanol intake at three developmental periods. Exp. 1 measured ethanol drinking at postnatal day 18, via an intraoral infusion procedure, in male or female pre-weanling rats screened for anxiety response in the light-dark box test and for distance traveled in a novel open field. Exp. 2 measured, in juvenile/adolescent or young adult rats, the association between shelter seeking, exploratory/risk-taking behaviors, anxiety or hedonic responses, and ethanol intake. Ethanol intake in pre-weanlings was explained by distance traveled in a novel environment, whereas anxiety responses, measured in the multivariate concentric square field apparatus (MSCF), selectively predicted ethanol intake at adolescence, but not at adulthood. Those juvenile/adolescents with lower mean duration of visit to areas of the MSCF that evoke anxiogenic responses exhibited heightened ethanol intake. These findings suggest that the association between anxiety and ethanol intake may be specifically relevant during adolescence. © 2020 Wiley Periodicals LLC
2 citations (Crossref) [2023-10-31] Place: (C) 2021 John Wiley & Sons, Ltd
Keywords: Alcohol Drinking; Animals; Anxiety; Ethanol; Female; Male; Rats; Self Administration; Wistar; Wistar rat; adolescents; alcohol; animal; anxiety; dept.psy; drinking behavior; drug self administration; ethanol intake; female; male; peer-reviewed; pre-weanling rat; rat

N400 amplitude, latency, and variability reflect temporal integration of beat gesture and pitch accent during language processing. - Morett, Laura M; Landi, Nicole; Irwin, Julia; McPartland, James C (Brain Research, 2020)
This study examines how across-trial (average) and trial-by-trial (variability in) amplitude and latency of the N400 event-related potential (ERP) reflect temporal integration of pitch accent and beat gesture. Thirty native English speakers viewed videos of a talker producing sentences with beat gesture co-occurring with a pitch accented focus word (synchronous), beat gesture co-occurring with the onset of a subsequent non-focused word (asynchronous), or the absence of beat gesture (no beat). Across trials, increased amplitude and earlier latency were observed when beat gesture was temporally asynchronous with pitch accenting than when it was temporally synchronous with pitch accenting or absent. Moreover, temporal asynchrony of beat gesture relative to pitch accent increased trial-by-trial variability of N400 amplitude and latency and influenced the relationship between across-trial and trial-by-trial N400 latency. These results indicate that across-trial and trial-by-trial amplitude and latency of the N400 ERP reflect temporal integration of beat gesture and pitch accent during language comprehension, supporting extension of the integrated systems hypothesis of gesture-speech processing and neural noise theories to focus processing in typical adult populations. Copyright © 2020 Elsevier B.V. All rights reserved.
8 citations (Crossref) [2023-10-31] Place: Netherlands Morett, Laura M. University of Alabama, United States. Electronic address: lmorett@ua.edu. Landi, Nicole. Haskins Laboratories, University of Connecticut, United States. Irwin, Julia. Haskins Laboratories, Southern Connecticut State University, United States. McPartland, James C. Yale University, United States.
Keywords: Adolescent; Adult; Beat gesture; Brain; Electroencephalography; Evoked Potentials; Evoked response variability; Female; Humans; Language; Male; N400; Pitch Perception; Pitch accent; Speech; Speech Perception; Temporal integration; Young Adult; adolescent; adult; article; brain; comprehension; controlled study; dept.psy; electroencephalography; event related potential; evoked response; female; gesture; human; human experiment; language; language processing; male; noise; peer-reviewed; physiology; pitch; pitch perception; speech; speech perception; videorecording; young adult

Motivation States for Physical Activity and Sedentary Behavior: Desire, Urge, Wanting, and Craving. - Stults-Kolehmainen, Matthew A; Blacutt, Miguel; Bartholomew, John B; Gilson, Todd A; Ash, Garrett I; McKee, Paul C; Sinha, Rajita (Frontiers in psychology, 2020)
To better explain daily fluctuations in physical activity and sedentary behavior, investigations of motivation are turning from social cognitive frameworks to those centered on affect, emotion and automaticity, such as the Affect and Health Behavior Framework (AHBF), Integrated Framework and Affective-Reflective Theory (ART). This shift has necessitated: (a) re-examination of older theories and their constructs, such as drives, needs and tensions and (b) an inspection of competing theories from other fields that also attempt to explain dynamic changes in health behaviors. The Dynamical Model of Desire, Elaborated Intrusion Theory and others commonly share with AHBF the idea that human behavior is driven strongly by desires and/or the similar concepts of wants, urges, and cravings. These affectively-charged motivation states (ACMS) change quickly and may better explain physical activity behavior from one moment to the next. Desires for movement predominantly derive from negative but also positive reinforcement. Data from clinical populations with movement dysfunction or psychiatric disorders provides further evidence of these drivers of movement. Those with Restless Legs Syndrome, akathisia, tic disorders and exercise dependence all report strong urges to move and relief when it is accomplished. Motor control research has identified centers of the brain responsible for wants and urges for muscular movement. Models elaborated herein differentiate between wants, desires, urges and cravings. The WANT model (Wants and Aversions for Neuromuscular Tasks) conceptualizes desires for movement and rest as varying by magnitude, approach or avoidance-orientation (wants versus aversions) and as occupying independent dimensions instead of opposite ends of the same axis. For instance, one hypothetically might be in a state of both high desire for movement and rest simultaneously. Variations in motivation states to move and rest may also be associated with various stress states, like freezing or fight and flight. The first validated instrument to measure feelings of desire/want for movement and rest, the CRAVE Scale (Cravings for Rest and Volitional Energy Expenditure) is already shedding light on the nature of these states. With these advances in theory, conceptual modeling and instrumentation, future investigations may explore the effects of desires and urges for movement and sedentary behavior in earnest. Copyright © 2020 Stults-Kolehmainen, Blacutt, Bartholomew, Gilson, Ash, McKee and Sinha.
15 citations (Crossref) [2023-10-31] Place: Switzerland Stults-Kolehmainen, Matthew A. Bariatric and Minimally Invasive Surgery Program, Yale-New Haven Hospital, New Haven, CT, United States. Stults-Kolehmainen, Matthew A. Department of Biobehavioral Sciences, Teachers College, Columbia University, New York, NY, United States. Blacutt, Miguel. Department of Biobehavioral Sciences, Teachers College, Columbia University, New York, NY, United States. Bartholomew, John B. Department of Kinesiology and Health Education, The University of Texas at Austin, Austin, TX, United States. Gilson, Todd A. Department of Kinesiology and Physical Education, Northern Illinois University, DeKalb, IL, United States. Ash, Garrett I. Pain Research, Informatics, Multi-morbidities, and Education (PRIME), VA Connecticut Healthcare System, West Haven, CT, United States. Ash, Garrett I. Center for Medical Informatics, Yale School of Medicine, New Haven, CT, United States. McKee, Paul C. Department of Psychology, Southern Connecticut State University, New Haven, CT, United States. Sinha, Rajita. Yale Stress Center, Yale School of Medicine, New Haven, CT, United States.
Keywords: conceptual analysis; dept.psy; desire; exercise; motivation; motivation states; peer-reviewed; physical activity; sedentary activity; urge for movement

The three-dimensional graphic method for quantifying body position - Trochim, William M K (Behavior Research Methods, 1976)
The three-dimensional graphic method for quantifying body position is a series of observer procedures and computer programs designed to yield three-dimensional (height, width, and depth) coordinates for various body points. These coordinates can be graphed by computer in several different ways, and can be analyzed mathematically to provide information about a wide variety of variables, including interpersonal distance and body activity. The procedure for collecting and analyzing the data is explained and the computer programs developed for the method are described. © 1976 Psychonomic Society, Inc.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/005-192-913-625-728 tex.type: [object Object]
Keywords: dept.psy

Sensory World - Introduction to Sensation and Perception - Bennett,tl - Fineman, MB (Contemporary Psychology, 1979)
tex.unique-id: ISI:A1979HH96300043
Keywords: dept.psy; ⛔ No DOI found

Environmental Noise in a Residential Institution for Mentally-Retarded Persons - Glenn, LE; Nerbonne, GP; Tolhurst, GC (American Journal of Mental Deficiency, 1978)
tex.unique-id: ISI:A1978EZ42100010
Keywords: dept.psy; ⛔ No DOI found

The effect of a moving dot transversal on the Poggendorff illusion - Fineman, Mark B; Melingonis, Mark P (Attention Perception & Psychophysics, 1977)
In attempting to derive the minimal component of the Poggendorff figure which would still produce an illusion, responses to three types of transversal were measured. One was the customary solid line type; a second type presented the two segments sequentially, alternating between them; and the third consisted of a moving dot which traveled the transversal path. Each transversal was shown with and without verticals, for a total of six conditions. Ten subjects in each condition adjusted the luminous transversal until the segments appeared to be collinear. Figures with verticals present showed a greater magnitude of illusion than those without, and discrepancies for moving dot transversals were greater than those for comparable solid line figures. Since alternating transversals were not significantly larger than solid line figures, it was concluded that the magnitude of the moving dot effect could not be attributed to temporal sequence. An eyemovement hypothesis was suggested instead. © 1977 Psychonomic Society, Inc.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-262-064-101-166 tex.type: [object Object]
Keywords: dept.psy; normal human; theoretical study; visual illusion

Egypts Christian Minority - Karas, SF (Middle East Review, 1977)
tex.unique-id: ISI:A1977CZ47800001
Keywords: dept.psy; ⛔ No DOI found

Primitive Drive-Dominated Thinking - Relationship to Acute Schizophrenia and Sociopathy - Harrow, M; Quinlan, D; Wallington, S; Pickett, L (Journal of Personality Assessment, 1976)
4 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1976BP36900007
Keywords: dept.psy

A comparison of the Ponzo illusion with a textural analogue - Fineman, Mark B; Carlson, Jeffrey (Attention Perception & Psychophysics, 1973)
The inappropriate constancy scaling notion of geometric illusions was explored by employing a textural analogue of the Ponzo figure. Ten Ss estimated the length of a horizontal line by equating it with varying companion lines in the context of the Ponzo figure, a textural analogue, and a baseline control in which the lines appeared with no surrounding contours. The textural analogue had the added feature of imposing no contours at the ends of the horizontal lines. It was found that length estimates were significantly different between the horizontals of the Ponzo figure and control stimuli, but not between the texture figure and a context-free control. The results suggest that inappropriate constancy scaling plays a minor role at best in the perception of geometric illusions. © 1973 Psychonomic Society, Inc.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/107-215-445-957-250 tex.type: [object Object]
Keywords: dept.psy; normal human; theoretical study; visual illusion

Consequences of transgression: self-punishment and depression. - Wallington, Sue A (Journal of Personality and Social Psychology, 1973)
Assessed the effects of transgression on self-aggression and depression in 96 high school students. Male confederates induced 1/2 of the Ss to transgress by deceiving the E. As a measure of self-aggression all Ss gave themselves electric shocks of intensity which they personally selected. Ss were also given behavioral and subjective-report measures of depression, including the Mood Adjective Check List. Transgressing Ss showed significantly more self-aggression. Transgressing Ss also showed changes on behavioral measures of depression but not on subjective-report measures. Females showed significantly more self-aggression than males regardless of condition. Findings suggest that the altruistic behavior found to occur after transgression may be engaged in for its self-punitive aspect as well as, or rather than as, a means of social restitution, as has been previously suggested. Contrary to the suggestion of some theories of depression, self-punishment did not appear to alleviate depression. (21 ref) (PsycINFO Database Record (c) 2006 APA, all rights reserved). © 1973 American Psychological Association.
27 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/106-375-491-281-980 tex.type: [object Object]
Keywords: Aggression; Depression; Electroshock; Female; Guilt; Human; Male; Morals; Orientation; Personality Inventory; Psychological Theory; Punishment; Self Concept; Sex Factors; Social Behavior; aggression; article; depression; depression; high school students; dept.psy; electric shock; female; guilt; human; male; morality; orientation; personality test; psychological theory; punishment; self concept; sex difference; social behavior; transgression; self-aggression &

Drug abuse and television viewing patterns - Brodlie, Jerome F. (Psychology, 1972)
tex.unique-id: ISI:A1972Z009700008
Keywords: dept.psy; ⛔ No DOI found

The effectiveness of a sex education program on the teacher's sex knowledge and attitudes - Karas, Shawky F; Elliot, Gale Ann (Small Group Research, 1972)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/037-993-116-130-600 tex.type: [object Object]
Keywords: dept.psy

The influence of communicator-recipient similarity upon the beliefs and behavior of pregnant women - Mazen, Ragaa; Leventhal, Howard (Journal of Experimental Social Psychology, 1972)
A field experiment was conducted to investigate the effects of communicator-recipient similarity and verbal communication upon the attitudes and behavior of pregnant women. Similarity was varied on two dimensions, pregnancy and color; and these factors were crossed with three communication conditions: (1) information on the advantages of rooming-in and breast feeding; (2) information combined with personal endorsement; and (3) no-information control. Both a pilot study and the main experiment showed no important differences in the amount of attitude change or behavioral compliance between the communication conditions. There were also no significant differences in attitude change as a function of similarity in pregnancy. However, a significantly higher proportion of mothers breast fed and roomed-in when the communicator was pregnant and similar than when she was nonpregnant and dissimilar. Similarity in color had no effect upon attitudes or behavior for the topic of rooming-in. But when the communicator was dissimilar in color there was significant negative change in attitudes toward breast feeding. Similarity in color also increased breast feeding. Attitudes and actions were related; mothers with initially favorable attitudes were more likely to comply for both issues. But with only one exception, attitude change was unrelated to behavioral compliance. The results are discussed in terms of visible similarity as a source of information or cues for action. © 1972.
18 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/112-126-262-556-629 tex.type: [object Object]
Keywords: dept.psy

Facilitation of stereoscopic depth perception by a relative-size cue in ambiguous disparity stereograms. - Fineman, Mark B. (Journal of Experimental Psychology, 1971)
Proposed that the cue of relative size may facilitate depth perception in accordance with a crossed or uncrossed disparity in stereograms in which both tendencies are equally represented. A concurrent concept was that the latency associated with the perception of depth in random-dot stereograms may be due, in part, to a cue conflict between binocular disparity and relative size. 4 male and 2 female graduate students were given 8 presentations of 5 stereographic stimuli, in which disparity was ambiguous but relative size was systematically altered. Ss were tested for direction of depth preferences and response latency. Both the relative-size effects and an uncrossed disparity bias were evidenced in the data. The latter effect was attributed to binocular rivalry between dissimilar elements in the stereoscopic half-fields. It is concluded that depth cue relationships are more complex than had been suggested by simple dominance theories. (PsycINFO Database Record (c) 2006 APA, all rights reserved). © 1971 American Psychological Association.
2 citations (Crossref) [2023-10-31] tex.ids: pop00125 tex.type: Journal article
Keywords: Conflict (Psychology); Cues; Depth Perception; Female; Form Perception; Human; Male; Reaction Time; Size Perception; Vision; article; association; conflict; dept.psy; depth perception; female; human; male; pattern recognition; perception; reaction time; steroscopic depth perception facilitation; relative-size cue in ambiguous disparity stereograms; vision

Student teachers as tutors for children in an inner city school - Levine, Murray; Dunn, Freda; Brochinsky, Steve; Bradley, Jesse; Donlan, Kay (Child Psychiatry & Human Development, 1970)
A tutoring program for first grade inner city children, employing student teachers as tutors, was developed and evaluated. Tutoring had no discernible effects on performance on the Illinois Test of Psycholinguistic Ability. However, tutored children were placed in the highest reading group, and were rated by the regular classroom teacher as having completed the first grade reading series more often than controls. Tutors saw their children as becoming more responsive over time. Classroom teachers rated the tutored children as more competent in the classroom, more confident, and as viewing the classroom as more benevolent. In contrast to controls, student teachers maintained favorable attitudes toward teaching in the inner city, and they claimed to have benefited in practice teaching from their tutoring experience. However, relatively few actually took teaching positions in inner city schools after completing their training. © 1972 Behavioral Publications, Inc.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-055-959-212-774 tex.type: [object Object]
Keywords: dept.psy

The mental patient and civil rights: Some moral, legal, and ethical considerations. - Tolchin, Gerald; Steinfeld, George; Suchotliff, Leonard (Professional Psychology, 1970)
Distinguishes between legal, ethical, and egalitarian principles involving hospitalization of persons alleged to be mentally ill. With regard to the question of legality, the need for compilation and distribution of relevant information and for informing patients of their rights is discussed. The boundaries of psychologists' professional and personal ethics are viewed as helping patients obtain services which they are personally unable to provide and insuring that the welfare of the patient is placed before the interests of the institution. Egalitarian issues are discussed with regard to: (a) judging whether a mental patient is responsible for his words and actions; (b) the patient's right to accept, reject, or select treatment; and (c) hospitalization of general medical patients and their rights to be informed about their condition, to be notified of test results, and to know the name, quantity, and expected reaction to drugs they are given. It is suggested that psychologists have too long been silent on these issues and in the face of abuses, and that more discussion and stands on them are needed. (PsycINFO Database Record (c) 2006 APA, all rights reserved). © 1970 American Psychological Association.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/002-538-943-386-031 tex.type: [object Object]
Keywords: dept.psy; moral vs. legal vs. ethical considerations regarding hospitalization of mentally ill

Development of a reduced set of composite equations for three predictors - Karas, Siiawky F (Psychological Reports, 1969)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/123-416-800-173-540 tex.type: [object Object]
Keywords: dept.psy

The analysis of means techniques - Karas, Shawky F (Journal of Experimental Education, 1968)
The theoretical basis for the Analysis of Means Technique is discussed. In addition, a simplified working procedure is outlined, step-by-step for an actual problem. The data for the problem are analyzed by the analysis of means techniques, which compares differences between means instead of population variances estimates. The data are also analyzed by the analysis of variance technique. The conclusions reached by both techniques are the same. The graphical representation of the ANOM is helpful in understanding data. The ANOM technique is usually used in conjunction with the analysis of variance, either as an initial analysis of data or to augment the analysis of variance. © Taylor & Francis Group, LLC.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/014-336-055-173-505 tex.type: [object Object]
Keywords: dept.psy

Preventing maladjustment from infancy through adolescence - rickel,au, allen,l - Glick, M (Contemporary Psychology, 1989)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1989CE35400063
Keywords: dept.psy

Theories of probabilistic reinforcement. - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1989)
In three experiments, pigeons chose between two alternatives that differed in the probability of reinforcement and the delay to reinforcement. A peck at a red key led to a delay of 5 s and then a possible reinforcer. A peck at a green key led to an adjusting delay and then a certain reinforcer. This delay was adjusted over trials so as to estimate an indifference point, or a duration at which the two alternatives were chosen about equally often. In Experiments 1 and 2, the intertrial interval was varied across conditions, and these variations had no systematic effects on choice. In Experiment 3, the stimuli that followed a choice of the red key differed across conditions. In some conditions, a red houselight was presented for 5 s after each choice of the red key. In other conditions, the red houselight was present on reinforced trials but not on nonreinforced trials. Subjects exhibited greater preference for the red key in the latter case. The results were used to evaluate four different theories of probabilistic reinforcement. The results were most consistent with the view that the value or effectiveness of a probabilistic reinforcer is determined by the total time per reinforcer spent in the presence of stimuli associated with the probabilistic alternative. According to this view, probabilistic reinforcers are analogous to reinforcers that are delivered after variable delays. 1989 Society for the Experimental Analysis of Behavior
72 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/098-819-689-500-794 tex.type: [object Object]
Keywords: Animal; Color Perception; Conditioning; Operant; Mental Recall; Probability Learning; Reinforcement Schedule; Support; U.S. Gov't; P.H.S.; adjusting schedule; animal; article; color vision; conditioned reinforcement; dept.psy; instrumental conditioning; intertrial interval; key peck; learning; pigeons; recall; reinforcement; reinforcer delay; reinforcer probability

The need to test hypotheses about paranoid schizophrenia: reply to Clementz and Sweeney. - Glick, Marion; Zigler, Edward (American Psychologist, 1989)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/079-001-880-085-55X tex.type: [object Object]
Keywords: dept.psy

Depression: A failure to suppress the self-conscious ‘Monitoring’ of dismal cognitions - Kunzendorf, Robert G; Mclaughlin, Susan (Imagination, Cognition and Personality, 1989)
11 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/061-928-824-373-602 tex.type: [object Object]
Keywords: dept.psy

Is paranoid schizophrenia really camouflaged depression - Zigler, Edward; Glick, Marion (American Psychologist, 1988)
85 citations (Crossref) [2023-10-31] tex.type: Journal article
Keywords: dept.psy

Effect of lysine-8-vasopressin on retention and retrieval of a discrimination reward task in the rat. - Mulvey, Debra J; Watt, Jean M; Mcewen, Barbara B; Flannelly, Linda M (Behavioral Neuroscience, 1988)
The effect of vasopressin on memory of a brightness discrimination reward task was investigated in 20 male Sprague-Dawley rats. Two measures of retention were used: resistance to extinction and savings scores on a reacquisition task given 45 days after the completion of extinction training. The effect of the peptide on both memory consolidation and retrieval was assessed. There were two major findings: (a) The peptide enhanced memory consolidation of the task whether measured after a short time interval (6 days) or after a long time interval (45 days after completion of extinction training) using a measure of trials to relearn the task, and (b) the peptide had no effect on memory retrieval. These results were compared to those of other studies designed to access memory consolidation and retrieval on appetitive tasks. The mechanisms of the peptide's effect on memory was briefly discussed with respect to three theories on the subject. This study extends the vasopressin research on memory consolidation by suggesting that it pertains to appetitive as well as to aversive tasks.
5 citations (Crossref) [2023-10-31] tex.type: Journal article
Keywords: Animal; Appetitive Behavior; Brain; Conditioning; Operant; Discrimination Learning; Extinction (Psychology); Lypressin; Male; Memory; Mental Recall; Motivation; Orientation; Rats; Rats; Inbred Strains; Retention (Psychology); animal experiment; controlled study; dept.psy; lypressin; male; memory consolidation; memory retrieval; nonhuman; psychological aspect; psychophysiology; rat; reward

Premorbid competence, role orientation, and gender differences in DSM-II versus DSM-III schizophrenic patients. - Glick, Marion; Quinlan, Donald M; Zigler, Edward (Journal of Consulting and Clinical Psychology, 1987)
The study compared 71 patients diagnosed as schizophrenic or within the schizophrenia spectrum according to the second edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-II) with 66 patients who received similar diagnoses according to the third edition of the same manual (DSM-III). On measures of premorbid competence and role orientation, DSM-II and DSM-III schizophrenic patients obtained comparable scores. The DSM-III patients with schizophrenic versus schizophrenia spectrum diagnoses also obtained comparable scores on these measures. The gender differences in premorbid competence and role orientation that have consistently characterized DSM-II schizophrenics continued to characterize DSM-III schizophrenic and schizophrenia spectrum patients. The results suggest that findings previously obtained with DSM-II schizophrenics concerning premorbid competence and role orientation can be generalized to DSM-III schizophrenics. © 1987 American Psychological Association.
3 citations (Crossref) [2023-10-31] tex.type: Journal article
Keywords: adult; classification; competence; dept.psy; gender; human; major clinical study; orientation; schizophrenia

Effectiveness of the Mini-Mult in detecting MMPI pathology in the blind - Needham, Walter E.; Ehmer, Marjy N.; Marchesseault, Linda; l'Aune, William R. De (Journal of Clinical Psychology, 1986)
The Mini‐Mult and MMPI were administered in random order to 60 blind male veterans admitted to a residential rehabilitation program. Mini‐Mult scores predicted the presence or absence of MMPI pathology in 81.7% of the cases. Correlations between the individual Mini‐Mult and MMPI scales were significant at the p < .01 level, but not of sufficient magnitude to permit their interchangeability or to allow for profile diagnosis on the basis of Mini‐Mult scores. Analysis of the false negatives raises questions about the clinical significance of an abnormal MMPI in the population studied. The results support the value of the Mini‐Mult as a screening device, but not as a substitute for a detailed psychological assessment of the blind. Copyright © 1986 Wiley Periodicals, Inc., A Wiley Company
4 citations (Crossref) [2023-10-31] Citation Key Alias: pop00119 tex.type: [object Object]
Keywords: Blindness; Human; MMPI; Male; Mass Screening; Mental Disorders; Middle Age; adult; blindness; central nervous system; clinical article; dept.psy; human; priority journal; psychological aspect; rehabilitation; visual system

Premorbid social competence and psychiatric outcome in male and female nonschizophrenic patients - Glick, Marion; Zigler, Edward (Journal of Consulting and Clinical Psychology, 1986)
The relation between premorbid social competence and outcome was examined in 448 (228 male and 220 female) first-admission, nonschizophrenic, state-hospital patients. For both sexes, higher social competence was related to more favorable outcome as reflected in shorter initial hospitalizations and shorter rehospitalizations. Consistent with a developmental formulation, these results provide further evidence that the relation between premorbid competence and outcome is not unique to schizophrenia but can be found for patients of both sexes across a range of diagnoses. © 1986 American Psychological Association.
12 citations (Crossref) [2023-10-31] tex.type: Journal article
Keywords: adult; central nervous system; clinical article; competence; dept.psy; human; mental patient; psychological aspect; social aspect; social behavior; therapy

Young-children reinvent arithmetic - implications of piaget theory - kamii,ck, declark,g - Smith, JP (Teachers College Record, 1986)
tex.unique-id: ISI:A1986D941000011
Keywords: dept.psy; ⛔ No DOI found

Developmental correlates of age at first hospitalization in nonschizophrenic psychiatric patients - Glick, M.; Zigler, E.; Zigler, B. (Journal of Nervous and Mental Disease, 1985)
Age at first hospitalization, premorbid social competence, and developmental categorizations of symptomatology were examined in 228 male and 220 female patients in three diagnostic categories: Major affective disorder, neuroses, and personality disorder. High social competence patients were older at first hospitalization than low competence individuals. Younger first admission patients showed more symptoms in the action category and in the role orientation of turning against others. Older patients more frequently displayed symptoms of the thought variety and of turning against the self. Gender differences in age at first hospitalization were not found. With respect to all developmental variables examined, the results suggest that a broader view of prognosis proposed in research with schizophrenic patients is applicable to nonschizophrenic groups. © 1985 by The Williams & Wilkins Co.
15 citations (Crossref) [2023-10-31]
Keywords: Adult; Age Factors; Female; Hospitalization; Human; Male; Marriage; Mental Disorders; Middle Age; Mood Disorders; Neurotic Disorders; Occupations; Personality Disorders; Prognosis; Role; Sex Factors; Social Adjustment; Support; Non-U.S. Gov't; Support; U.S. Gov't; P.H.S.; affective neurosis; age; central nervous system; clinical article; dept.psy; hospitalization; human; mental patient; neurosis; personality disorder; priority journal; psychological aspect; social aspect; sociology

Paranoid schizophrenia: An unorthodox view. - Zigler, Edward; Glick, Marion (American Journal of Orthopsychiatry, 1984)
12 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1984SB44900004 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.psy

Parent diary - a technique for sampling the expressive language of hearing-impaired children - Kessler, ME (Volta Review, 1983)
tex.unique-id: ISI:A1983QK55500004
Keywords: dept.psy; ⛔ No DOI found

Complexity of context and orientation of figure in the corridor illusion - Fineman, Mark B (Perceptual and Motor Skills, 1981)
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/007-837-285-081-691 tex.type: [object Object]
Keywords: dept.psy

Comparison of competitive trait anxiety levels of 9-12-year-old participants in little league and neighborhood baseball - Finn, JA; Sprague, LK (International Journal of Sport Psychology, 1981)
tex.unique-id: ISI:A1981ML28300017
Keywords: dept.psy; ⛔ No DOI found

Premorbid social competence and the revolving door phenomenon in psychiatric hospitalization - Marsh, A.; Glick, M.; Zigler, E. (Journal of Nervous and Mental Disease, 1981)
The relation between premorbid social competence and length of initial hospitalization was examined in 381 male state hospital patients in four diagnostic categories: Schizophrenic, affective reaction, psychoneurotic, and personality disorder. A significant relation was discovered between diagnosis and outcome, with schizophrenic patients having the longest and personality disorder patients the shortest lengths of initial hospitalization. Premorbid social competence was related to outcome, as assessed both by length of initial hospitalization, and by whether the patient was rehospitalized. These two outcome measures were found to be positively related, thus supporting the developmental formulation that premorbid social competence is indicative generally of prognosis. The findings were employed to generate the inference that patients at differing levels of premorbid social competence require different treatment modalities. © 1981 by The Williams & Wilkins Co.
8 citations (Crossref) [2023-10-31]
Keywords: Adult; Hospitals; Psychiatric; Human; Length of Stay; Male; Mental Disorders; Mood Disorders; Neurotic Disorders; Personality Disorders; Recurrence; Schizophrenia; Social Adjustment; central nervous system; dept.psy; major clinical study; mental hospital; personality disorder; schizophrenia; sociology

Inter-relationships among hospitalization measures of psychiatric outcome - Glick, M.; Marsh, A.; Zigler, E. (Journal of Nervous and Mental Disease, 1980)
In a diagnostically heterogeneous sample of 381 first admission male state hospital patients, no consistent correlations appeared among three commonly employed hospitalization measures of outcome. The possibility that psychiatric hospitalization may be a multidimensional criterion is considered and the implications for outcome research are discussed. © 1980 by The Williams & Wilkins Co.
3 citations (Crossref) [2023-10-31]
Keywords: Follow-Up Studies; Hospitalization; Human; Length of Stay; Male; Mental Disorders; Models; Theoretical; Patient Readmission; Support; U.S. Gov't; P.H.S.; central nervous system; dept.psy; hospitalization; major clinical study; therapy

Irrational thinking and adjustment to loss of vision - Needham, WE; Ehmer, MN (Journal of visual impairment & blindness, 1980)
11 citations (Crossref) [2023-10-31] tex.eissn: 1559-1476 tex.unique-id: ISI:A1980JK16600003
Keywords: dept.psy

Premorbid Social Competence and Outcome among Schizophrenic and Nonschizophrenic Patients - Zigler, Edward; Glick, Marion; Marsh, Anna (The Journal of Nervous and Mental Disease, 1979)
The relation between premorbid social competence and outcome was examined with 381 male state hospital patients in four diagnostic categories: schizophrenia, affective reaction, psychoneurotic disorder, and personality disorder. Outcome was assessed using the measures of length of initial hospitaliz
26 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1979HL47900004 tex.unique-id: [object Object]
Keywords: Affective Symptoms; Hospitals; Psychiatric; Human; Length of Stay; Male; Neurotic Disorders; Outcome and Process Assessment (Health Care); Personality Disorders; Prognosis; Schizophrenia; Schizophrenic Psychology; Social Adjustment; Support; U.S. Gov't; P.H.S.; affective neurosis; central nervous system; dept.psy; hospitalization; major clinical study; neurosis; personality disorder; schizophrenia; sociology; therapy

Normal development and psychopathological impairment of the concept of the object on the Rorschach. - Blatt, Sidney J.; Brenneis, C. Brooks; Schimek, Jean G.; Glick, Marion (Journal of Abnormal Psychology, 1976)
103 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1976CB12400004 tex.unique-id: [object Object]
Keywords: dept.psy

Preferences for and against stimuli paired with food - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1999)
Pigeons were presented with a concurrent-chains schedule in which terminal-link entries were assigned to two response keys on a percentage basis. The terminal links were fixed delays that sometimes ended with food and sometimes did not. In most conditions, 80% of the terminal links were assigned to one key, but a smaller percentage of the terminal links ended with food for this key, so the number of food reinforcers delivered by the two alternatives was equal. When the same terminal-link stimuli (orange houselights) were used for both alternatives, the pigeons showed a preference for whichever alternative delivered more frequent terminal links. When different terminal-link stimuli (green vs. red houselights) were used for the two alternatives, the pigeons showed a preference for whichever alternative delivered fewer terminal links when terminal-link durations were long, and no systematic preferences when terminal-link durations were short. This pattern of results was consistent with the predictions of Grace's (1994) contextual choice model. Preference for the alternative that delivered more frequent terminal links was usually stronger in the first few sessions of a condition than at the end of a condition, suggesting that the conditioned reinforcing effect of the additional terminal-link presentations was, in part, transitory.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/006-990-830-192-667 tex.type: [object Object]
Keywords: *Choice Behavior/ph [Physiology]; *Feeding Behavior/px [Psychology]; *Food Preferences; Animals; Behavior; Animal; Behavior; Animal/ph [Physiology]; Choice; Choice Behavior; Columbidae; Concurrent chains; Conditioned reinforcement; Conditioning (Psychology); Conditioning; Psychological; Feeding Behavior; Food Preferences; Key peck; Pigeons; Reinforcement (Psychology); Reinforcement probability; Reinforcement; Psychology; animal; animal behavior; article; conditioning; decision making; dept.psy; feeding behavior; food preference; physiology; pigeons and doves; psychological aspect; reinforcement

Compliance, noncompliance strategies, and the correlates of compliance in 5-year-old japanese and american children - Abe, Jo Ann A; Izard, Carroll E (Social Development, 1999)
The present study compared compliance, noncompliance strategies, and the correlates in 5-year old Japanese and American children were observed during three standardized laboratory procedures. Compliance, noncompliance strategies, and negative affect were coded during Toy Pick Up procedure. Maternal directiveness and mother-directed behaviors were coded during Mother-Child play and Free-play procedures, respectively. A baseline level of play was also obtained during the Free Play procedures to ensure that the children's willingness to engage in the Toy Pick Up procedure would not be confounded with their level of involvement with the toys. Consistent with predictions derived from a review of cross-cultural research on socialization practices, Japanese children showed longer latencies to begin picking up toys in response to maternal requests and were also more likely to engage in the `less skilled' noncompliance strategies of direct defiance and passive noncompliance than American children. The two groups of children did not, however, differ in their level of negative affect during the Toy Pick Up procedure. Contrary to expectations, maternal directiveness was not associated with compliance in either group of children. However, approach behavior to mother during Free Play was inversely correlated with compliance in Japanese, but not American children.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/066-397-543-896-492 tex.type: [object Object]
Keywords: Compliance; Cross-cultural; Preschool children; Self-regulation; dept.psy

A comparative study of quiet sleep, active sleep, and waking on the first 2 days of life - Carroll, D.A.; Denenberg, V.H.; Thoman, E.B. (Developmental Psychobiology, 1999)
Direct behavioral observation and motility monitoring procedures provide reliable data, and both are appropriate for sleep/wake state measurements starting immediately after birth. Using these procedures, newborn rats, rabbits, and humans were found to have a greater amount of quiet sleep on the day of birth rather than 24 hr later. Changes in active sleep and wake were inconsistent across the 2 days. The quiet sleep findings are contrary to the developmental course which increases with age. The findings are interpreted as a temporary adaptive response to the stress of the birth process.
12 citations (Crossref) [2023-10-31]
Keywords: Animalia; Animals; Animals and human infants; Animals; Newborn; Cross-species sleep; Female; Humans; Infant; Newborn; Male; Motor Activity; Newborn sleep; Oryctolagus cuniculus; Pregnancy; Rabbits; Rats; Sleep Stages; Sleep in neonates; Sleep; REM; Sleep/wake states in neonates; Species Specificity; Wakefulness; adaptive behavior; animal behavior; animal experiment; article; breathing rate; child behavior; dept.psy; human; human experiment; infant; nonhuman; normal human; rabbit; rat; sleep pattern; sleep time; sleep waking cycle; stress

Choice with delayed and probabilistic reinforcers: Effects of prereinforcer and postreinforcer stimuli - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1998)
In Experiment 1, pigeons' pecks on a green key led to a 5-s delay with green houselights, and then food was delivered on 20% (or, in other conditions, 50%) of the trials. Pecks on a red key led to an adjusting delay with red houselights, and then food was delivered on every trial. The adjusting delay was used to estimate indifference points: delays at which the two alternatives were chosen about equally often. Varying the presence or absence of green houselights during the delays that preceded possible food deliveries had large effects on choice. In contrast, varying the presence of the gr een or red houselights in the intertrial intervals had no effects on choice. In Experiment 2, pecks on the green key led to delays of either 5 s or 30 s with green houselights, and then food was delivered on 20% of the trials. Varying the duration of the green houselights on nonreinforced trials had no effect on choice. The results suggest that the green houselights served as a conditioned reinforcer at some rimes but not at others, depending on whether or nor there was a possibility that a primary reinforcer might be delivered. Given this interpretation of what constitutes a conditioned reinforcer, most of the results were consistent with the view that the strength of a conditioned reinforcer is inversely related to its duration.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/010-649-994-407-690 tex.type: [object Object]
Keywords: *Choice Behavior/ph [Physiology]; *Conditioning; Psychological/ph [Physiology]; *Reinforcement; Psychology; Animals; Behavior; Animal; Behavior; Animal/ph [Physiology]; Choice; Choice Behavior; Columbidae; Conditioned reinforcement; Conditioning (Psychology); Delay; Key peck; Pigeons; Probability; Reinforcement (Psychology); Time Factors; animal; animal behavior; article; comparative study; conditioning; decision making; dept.psy; physiology; pigeons and doves; reinforcement; time

A longitudinal study of AIDS conversations between mothers and adolescents - Lefkowitz, ES; Kahlbaugh, P; Au, TKF; Sigman, M (Aids Education and Prevention, 1998)
The current study examined the stability of mother-adolescent AIDS conversations. Twenty-four mother-adolescent dyads (9 boys, 15 girls) participated at Time 1 (adolescents aged 10-14 years), and again 2 years later. Mothers and adolescents engaged in a videotaped conversation about AIDS and completed AIDS questionnaires. Conversations were coded for content and the extent to which mothers dominated conversations. Conversational dominance remained stable over time. AIDS knowledge was greater for mothers than adolescents, but it improved over time for adolescents while remaining stable for mothers. Mothers who reported discussing AIDS-related topics with their adolescents had less discrepancy between their own and their children's AIDS knowledge. Conversational dominance at Time 1 predicted discrepancy in AIDS knowledge 2 years later, whereas discrepancy in AIDS knowledge at Time 1 did not predict conversational dominance two years later. These results suggest the importance of interactive conversations as a more effective way of teaching than didactic conversations.
tex.orcid-numbers: Au, Terry/0000-0001-5810-488X tex.researcherid-numbers: Au, Terry/P-6045-2019 Au, Terry/A-2285-2010 tex.unique-id: ISI:000075395900006
Keywords: dept.psy; ⛔ No DOI found

Procrastination by pigeons with fixed-interval response requirements - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1998)
Two experiments studied the phenomenon of procrastination, in which pigeons chose a larger, more delayed response requirement over a smaller, more immediate response requirement. The response requirements were fixed-interval schedules that did not lead to an immediate food reinforcer, but that interrupted a 55-s period in which food was delivered at random times. The experiments used an adjusting-delay procedure in which the delay to the start of one fixed-interval requirement was varied over trials to estimate an indifference point-a delay at which the two alternatives were chosen about equally often. Experiment 1 found that as the delay to a shorter fixed-interval requirement was increased, the adjusting delay to a longer fixed-interval requirement also increased, and the rate of increase depended on the duration of the longer fixed-interval requirement. Experiment 2 found a strong preference for a fixed delay of 10 s to the start of a fixed-interval requirement compared to a mixed delay of either 0 or 20 s. The results help to distinguish among different equations that might describe the decreasing effectiveness of a response requirement with increasing delay, and they suggest that delayed reinforcers and delayed response requirements have symmetrical but opposite effects on choice.
7 citations (Crossref) [2023-10-31] Place: United States Mazur, J E. Psychology Department, Southern Connecticut State University, New Haven, USA. mazur@scsu.ctstateu.edu
Keywords: *Behavior; Animal/ph [Physiology]; *Choice Behavior; *Feeding Behavior/px [Psychology]; *Reinforcement Schedule; Animals; Behavior; Animal; Choice; Choice Behavior; Columbidae; Delay; Feeding Behavior; Fixed-interval schedules; Key peck; Models; Psychological; Pigeons; Procrastination; Reinforcement (Psychology); Reinforcement Schedule; Reinforcement; Psychology; Time Factors; animal; animal behavior; article; comparative study; decision making; dept.psy; feeding behavior; physiology; pigeons and doves; psychological aspect; psychological model; reinforcement; time

Choice and Self-Control - Mazur, James E. (Handbook of Research Methods in Human Operant Behavior, 1998)
For several decades, choice has been the focus of considerable research by those who study operant behavior. This is not surprising, because the topics of choice and operant behavior are intimately intertwined. In everyday life, people can choose among a large, almost infinite set of operant behaviors, and they can choose not only which behaviors to perform, but under what conditions, at what rate, and for how long. Because choice is an essential part of human (and animal) life, it has been studied with great interest not only by behavioral psychologists, but also by decision theorists, economists, political scientists, biologists, and others. The research methods used in these different disciplines vary widely, and a review of all of the different methods for studying choice is well beyond the scope and purpose of this chapter. Instead, the chapter will focus on the techniques most frequently used in operant research—techniques that involve single-subject designs, that allow precise control of the reinforcement contingencies, and that produce (in most cases) large and clear effects on each subject’s behavior.
Citation Key Alias: lens.org/051-873-009-186-896, pop00093
Keywords: Conditioned Reinforcer; Discriminative Stimulus; Indifference Point; Reinforcement Schedule; Terminal Link; dept.psy

Effects of Rate of Reinforcement and Rate of Change on Choice Behaviour in Transition - Mazur, J.E. (Quarterly Journal of Experimental Psychology Section B: Comparative and Physiological Psychology, 1997)
In two experiments with pigeons, a single variable-interval schedule assigned reinforcers to two response keys on a percentage basis. The percentage of reinforcers assigned to each key was changed every few sessions, and subjects' choice responses were recorded before and after each change. In Experiment 1, the overall rate of reinforcement was varied across conditions The pigeons' choice responses adapted more quickly to a change in the reinforcement percentages when the overall reinforcement rates were higher, but acquisition rates varied by only about a factor of 3, whereas reinforcement rates were varied by about a factor of 9. In Experiment 2, the reinforcement percentages changed about every 8 sessions in Phases 1 and 3, but every 1 or 2 sessions in Phase 2. Pigeons' choice responses adapted to a change in reinforcement percentages more quickly in Phase 2 than in Phases 1 and 3. The results from both experiments pose difficulties for several prominent models of transitional choice behaviour. The results suggest that each successive reinforcer has more impact on a subject's subsequent choice behaviour when the overall rate of reinforcement is lower and when the reinforcement contingencies have changed frequently in the recent past.
Keywords: *Choice Behavior; *Reinforcement; Psychology; Animals; Behavior; Animal; Choice Behavior; Columbidae; Reinforcement (Psychology); animal; animal behavior; article; comparative study; decision making; dept.psy; pigeons and doves; reinforcement; ⛔ No DOI found

Comparative affective reactivity of different types of communication disturbances in schizophrenia - Docherty, Nancy M; Hebert, Anthony S (Journal of Abnormal Psychology, 1997)
34 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/058-153-643-757-958 tex.type: [object Object]
Keywords: dept.psy

Basic and applied research on choice responding - Fisher, Wayne W; Mazur, James E (Journal of Applied Behavior Analysis, 1997)
Choice responding refers to the manner in which individuals allocate their time or responding among available response options. In this article, we first review basic investigations that have identified and examined variables that influence choice responding, such as response effort and reinforcement rate, immediacy, and quality. We then describe recent bridge and applied studies that illustrate how the results of basic research on choice responding can help to account for human behavior in natural environments and improve clinical assessments and interventions.
136 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/094-509-768-839-105 tex.type: [object Object]
Keywords: dept.psy

The affective nature of Mother–Adolescent communication concerning sexuality and conflict - Kahlbaugh, Patricia E; Lefkowitz, Eva S; Valdez, Patricia; Sigman, Marian (Journal of Research on Adolescence, 1997)
This 2-year longitudinal study examined the affective nature of communication between mothers and adolescents from early to mid-adolescence. Eleven-to 16-year-old adolescents and their mothers were videotaped while engaging in conversations about everyday topics, dating and sexuality, and conflicts. Nonverbal displays of affiliation, embarrassment, and contempt were found to be fairly stable across conversations, across members of the same dyad, and across time for the mothers. However, there were some effects of conversational topic in that adolescents displayed less affiliation in the conflict conversation than in the other conversations during the 1st session. In addition, boys displayed more contempt when talking about dating and sexuality than about conflicts. Over the 2-year period, the level of affiliation decreased for adolescents, and maternal conversational dominance increased. In all conversations and at both time periods, adolescents displayed more embarrassment and contempt and less affiliation than did mothers. Both maternal and adolescent levels of affiliation during the conversations in the 1st session predicted degree of satisfaction with certain family characteristics expressed in the 2nd session. Copyright © 1997, Lawrence Erlbaum Associates, Inc.
19 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/085-813-705-746-702 tex.type: [object Object]
Keywords: dept.psy

Choice, delay, probability, and conditioned reinforcement - Mazur, James E (Animal Learning & Behavior, 1997)
The hyperbolic-decay model is a mathematical expression of the relation between delay and reinforcer value. The model has been used to predict choices in discrete-trial experiments on delay-amount tradeoffs, on preference for variable over fixed delays, and on probabilistic reinforcement. Experiments manipulating the presence or absence of conditioned reinforcers on trials that end without primary reinforcement have provided evidence that the hyperbolic-decay model actually predicts the strength of conditioned reinforcers rather than the strength of delayed primary reinforcers. The model states that the strength of a conditioned reinforcer is inversely related to the time spent in its presence before a primary reinforcer is delivered. A possible way to integrate the model with Grace's (1994) contextual-choice model for concurrent-chain schedules is presented. Also discussed are unresolved difficulties in determining exactly when a stimulus will or will not serve as a conditioned reinforcer.
95 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/068-690-976-083-37X tex.type: [object Object]
Keywords: article; behavior; conditioning; decision making; dept.psy; model; nonhuman; reinforcement; theory

Choice with certain and uncertain reinforcers in an adjusting-delay procedure - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1996)
A discrete-trials adjusting-delay procedure was used to investigate the conditions under which pigeons might show a preference for partial reinforcement over 100% reinforcement, an effect reported in a number of previous experiments. A peck on a red key always led to a delay with red houselights and then food. In each condition, the duration of the red-houselight delay was adjusted to estimate an indifference point. In 100% reinforcement conditions, a peck on a green key always led to a delay with green houselights and then food. In partial-reinforcement conditions, a peck on the green key led either to the green houselights and food or to white houselights and no food. In some phases of the experiment, statistically significant preference for partial reinforcement over 100% reinforcement was found, but this effect was observed in only about half of the pigeons. The effect was largely eliminated when variability in the delay stimulus colors was equated for 50% reinforcement conditions and 100% reinforcement conditions. Idiosyncratic preferences for certain colors or for stimulus variability may be at least partially responsible for the effect.
30 citations (Crossref) [2023-10-31] Place: United States Mazur, J E. Psychology Department, Southern Connecticut State University, New Haven, Connecticut 06515, USA.
Keywords: *Appetitive Behavior; *Choice Behavior; *Motivation; Animals; Appetitive Behavior; Choice; Choice Behavior; Color Perception; Columbidae; Conditioned reinforcers; Key peck; Motivation; Pigeons; Reinforcement Schedule; Reinforcement delay; Reinforcement probability; animal; appetite; article; color vision; decision making; dept.psy; motivation; pigeons and doves; reinforcement; ❓ Multiple DOI

Turn-taking in mother-adolescent conversations about sexuality and conflict - Lefkowitz, Eva S; Kahlbaugh, Patricia E; Sigman, Marian (Journal of Youth and Adolescence, 1996)
The current study examined the nature and style of mother-adolescent conversations, how these conversations differ by subject matter and dyadic and individual differences. Thirty-one mother-adolescent dyads (17 boys, 14 girls) with a child between the ages of 11 and 14 had a nonstructured conversation and conversations about conflict and sexuality They also completed questionnaires on beliefs about acquired immunodeficiency syndrome (AIDS). Conversations were measured for turn taking, total number of words, and conversational dominance, as well as nonverbal measures of affiliation, shame, and contempt Conversations about sexuality involved less turn taking, fewer words, and more mother dominance than nonstructured conversations. Conversations about conflicts involved less turn taking but more words than nonstructured conversations Some gender and age differences were found. Move interactive conflict conversations contained higher levels of affiliation, and lower levels of child shame than conversations with fewer turns or higher mother dominance. In addition, children in move interactive dyads possessed a larger percentage of their mother's AIDS knowledge, and worried about AIDS a moderate amount.
39 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/024-871-870-266-289 tex.type: [object Object]
Keywords: dept.psy

To forget or not to forget: The effect of probability of test on directed forgetting - Golding, JM; Roper, KL; Hauselt, J (Quarterly Journal of Experimental Psychology Section a-Human Experimental Psychology, 1996)
Two experiments investigated how individuals use explicit memory cues that designate different probabilities of test. As in typical directed forgetting studies, subjects received words explicitly cued as having either a 0% or a 100% chance of being on a subsequent memory test (i.e. forget and remember cues, respectively). In addition, some words were explicitly cued as having the potential to be either forgotten or remembered (i.e. a 50% cue). Recall of 50% words was between that of 0% and 100% words. In addition, the presence of 50% words lowered recall of the 100% words compared to that of a control group that did not receive the 50% words, but received the same number of 100% words. A think-aloud task indicated that these results were due to the 50% words being treated like either 100% or 0% words at encoding. The results are discussed in terms of the effect of different probabilities of test on the strategic processing and representation of information.
3 citations (Crossref) [2023-10-31] tex.orcid-numbers: Roper, Karen/0000-0002-7281-1713 tex.unique-id: ISI:A1996UV09500004
Keywords: Adult; Attention; Female; Humans; Male; Mental Recall; Probability Learning; Verbal Learning; adult; article; attention; dept.psy; female; human; learning; male; recall

Past experience, recency, and spontaneous recovery in choice behavior - Mazur, James E (Learning & Behavior, 1996)
Pigeons' responses on two keys were recorded before and after the percentage of reinforcers delivered by each key was changed. In each condition of Experiment 1, the reinforcement percentage for one key was 50% for several sessions, then either 70% or 90% for one, two, or three sessions, and then 50% for another few sessions. At the start of the second and third sessions after a change in reinforcement percentages, choice percentages often exhibited spontaneous recovery-a reversion to the response percentages of earlier sessions. The spontaneous recovery consisted of a shift toward a more extreme response percentage in some cases and toward a less extreme response percentage in other cases, depending on what reinforcement percentages were previously in effect. In Experiment 2, some conditions included a 3-day rest period before a change in reinforcement percentages, and other conditions included no such rest days. Slightly less spontaneous recovery was observed in conditions with the rest periods, suggesting that the influence of prior sessions diminished with the passage of time. The results are consistent with the view that choice behavior at the start of a new session is based on a weighted average of the events of the past several sessions.
37 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/143-816-663-594-485 tex.type: [object Object]
Keywords: Animalia; Columba; animal behavior; animal experiment; article; computer simulation; conditioning; decision making; dept.psy; experience; feeding; model; nonhuman; pigeon; reinforcement; reliability

STIR Success Through Individual Recreation: Working with the low-functioning resident with dementia or Alzheimer's disease: - Russen-Rondinone, Tonya; DesRoberts, Anne-Marie M. (American Journal of Alzheimer's Disease, 1996)
STIR, Success Through Individual Recreation is examined to determine the benefits of individualized recreational activities geared towards the lower functioning...
5 citations (Crossref) [2023-10-31]
Keywords: dept.psy

Procrastination by pigeons: Preference for larger, more delayed work requirements - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1996)
In three experiments, pigeons chose between alternatives that required the completion of a small ratio schedule early in the trial or a larger ratio schedule later in the trial. Completion of the ratio requirement did not lead to an immediate reinforcer, but simply allowed the events of the trial to continue. In Experiment 1, the ratio requirements interrupted periods in which food was delivered on a variable-time schedule. In Experiments 2 and 3, each ratio requirement was preceded and followed by a delay, and only one reinforcer was delivered, at the end of each trial. Two of the experiments used an adjusting-ratio procedure in which the ratio requirement was increased and decreased over trials so as to estimate an indifference point-a ratio size at which the two alternatives were chosen about equally often. These experiments found clear evidence for `'procrastination”-the choice of a larger but more delayed response requirement. In some cases, subjects chose the more delayed ratio schedule even when it was larger than the more immediate alternative by a factor of four or more. The results suggest that as the delay to the start of a ratio requirement is increased, it has progressively less effect on choice behavior, in much the same way that delaying a positive reinforcer reduces it effect on choice.
20 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/089-003-563-128-044 tex.type: [object Object]
Keywords: *Appetitive Behavior; *Conditioning; Operant; *Motivation; *Reinforcement Schedule; Animals; Appetitive Behavior; Attention; Choice; Choice Behavior; Columbidae; Conditioning; Operant; Delay; Inhibition (Psychology); Inhibition; Psychological; Key peck; Motivation; Pigeons; Problem Solving; Procrastination; Ratio schedules; Reinforcement Schedule; animal; appetite; article; attention; decision making; dept.psy; inhibition (psychology); instrumental conditioning; motivation; pigeons and doves; problem solving; reinforcement

The process of answering direction‐giving questions when someone is lost on a university campus: The role of pragmatics - Golding, Jonathan M; Graesser, Arthur C; Hauselt, Jerry (Applied Cognitive Psychology, 1996)
Two experiments investigated how college students answered direction-giving questions when a confederate asked for directions to a destination on a university campus. The experiments applied the QUEST model (Graesser and Franklin, 1990) to direction giving, emphasizing the pragmatic component of the model that focuses on establishing common ground and dealing with the questioner's goals. The two experiments had different articulations of the direction-giving question (i.e.'How do you get to destination X?' versus `Where is destination X?'), and a different destination. The answers generated by subjects supported both aspects of the pragmatic component.
27 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/070-512-736-743-674 tex.type: [object Object]
Keywords: dept.psy

Conditioned reinforcement and choice with delayed and uncertain primary reinforcers - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1995)
In an adjusting-delay choice procedure, pigeons could peck on either a red key or a green key. A peck on the red key always led to a delay associated with red houselights and then food. The delay was adjusted over trials to estimate an indifference point-a delay at which the two keys were chosen about equally often. In some conditions, a peck on the green key led to food on all trials after delays of either 10 a or 30 s, and green houselights were lit during the delays. In other conditions, food was presented on only half of the green-key trials. If the green houselights continued to occur on both reinforcement and nonreinforcement trials, preference for the green key always decreased. Preference for the green key also decreased if half of the trials had 30-s houselights followed by food and the other half had no green houselights and no food. However, preference for the green key actually increased if half of the trials had 10-s green houselights followed by food and the other half had no green houselights followed by no food. The latter condition therefore demonstrated a case in which preference for an alternative increased when food was removed from half of the trials. The results suggest that the red and green houselights served as conditioned reinforcers. A hyperbolic decay model (Mazur, 1989) provided good predictions for all conditions by assuming that the strength of a conditioned reinforcer is inversely related to the total time spent in its presence before food is delivered.
55 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/014-778-348-905-085 tex.type: [object Object]
Keywords: Animal; Association Learning; Choice Behavior; Color Perception; Conditioning; Operant; Discrimination Learning; Mental Recall; Motivation; Pigeons; Reinforcement Schedule; Retention (Psychology); Support; U.S. Gov't; P.H.S.; animal; article; choice; color vision; conditioned reinforcement; decision making; delay of reinforcement; dept.psy; discrimination learning; instrumental conditioning; key peck; learning; long term memory; motivation; pigeon; pigeons; probability of reinforcement; recall; reinforcement

Development of preference and spontaneous recovery in choice behavior with concurrent variable-interval schedules - Mazur, James E (Animal Learning & Behavior, 1995)
Pigeons pecked on two response keys that delivered reinforcers on a variable-interval schedule. The proportion of reinforcers delivered by one key was constant for a few sessions and then changed, and subjects' choice responses were recorded during these periods of transition. In Experiment 1, response proportions approached a new asymptote slightly more slowly when the switch in reinforcement proportions was more extreme. In Experiment 2, slightly faster transitions were found with higher overall rates of reinforcement. The results from the first session, after a switch in the reinforcement proportions, were generally consistent with a mathematical model that assumes that the strength of each response is increased by reinforcement and decreased by nonreinforcement. However, neither this model nor other similar models; predicted the `'spontaneous recovery” observed in later sessions: At the start of these sessions, response proportions reverted toward their preswitch levels. Computer simulations could mimic the spontaneous recovery by assuming that subjects store separate representations of response strength for each session, which are averaged at the start of each new session.
23 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/157-089-996-996-706 tex.type: [object Object]
Keywords: animal behavior; article; decision making; dept.psy; mathematical model; nonhuman; pigeon; reinforcement

Developmental differences in the symptomatology of psychiatric-inpatients with and without mild mental-retardation - Glick, M; Zigler, E (American Journal on Mental Retardation, 1995)
The symptomatology of psychiatric inpatients with mild mental retardation was compared with that of a matched sample of inpatients without mental retardation. An integration of the developmental position on mental retardation with the developmental approach to adult psychopathology generated the hypotheses that, compared to patients without mental retardation, patients with mild mental retardation would display (a) more symptoms indicative of turning against others and fewer symptoms indicative of turning against the self, (b) more symptoms involving expression in action rather than thought, and (c) psychotic symptom pictures that more frequently involve hallucinations without delusions and infrequently involve delusions alone. All hypotheses were confirmed.
Place: United States Glick, M. Southern Connecticut State University, USA.
Keywords: *Intellectual Disability/co [Complications]; *Mental Disorders/co [Complications]; Adult; Delusions/et [Etiology]; Female; Hallucinations/et [Etiology]; Hospitalization; Hospitals; Psychiatric; Humans; Male; Mental Disorders/px [Psychology]; Mental Disorders/rh [Rehabilitation]; dept.psy; ⛔ No DOI found

Effects of intertrial reinforcers on self-control choice. - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1994)
In three experiments, pigeons chose between a small amount of food delivered after a short delay and a larger amount delivered after a longer delay. A discrete-trial adjusting-delay procedure was used to estimate indifference points-pairs of delay-amount combinations that were chosen about equally often. In Experiment 1, when additional reinforcers were available during intertrial intervals on a variable-interval schedule, preference for the smaller, more immediate reinforcer increased. Experiment 2 found that this shift in preference occurred partly because the variable-interval schedule started sooner after the smaller, more immediate reinforcer, but there was still a small shift in preference when the durations and temporal locations of the variable-interval schedules were identical for both alternatives. Experiment 3 found greater increases in preference for the smaller, more immediate reinforcer with a variable-interval 15-s schedule than with a variable-interval 90-s schedule. The results were generally consistent with a model that states that the impact of any event that follows a choice response declines according to a hyperbolic function with increasing time since the moment of choice.
44 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/070-746-941-813-91X tex.type: [object Object]
Keywords: Animal; Appetitive Behavior; Choice Behavior; Color Perception; Conditioning; Operant; Mental Recall; Motivation; Pigeons; Reinforcement Schedule; Support; Non-U.S. Gov't; Support; U.S. Gov't; P.H.S.; animal; appetite; article; color vision; decision making; dept.psy; instrumental conditioning; intertrial reinforcers; key peck; motivation; pigeon; pigeons; recall; reinforcement; reinforcer amount; reinforcer delay; self‐control

Anhedonia and premorbid competence in young, nonpsychotic psychiatric inpatients. - Garnet, Kathleen E; Glick, Marion; Edell, William S (Journal of Abnormal Psychology, 1993)
Earlier studies have demonstrated a significant relation between scores on the Physical Anhedonia Scale-but not on the Perceptual Aberration Scale-and premorbid social adjustment in schizophrenics (Chapman, Chapman, & Raulin, 1976, 1978; Schuck, Leventhal, Rothstein, & Irizarry, 1984). A similar relation between scores on these 2 scales and interpersonal competence in college students has also been noted (Beckfield, 1985; Haberman, Chapman, Numbers, & McFall, 1979; Numbers & Chapman, 1982). The present study extends this work by examining the relation of premorbid adjustment to scores on these 2 scales among young, nonpsychotic psychiatric inpatients. Consistent with the earlier findings, anhedonic Ss had poorer premorbid social competence when compared with nonanhedonic Ss, whereas no relation was found between scores on perceptual aberration and premorbid social competence.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-972-234-241-121 tex.type: [object Object]
Keywords: Adolescent; Adult; Affective Symptoms; Female; Hospitalization; Human; Interpersonal Relations; Male; Perceptual Distortion; Personality Inventory; Psychiatric Status Rating Scales; Schizophrenia; Schizophrenic Psychology; Social Adjustment; adolescent; adult; article; competence; dept.psy; female; human; major clinical study; male; mental patient; neurosis; perception disorder; schizophrenia; social adaptation

Predicting the strength of a conditioned reinforcer: effects of delay and uncertainty: - Mazur, James E (Current Directions in Psychological Science, 1993)
22 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/088-251-746-085-397 tex.type: [object Object]
Keywords: dept.psy

Choice with delayed and probabilistic reinforcers: effects of variability, time between trials, and conditioned reinforcers - Mazur, James E; Romano, Angela (Journal of the Experimental Analysis of Behavior, 1992)
In a discrete-trials procedure with pigeons, a response on a green key led to a 4-s delay (during which green houselights were lit) and then a reinforcer might or might not be delivered. A response on a red key led to a delay of adjustable duration (during which red houselights were lit) and then a certain reinforcer. The delay was adjusted so as to estimate an indifference point-a duration for which the two alternatives were equally preferred. Once the green key was chosen, a subject had to continue to respond on the green key until a reinforcer was delivered. Each response on the green key, plus the 4-s delay that followed every response, was called one “link” of the green-key schedule. Subjects showed much greater preference for the green key when the number of links before reinforcement was variable (averaging four) than when it was fixed (always exactly four). These findings are consistent with the view that probabilistic reinforcers are analogous to reinforcers delivered after variable delays. When successive links were separated by 4-s or 8-s “interlink intervals” with white houselights, preference for the probabilistic alternative decreased somewhat for 2 subjects but was unaffected for the other 2 subjects. When the interlink intervals had the same green houselights that were present during the 4-s delays, preference for the green key decreased substantially for all subjects. These results provided mixed support for the view that preference for a probabilistic reinforcer is inversely related to the duration of conditioned reinforcers that precede the delivery of food.
21 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/131-277-176-129-505 tex.type: [object Object]
Keywords: Animal; Behavior; Animal; Choice Behavior; Competitive Behavior; Conditioning; Operant; Female; Instinct; Male; Models; Psychological; Pigeons; Reinforcement (Psychology); Reinforcement Schedule; Spatial Behavior; Support; U.S. Gov't; P.H.S.; animal; animal behavior; article; behavior; choice; competitive behavior; conditioned reinforcement; decision making; delay of reinforcement; dept.psy; drive; female; instrumental conditioning; key peck; male; model; pigeon; pigeons; probability of reinforcement; reinforcement

Choice behavior in transition : development of preference with ratio and interval schedules - Mazur, James E (Journal of Experimental Psychology: Animal Behavior Processes, 1992)
In Experiment 1, the choice responses of 8 pigeons were observed during 50 periods of transition. Each condition began with equal probabilities of reinforcement on 2 response keys and switched to unequal probabilities. With the ratio of the 2 probabilities held constant, preference for the higher probability developed more rapidly when the 2 probabilities were high than when they were low. In Experiment 2, each condition began with 2 equal variable-interval schedules, but later 1 key delivered 60%, 75%, or 90% of the reinforcers. The rate of approach to asymptotic performance was roughly the same with all 3 reinforcement percentages. These and previous results pose difficulties for some well-known models of acquisition, but the results are well described by a simple model that states that the strength of each response is independently increased by reinforcement and decreased by nonreinforcement.
30 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/033-292-029-733-246 tex.type: [object Object]
Keywords: dept.psy

Personal privacy and access to information on a college campus - a preliminary-report - Tolchin, G (Psychology, 1992)
A survey of college students concerning their knowledge and attitudes towards informational privacy was conducted. Virtually all subjects surveyed considered their personal privacy to be important to them. However, the survey results suggest considerable misunderstanding and misinformation regarding informational privacy. In addition, students showed little faith that their personal information was being securely protected against unauthorized disclosure. Indeed, they seemed to expect a considerable measure of privacy violation with respect to their student records.
tex.unique-id: ISI:A1992HQ53800002
Keywords: dept.psy; ⛔ No DOI found

Choice behavior in transition: Development of preference in a free-operant procedure - Mazur, James E; Ratti, Theresa A (Learning & Behavior, 1991)
Twenty acquisition curves were obtained from each of 8 pigeons in a free-operant choice procedure. Every condition began with a phase in which two response keys had equal probabilities of reinforcement, and, as a result, subjects' responses were divided fairly evenly between the two keys. This was followed by a phase in which one key had a higher probability of reinforcement than the other, and the development of preference was observed. In all but a few cases, response proportions increased for the key with the higher probability of reinforcement. In most conditions, the two probabilities differed by .06, but the actual probabilities varied (from .16 and .10 in one condition to .07 and .01 in another). Development of preference for the key with the higher probability of reinforcement was slower when the ratio of the two reinforcement probabilities was small (.16/.10) than when it was large (.07/.01). This finding is inconsistent with the predictions of several different quantitative models of acquisition, including the kinetic model (Myerson & Miezin, 1980) and the ratio-invariance model (Horner & Staddon, 1987). However, the finding is consistent with a hypothesis based on Weber's law, which states that the two alternatives are more discriminable when the ratio of their reinforcement probabilities is larger, and, as a result, the acquisition of preference is faster.
23 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/178-202-728-762-640 tex.type: [object Object]
Keywords: animal experiment; article; behavior; conditioned reflex; dept.psy; discrimination learning; instrumental conditioning; kinetics; model; nonhuman; pigeon; probability; reinforcement

Straining the word “optimal” - Mazur, James E (Behavioral and Brain Sciences, 1991)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/136-907-430-102-216 tex.type: [object Object]
Keywords: dept.psy

Choice with probabilistic reinforcement: effects of delay and conditioned reinforcers. - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1991)
Two experiments measured pigeons' choices between probabilistic reinforcers and certain but delayed reinforcers. In Experiment 1, a peck on a red key led to a 5-s delay and then a possible reinforcer (with a probability of .2). A peck on a green key led to a certain reinforcer after an adjusting delay. This delay was adjusted over trials so as to estimate an indifference point, or a duration at which the two alternatives were chosen about equally often. In all conditions, red houselights were present during the 5-s delay on reinforced trials with the probabilistic alternative, but the houselight colors on nonreinforced trials differed across conditions. Subjects showed a stronger preference for the probabilistic alternative when the houselights were a different color (white or blue) during the delay on nonreinforced trials than when they were red on both reinforced and nonreinforced trials. These results supported the hypothesis that the value or effectiveness of a probabilistic reinforcer is inversely related to the cumulative time per reinforcer spent in the presence of stimuli associated with the probabilistic alternative. Experiment 2 tested some quantitative versions of this hypothesis by varying the delay for the probabilistic alternative (either 0 s or 2 s) and the probability of reinforcement (from .1 to 1.0). The results were best described by an equation that took into account both the cumulative durations of stimuli associated with the probabilistic reinforcer and the variability in these durations from one reinforcer to the next.
43 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/070-304-798-844-976 tex.type: [object Object]
Keywords: Animal; Attention; Choice Behavior; Color Perception; Conditioning; Operant; Mental Recall; Pigeons; Probability Learning; Reinforcement Schedule; Support; U.S. Gov't; P.H.S.; Time Perception; adjusting schedule; animal; article; attention; color vision; conditioned reinforcement; decision making; dept.psy; instrumental conditioning; key peck; learning; pigeon; pigeons; recall; reinforcement; reinforcer delay; reinforcer probability; time perception

Choice behavior in transition: development of preference for the higher probability of reinforcement - Bailey, John T.; Mazur, James E. (Journal of the Experimental Analysis of Behavior, 1990)
Ten acquisition curves were obtained from each of 4 pigeons in a two‐choice discrete‐trial procedure. In each of these 10 conditions, the two response keys initially had equal probabilities of reinforcement, and subjects' choice responses were about equally divided between the two keys. Then the reinforcement probabilities were changed so that one key had a higher probability of reinforcement (the left key in half of the conditions and the right key in the other half), and in nearly every case the subjects developed a preference for this key. The rate of acquisition of preference for this key was faster when the ratio of the two reinforcement probabilities was higher. For instance, acquisition of preference was faster in conditions with reinforcement probabilities of .12 and .02 than in conditions with reinforcement probabilities of .40 and .30, even though the pairs of probabilities differed by .10 in both cases. These results were used to evaluate the predictions of some theories of transitional behavior in choice situations. A trial‐by‐trial analysis of individual responses and reinforcers suggested that reinforcement had both short‐term and long‐term effects on choice. The short‐term effect was an increased probability of returning to the same key on the one or two trials following a reinforcer. The long‐term effect was a gradual increase in the proportion of responses on the key with the higher probability of reinforcement, an increase that usually continued for several hundred trials. 1990 Society for the Experimental Analysis of Behavior
71 citations (Crossref) [2023-10-31] Citation Key Alias: pop00012 tex.type: [object Object]
Keywords: Animal; Attention; Choice Behavior; Color Perception; Discrimination Learning; Motivation; Orientation; Pigeons; Probability Learning; Reinforcement Schedule; Support; U.S. Gov't; P.H.S.; acquisition; animal; article; attention; choice; color vision; decision making; dept.psy; discrimination learning; key peck; learning; motivation; orientation; pigeon; pigeons; probability of reinforcement; reinforcement

Differences across gender, grade level, and academic track in the content of the ideal self-image - Bybee, Jane; Glick, Marion; Zigler, Edward (Sex Roles, 1990)
Students from the 5th, 8th, and 11th grades (55 male and 53 female) were asked to describe their ideal self-image. Analyses revealed a number of gender and developmental differences not found with other self-image measures. A greater proportion of females than males mentioned two of the categories related to family life: marriage and improving relations with their family of origin. Mentions of categories surrounding athletics were more prevalent among males. Grade level differences in the content of the ideal self-image reflected cognitive-developmental shifts away from concrete descriptors, changes in physical maturity and the heightened importance of peer relationships around adolescence, and the approach of developmental milestones. Fewer students mentioned physical appearance at higher grade levels. Mentions of athletic abilities and social acceptance peaked at the 8th grade, while mentions of college, marriage, and having children rose at higher grade levels. Differences in the content areas mentioned by average versus advanced track students appeared to reflect differences in both cognitive-developmental level and socialization experiences. © 1990 Plenum Publishing Corporation.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-509-861-539-600 tex.type: [object Object]
Keywords: dept.psy

Choice between delayed reinforcers and fixed‐ratio schedules requiring forceful responding - Mazur, James E; Kralik, J D (Journal of the Experimental Analysis of Behavior, 1990)
This experiment measured pigeons' choices between delayed reinforcers and fixed‐ratio schedules in which a force of approximately 0.48 N was needed to operate the response key. In ratio‐delay conditions, subjects chose between a fixed‐ratio schedule and an adjusting delay. The delay was increased or decreased several times a session in order to estimate an indifference point—a delay duration at which the two alternatives were chosen about equally often. Each ratio‐delay condition was followed by a delay‐delay condition in which subjects chose between the adjusting delay and a variable‐time schedule, with the components of this schedule selected to match the ratio completion times of the preceding ratio‐delay condition. The adjusting delays at the indifference point were longer when the alternative was a fixed‐ratio schedule than when it was a matched variable‐time schedule, which indicated a preference for the matched variable‐time schedules over the fixed‐ratio schedules. This preference increased in a nonlinear manner with increasing ratio size. This nonlinearity was inconsistent with a theory that states that indifference points for both time and ratio schedules can be predicted by multiplying the choice response‐reinforcer intervals of the two types of schedules by different multiplicative constants. Two other theories, which predict nonlinear increases in preference for the matched variable‐time schedules, are discussed. 1990 Society for the Experimental Analysis of Behavior
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/053-703-899-104-872 tex.type: [object Object]
Keywords: Animal; Choice Behavior; Conditioning; Classical; Exertion; Memory; Mental Recall; Motivation; Pigeons; Psychomotor Performance; Reinforcement Schedule; Support; U.S. Gov't; P.H.S.; adjusting procedure; animal; article; conditioned reflex; decision making; dept.psy; exercise; fixed ratio; key peck; memory; motivation; pigeon; pigeons; psychomotor performance; recall; reinforcement; reinforcer delay; response effort; variable time

A longitudinal study of emotion expression and personality relations in early development - Abe, J.A.A.; Izard, C.E. (Journal of Personality and Social Psychology, 1999)
To investigate emotion expression and personality relations, the authors coded infants' full-face and component positive and negative expressions during Episodes 4 through 8 of the strange situation procedure at age 18 months and obtained maternal ratings of the 5-factor model of personality when children were 3.5 years old. Full-face negative expression was directly related to Neuroticism and inversely related to Agreeableness and Conscientiousness. By contrast, component positive expression showed the exact opposite pattern of relations. Full-face positive expression was positively correlated with Extraversion and Openness to Experience. These findings indicate that full-face and component expressions may index different intensities of emotions. Emotion expression and personality relations were not mediated by the security of attachment continuum or the emotional reactivity dichotomy derived from the attachment subclassifications.
58 citations (Crossref) [2023-10-31]
Keywords: *Emotions; *Personality; Age Factors; Child; Preschool; Emotions; Female; Humans; Longitudinal Studies; Male; Personality; age; article; dept.ils; dept.psy; emotion; female; human; longitudinal study; male; personality; preschool child

College student sleep and executive functioning: An examination of potential moderators - Cifre, Anthony B.; Walters, Kenneth S.; Budnick, Christopher J. (Translational Issues in Psychological Science, 2020)
Approximately 60% of college students report sleep disturbances. Sleep disturbances, such as insomnia, negatively influence physical energy, cognitive resources, and affective states that might inhibit executive functioning. To better delineate the variables that alter the college student insomnia and executive functioning relationship we examined sleepiness, sleep debt, and attention-deficit/hyperactivity disorder (ADHD) symptomatology. We expected insomnia to predict executive dysfunction, with a stronger relationship observed at higher levels of the focal moderator (i.e., sleepiness, sleep debt, or ADHD symptoms). Undergraduate participants (n = 472) completed a cross-sectional survey assessing insomnia, state sleepiness, sleep debt, ADHD symptomatology (inattention, hyperactivity, and impulsivity), and executive dysfunction. Hierarchical linear regressions showed that poor sleep had a negative influence on executive function when college students also had high levels of impulsivity, state sleepiness, or sleep debt. These results partially support our expectations and further the academic sleep-related literature while providing insight for counselors, academic advisors, or other professionals working with college student populations. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
3 citations (Crossref) [2023-10-31] tex.ids: cifreCollegeStudentSleepinpress place: US
Keywords: Attention Deficit Disorder with Hyperactivity; College Students; Executive Function; Financial Strain; Insomnia; Sleep; Sleepiness; Symptoms; dept.psy; peer-reviewed

The predictive validity of the Five-Factor Model of personality with preschool age children: A nine year follow-up study☆ - Abe, Jo Ann A (Journal of Research in Personality, 2005)
This study examined whether maternal ratings of the Five-Factor Model (FFM) obtained when children were 3.5 years would show theoretically coherent patterns of relations with a variety of behavioral referents in the laboratory at 5 years as well as with maternal and self-ratings of psychological functioning in adolescence. As expected, Agreeableness and Conscientiousness were associated with measures of self-regulation at both ages as well as with an internal locus of control, but only Conscientiousness was associated with high academic performance. By contrast, Neuroticism was associated with measures of anxiety and Extraversion was associated with difficulty inhibiting behaviors at both ages. Openness to Experience was associated with sophisticated play behavior at 5 years and self-confidence in adolescence. Overall, this study yielded strong support for the predictive validity of the FFM with preschool age children and provided further evidence that there are striking continuities in personality from early childhood to adolescence. (c) 2004 Elsevier Inc. All rights reserved.
52 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/072-295-048-962-659 tex.type: [object Object]
Keywords: dept.psy; peer-reviewed

Use of visual information in speech perception: evidence for a visual rate effect both with and without a McGurk effect. - Brancazio, Lawrence; Miller, Joanne L (Perception & psychophysics, 2005)
The McGurk effect, where an incongruent visual syllable influences identification of an auditory syllable, does not always occur, suggesting that perceivers sometimes fail to use relevant visual phonetic information. We tested whether another visual phonetic effect, which involves the influence of visual speaking rate on perceived voicing (Green & Miller, 1985), would occur in instances when the McGurk effect does not. In Experiment 1, we established this visual rate effect using auditory and visual stimuli matching in place of articulation, finding a shift in the voicing boundary along an auditory voice-onset-time continuum with fast versus slow visual speech tokens. In Experiment 2, we used auditory and visual stimuli differing in place of articulation and found a shift in the voicing boundary due to visual rate when the McGurk effect occurred and, more critically, when it did not. The latter finding indicates that phonetically relevant visual information is used in speech perception even when the McGurk effect does not occur, suggesting that the incidence of the McGurk effect underestimates the extent of audio-visual integration.
28 citations (Crossref) [2023-10-31] Place: United States Brancazio, Lawrence. Department of Psychology, Southern Connecticut State University, 501 Crescent St., New Haven, CT 06515, USA. brancazioL1@southernct.edu
Keywords: *Speech Perception; *Visual Perception; Adolescent; Adult; Auditory Perception; Cues; Humans; Middle Aged; dept.psy

Effects of reinforcer probability, delay, and response requirements on the choices of rats and pigeons: Possible species differences - Mazur, James E (Journal of the Experimental Analysis of Behavior, 2005)
In Experiment 1 with rats, a left lever press led to a 5-s delay and then a possible reinforcer. A right lever press led to an adjusting delay and then a certain reinforcer. This delay was adjusted over trials to estimate an indifference point, or a delay at which the two alternatives were chosen about equally often. Indifference points increased as the probability of reinforcement for the left lever decreased. In some conditions with a 20% chance of food, a light above the left lever was lit during the 5-s delay on all trials, but in other conditions, the light was only lit on those trials that ended with food. Unlike previous results with pigeons, the presence or absence of the delay light on no-food trials had no effect on the rats' indifference points. In other conditions, the rats showed less preference for the 20% alternative when the time between trials was longer. In Experiment 2 with rats, fixed-interval schedules were used instead of simple delays, and the presence or absence of the fixed-interval requirement on no-food trials had no effect on the indifference points. In Experiment 3 with rats and Experiment 4 with pigeons, the animals chose between a fixed-ratio 8 schedule that led to food on 33% of the trials and an adjusting-ratio schedule with food on 100% of the trials. Surprisingly, the rats showed less preference for the 33% alternative in conditions in which the ratio requirement was omitted on no-food trials. For the pigeons, the presence or absence of the ratio requirement on no-food trials had little effect. The results suggest that there may be differences between rats and pigeons in how they respond in choice situations involving delayed and probabilistic reinforcers.
19 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/053-049-743-382-047 tex.type: [object Object]
Keywords: *Behavior; Animal/ph [Physiology]; *Choice Behavior; *Reaction Time; *Reinforcement; Psychology; Animals; Behavior; Animal; Choice; Choice Behavior; Columbidae; Delay; Fixed interval; Fixed ratio; Key peck; Lever press; Male; Pigeons; Probability; Rats; Rats; Sprague-Dawley; Reaction Time; Reinforcement (Psychology); Species Specificity; Sprague Dawley rat; animal; animal behavior; decision making; dept.psy; male; peer-reviewed; physiology; pigeons and doves; probability; rat; reaction time; reinforcement; review; species difference

Exploring a concurrent-chains paradox: decreasing preference as an initial link is shortened. - Mazur, James E (Journal of experimental psychology. Animal behavior processes, 2005)
Experiments with pigeons and rats on concurrent-chains schedules examined a paradoxical effect reported by R. A. Preston and E. Fantino (1991). One schedule in the concurrent chain had a variable-interval (VI) 60-s initial link, and its terminal link was a 10-s delay to food. The other schedule had an initial link that ranged from VI 60 s to VI 2 s, and its terminal link was a 20-s delay to food. The paradoxical effect–a decrease in preference for the 20-s delay as its initial link was shortened–was found in some conditions but not in others. An analysis of response-reinforcer delays suggested that the paradoxical effect occurred in conditions in which responding on the short VI schedule almost always led to the 20-s delay, eliminating the possibility of switching to the alternative with the shorter delay. Copyright 2005 APA.
1 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Psychology Department, Southern Connecticut State University, New Haven, CT 06515, USA. mazurj1@southernct.edu
Keywords: *Choice Behavior; *Motivation; *Reinforcement Schedule; Animals; Association Learning; Choice Behavior; Color Perception; Columba; Columbidae; Discrimination Learning; Models; Psychological; Motivation; Psychomotor Performance; Reaction Time; Reinforcement Schedule; animal; article; color vision; decision making; dept.psy; discrimination learning; learning; motivation; pigeons and doves; psychological model; psychomotor performance; reaction time; reinforcement

From Freud to Erikson to Marcia: Concept maps in personality psychology courses - Anthis, K (Teaching of Psychology, 2005)
This study examined concept maps produced by personality psychology students as a function of different types of concept map instruction. The results indicated the number of quantitative items in the students' concept maps significantly increased from the pretest to the posttest, as would be expected over the course of an academic semester. More importantly, the type of instructions the students received at the pretest played a significant role in the number of cross links depicted in the maps at the posttest. I discuss the results in term of the utility of instruction type when using concept maps in social science courses.
tex.unique-id: ISI:000232610800020
Keywords: dept.psy; ⛔ No DOI found

Heuristics and general principles of learning. - Mazur, James E (Behavioural Processes, 2005)
This research on decision-making heuristics is similar to research on animal learning in at least two ways. First, optimality modeling has not proven to be very useful for either research area. Second, both of these research areas seek to find general principles (or heuristics) that are applicable to different species in different settings. However, the basic principles of classical and operant conditioning seem to be more uniform across species and situations, whereas decision-making heuristics can vary for different species and different situations, even for tasks with very similar characteristics.
0 citations (Crossref) [2023-10-31] Place: Netherlands Mazur, James E. Psychology Department, Southern Connecticut State University, New Haven, CT 06515, USA. mazurj1@southernct.edu
Keywords: *Algorithms; *Decision Making; *Learning; *Models; Psychological; Animalia; Animals; Decision-making; Heuristics; Humans; Optimality modeling; behavioral research; conditioned reflex; conference paper; decision making; dept.psy; heuristics; human; instrumental conditioning; learning; mental task; nonhuman

Varying initial-link and terminal-link durations in concurrent-chains schedules: a comparison of three models. - Mazur, James E (Behavioural Processes, 2004)
In Experiment 1, pigeons responded on concurrent-chains schedules with equal variable-interval schedules as initial links and fixed delays to food as terminal links. One terminal-link delay was always three times as long as the other. As terminal-link delays increased, response percentages on the key with the shorter terminal link increased according to a curvilinear function. This result supported the predictions of the hyperbolic value-added model and the contextual-choice theory but not delay-reduction theory. In Experiment 2, the terminal links were always delays of 2 s and 12 s, followed by food, and the durations of the initial links varied across conditions. As initial-link durations increased, pigeons' response percentages on the key with the shorter terminal link decreased, but toward an asymptote greater than 50%, indicating a continued preference for the shorter terminal link with very long initial links. This result was more consistent with the predictions of the hyperbolic-value added model than with those of the contextual-choice model or of delay-reduction theory. (C) 2004 Elsevier B.V. All rights reserved.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/023-773-022-282-811 tex.type: [object Object]
Keywords: *Behavior; Animal; *Reinforcement; Psychology; Animals; Behavior; Animal; Columba; Columbidae; Concurrent-chains schedule; Initial links; Key peck; Pigeons; Reinforcement (Psychology); Terminal links; Time Factors; animal experiment; behavioral response; bird; conference paper; controlled study; decision making; dept.psy; experiment; food; intermethod comparison; model; modeling; nonhuman; pigeon; prediction; reinforcement; response time; temporal analysis; theory

Self-esteem, perception of relationships, and emotional distress: A cross-cultural study - Abe, Jo Ann A (Personal Relationships, 2004)
This study examined the relative importance of self-esteem, family cohesion, and support from friends in predicting depressed mood and anxiety in Japanese and American college students. Contrary to expectations, self-esteem was the strongest predictor of emotional distress in both groups of students. Nevertheless, consistent with predictions derived from Markus and Kitayama's theory of self-construals, family cohesion accounted for a significantly larger percentage of the variance in predicting emotional distress in Japan than in the United States. In both countries, the relations between support from friends and the measures of emotional distress were entirely mediated by self-esteem. However, among Japanese students, family cohesion accounted for additional significant variance in predicting the measures of emotional distress, even after controlling for self-esteem.
24 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-511-906-572-838 tex.type: [object Object]
Keywords: dept.psy

Lexical influences in audiovisual speech perception - Brancazio, Lawrence (Journal of Experimental Psychology: Human Perception and Performance, 2004)
Phoneme identification with audiovisually discrepant stimuli is influenced by information in the visual signal (the McGurk effect). Additionally, lexical status affects identification of auditorily presented phonemes. The present study tested for lexical influences on the McGurk effect. Participants identified phonemes in audiovisually discrepant stimuli in which lexical status of the auditory component and of a visually influenced percept was independently varied. Visually influenced (McGurk) responses were more frequent when they formed a word and when the auditory signal was a nonword (Experiment 1). Lexical effects were larger for slow than for fast responses (Experiment 2), as with auditory speech, and were replicated with stimuli matched on physical properties (Experiment 3). These results are consistent with models in which lexical processing of speech is modality independent.
39 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/108-054-092-602-383 tex.type: [object Object]
Keywords: *Lipreading; *Speech Perception; *Visual Perception; *Vocabulary; Adolescent; Adult; Female; Humans; Lipreading; Male; Phonetics; Reaction Time; Speech Perception; Visual Perception; Vocabulary; adolescent; adult; article; clinical trial; controlled clinical trial; controlled study; dept.psy; female; human; linguistics; lip reading; male; phonetics; randomized controlled trial; reaction time; speech perception; vision

Shame, guilt, and personality judgment - Abe, Jo Ann A (Journal of Research in Personality, 2004)
The purpose of this study was to shed further light on the intrapersonal and interpersonal correlates of shame- and guilt-proneness by examining their relations with self- and peer-ratings of the five-factor model (FFM) of personality. Shame- and guilt-proneness were assessed using a scenario-based and a checklist measure. Consistent with findings from previous research, the self-rating data yielded support for the view that shame-proneness may be associated with more maladaptive patterns than guilt-proneness. However, peer-ratings of personality failed to corroborate these findings. Both scenario-based and checklist measures of shame-proneness were associated with a tendency to underestimate one's Agreeableness relative to peer-ratings. Several possible interpretations of these findings are discussed in light of the extant research on personality judgment. (C) 2003 Elsevier Science (USA). All rights reserved.
43 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/028-498-536-772-541 tex.type: [object Object]
Keywords: dept.psy; peer-reviewed

Gender and identity status differences in late adolescents’ possible selves - Anthis, Kristine; Dunkel, Curt S; Anderson, Brian (Journal of Adolescence, 2004)
The current study examined gender and identity status differences in late adolescents' possible selves. The intent of the study was to clarify conflicts between theory and research on gender differences in identity by investigating the content of participants' possible selves. Participants completed measures of identity and possible selves. The results indicated that there was a relationship between gender and the mean number of both feared and balanced interpersonally themed possible selves. The pattern of results is discussed in terms of prior findings regarding gender differences in both identity and possible selves. Suggestions for future research are also provided. (C) 2003 The Association for Professionals in Services for Adolescents. Published by Elsevier Ltd. All rights reserved.
25 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/125-439-454-273-569 tex.type: [object Object]
Keywords: *Sex Factors; *Social Identification; Adolescent; Adult; Female; Humans; Male; Surveys and Questionnaires; United States; adolescent; adult; article; child behavior; controlled study; coping behavior; dept.psy; ego identity; ethnology; fear; female; gender identity; human; male; personality; race difference; sex difference; social status

A new psychology of women: Gender, culture, and ethnicity, 2(nd) edition. - Anthis, K (Psychology of Women Quarterly, 2004)
tex.unique-id: ISI:000220478200011
Keywords: dept.psy; ⚠️ Invalid DOI

The phenomenological experience of global women's issues - Anthis, Kristine (Psychology of Women Quarterly, 2004)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/048-591-446-805-700 tex.type: [object Object]
Keywords: dept.psy

Developmental changes in facial expressions of emotions in the strange situation during the second year of life - Izard, Carroll E; Abe, Jo Ann A (Emotion, 2004)
Infants' expressions of discrete emotions were coded during the more stressful episodes (4 through 8) of the Strange Situation at 13 and 18 months. The data showed a significant decrease in full-face expressions (more complex configurations of movements) and a significant increase in component expressions (simpler and more constrained patterns of movements). The authors interpreted this trend as a developmental change toward more regulated and less intense emotions. Consistent with this view, the aggregate index of infants' full-face negative emotion expressions, interpreted as reflecting relatively unregulated intense emotions, correlated significantly with maternal ratings of difficult temperament. The authors discuss alternative interpretations of the findings in terms of changes in reactivity/arousability and the emerging capacity for self-regulation.
25 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/010-936-730-858-844 tex.type: [object Object]
Keywords: Adult; Affect; Arousal; Facial Expression; Female; Humans; Infant; Social Control; Informal; Temperament; adult; anger; arousal; article; body movement; body posture; child behavior; child development; child parent relation; dept.psy; emotion; face; facial expression; happiness; human; infant; longitudinal study; mother child relation; rating scale; temperament

Therapist variables that predict symptom change in psychotherapy with chronically depressed outpatients. - Vocisano, Carina; Klein, Daniel N; Arnow, Bruce A; Rivera, Caridad; Blalock, Janice A; Rothbaum, Barbara O; Vivian, Dina; Markowitz, John C; Kocsis, James H; Manber, Rachel; Castonguay, Louis G; Rush, A John; et al. (Psychotherapy, 2004)
The present study examines the contribution of psychotherapist variables to change in depressive symptoms in a large clinical trial comparing the efficacy of the cognitive-behavioral analysis system of psychotherapy, the antidepressant nefazodone, and the combination of both in the treatment of chronic depression. Greater change on the Hamilton Rating Scale for Depression (HRSD) was associated with greater emphasis on the therapeutic relationship, lower overall psychotherapy caseload, therapist psychodynamic orientation, and supervisory status. There was no relationship between HRSD change and therapist sex, age, or years of experience.
35 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/104-228-113-585-108 tex.type: [object Object]
Keywords: Hamilton scale; adult; age; article; behavior therapy; clinical practice; clinical trial; cognitive therapy; controlled clinical trial; controlled study; depression; dept.psy; doctor patient relation; drug efficacy; female; gender; human; major clinical study; male; multicenter study; nefazodone; normal human; outpatient; patient care; patient guidance; physician attitude; prediction; psychodynamics; psychopharmacotherapy; psychotherapist; psychotherapy; randomized controlled trial; symptomatology; workload

Book Review: midlife and aging in gay america. d. c. kimmel & d. l. martin, harrington park press, binghamton, NY; 2001. 116 pp. 19.95 - Anthis, Kristine (Sex Roles, 2003)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/070-736-980-435-799 tex.type: [object Object]
Keywords: book.review; dept.psy

Visual influences on the internal structure of phonetic categories - Brancazio, L; Miller, JL; Pare, MA (Perception & Psychophysics, 2003)
Previous work has demonstrated that the graded internal structure of phonetic categories is sensitive to a variety of contextual factors. One such factor is place of articulation: The best exemplars of voiceless stop consonants along auditory bilabial and velar voice onset time (VOT) continua occur over different ranges of VOT! (Volaitis & Miller, 1992). In the present study, we exploited the McGurk effect to examine whether-visual information for place of articulation also shifts the best-exemplar range for voiceless consonants, following Green and Kuhl's (1989) demonstration of effects of visual place of articulation on the location of voicing boundaries. In Experiment 1, we established that /p/ and /t/ have different best-exemplar ranges along auditory bilabial and alveolar VOT continua. We then found, in Experiment 2, a-similar shift in the best-exemplar range for /t/ relative to that for /p/ when there was a change in visual place of articulation, with auditory place of articulation held constant. These findings indicate-that the perceptual mechanisms that determine internal phonetic category structure-are sensitive to visual, as well as to Auditory, information.
12 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000183134600008
Keywords: Adolescent; Adult; Female; Humans; Male; Middle Aged; Phonetics; Random Allocation; Speech Perception; Time Factors; Visual Perception; Voice; adolescent; adult; article; dept.psy; female; human; male; middle aged; phonetics; randomization; speech perception; time; vision; voice

Effects of free-food deliveries and delays on choice under concurrent-chains schedules. - Mazur, James E (Behavioural Processes, 2003)
Pigeons responded on a concurrent-chains schedule with two equal variable-interval (VI) schedules as initial links and delays to food of 3 and 12 s as the two terminal links. In even-numbered sessions, no other reinforcement schedule was present, and all pigeons showed a strong preference for the response key that had the shorter, 3-s terminal-link delay. In odd-numbered sessions, the initial links were interrupted at random times by one of three different types of events. When the interruptions were immediate food deliveries, the response percentages increased on the key that had the 3-s delay. When the interruptions were 30-s delays followed by food, the response percentages remained approximately unchanged. When the interruptions were 30-s delays with no food, the response percentages decreased. The results were used to compare the predictions of different mathematical models of concurrent-chains performance. The results favored models that assume that preference is determined by the relative amount of advantage that is gained when a terminal link is entered. (C) 2003 Elsevier B.V. All rights reserved.
3 citations (Crossref) [2023-10-31] Place: Netherlands Mazur, James E.. Psychology Department, Southern Connecticut State University, 06515, New Haven, CT, USA
Keywords: Choice; Columba; Concurrent chains; Free food; Key peck; Pigeons; Reinforcer delay; animal behavior; animal experiment; article; controlled study; decision making; dept.psy; food; food deprivation; mathematical model; nonhuman; pigeon; prediction; preference behavior; reinforcement; stimulus response

The role of sexist discrimination in adult women's identity development - Anthis, Kristine (Sex Roles, 2002)
The purpose of the current study was to examine the relationship between sexist discrimination and identity development in a sample of adult women. Participants completed a scale to indicate the extent to which sexist events had occurred in their lives and a measure of identity at 2 different data collection periods that spanned approximately 5 months. The results indicated that sexist events reported to occur within the last year at the first data collection period significantly predicted identity scores at the second data collection period. These findings are discussed in terms of how sexist discrimination may play a role in adult women's identity development and in terms of the additional psychometric data that supports the validity of the measure of sexist discrimination.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-138-574-547-367 tex.type: [object Object]
Keywords: dept.psy; identity; sexist discrimination; women

Winning friends and influencing peers: Strategies of peer influence in late childhood - Hawley, Patricia H; Little, Todd D; Pasupathi, Monisha (International Journal of Behavioral Development, 2002)
We divided children (N = 719, grades 3-6) into five control types based on the degree to which they reported employing prosocial (indirect, cooperative) and coercive (direct, hostile) strategies of control (prosocial controllers, coercive controllers, bistrategic controllers, noncontrollers, and typicals). We tested for differences across the five types on personal characteristics, friendship motivations, wellbeing, and social integration, expecting specific patterns according to whether control is wielded, and whether coercive or prosocial behaviour (or both) is employed. Prosocial controllers revealed positive characteristics (e. g., social skills, agreeableness), intrinsic friendship motivations, and positive wellbeing. In contrast, coercive controllers revealed negative characteristics (e. g., hostility), extrinsic friendship motivations, and ill-being. Bistrategic controllers, as expected, reported the highest control, and revealed characteristics associated with both prosocial and coercive orientations. Noncontrollers, in contrast, did not report having these characteristics and felt the least effective in the peer group. Our evolutionary perspective offers unique predictions of how prosocial and coercive children are similar in terms of their instrumental goals and the consequences of using both strategies or neither.
107 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-731-986-341-419 tex.type: [object Object]
Keywords: childhood; controlled study; cooperation; dept.psy; female; hostility; human; male; motivation; perception; personality test; persuasive communication; prediction; review; school child; social adaptation; social control; social interaction; sociology; wellbeing

George perkins marsh: prophet of conservation. - Martin, GJ (Professional Geographer, 2002)
tex.unique-id: ISI:000175693000022
Keywords: dept.psy; ⛔ No DOI found

Evidence against a constant-difference effect in concurrent-chains schedules - Mazur, James E (Journal of the Experimental Analysis of Behavior, 2002)
Savastano and Fantino (1996) reported that in concurrent-chains schedules, initial-link choice proportions remained constant as terminal-link durations increased as long as the subtractive difference between the two terminal-link schedules remained constant. Two experiments with pigeons were conducted to examine this constant-difference effect. Both experiments used equal variable-interval schedules as initial links. The terminal links were fixed delays to reinforcement in Experiment 1 and variable delays to reinforcement in Experiment 2. The durations of the terminal links were varied across conditions, but the difference between pairs of terminal links was always 10 s. In both experiments, preference for the shorter terminal link became less extreme as terminal-link, durations increased, so a constant-difference effect was not found, It is argued, however, that this choice situation does not provide clear evidence for or against delay-reduction theory versus other theories of choice.
3 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Psychology Department, Southern Connecticut State University, New Heaven 06515, USA. mazur@southernct.edu
Keywords: *Choice Behavior; *Motivation; *Reinforcement Schedule; Animals; Appetitive Behavior; Choice Behavior; Color Perception; Columbidae; Concurrent-chains schedules; Delay-reduction theory; Fixed delays; Key peck; Mental Recall; Motivation; Pigeons; Reinforcement Schedule; Variable delays; animal; appetite; article; color vision; comparative study; decision making; dept.psy; motivation; peer-reviewed; pigeons and doves; recall; reinforcement

Learning and behavior, 5th ed. - Mazur, James E. (2002)
Keywords: dept.psy

On the calamity theory of growth: the relationship between stressful life events and changes in identity over time - Anthis, Kristine (Identity, 2002)
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/106-281-414-377-746 tex.type: [object Object]
Keywords: dept.psy

Social dominance and prosocial and coercive strategies of resource control in preschoolers - Hawley, P.H. (International Journal of Behavioral Development, 2002)
This study was designed to investigate the predictors of social dominance, the strategies children use to control resources (prosocial and coercive), and the associations between these strategies and measures of personality, social skills, and peer regard. A total of 30 preschoolers (ages 3-6) were rated by their teachers on social dominance. Based on these ratings, dominant children were paired with multiple subordinate children (i.e., block design; Kenny, 1990) and observed in a play situation designed to elicit resource control behaviour. As hypothesised, age and the surgency facet of extraversion predicted social dominance (but openness to experience did not). Furthermore, also as expected, both prosocial behaviour and coercive behaviour were related to resource control in the play situation. Last, both resource control strategies were associated with parent-rated social competence, but only coercive control was associated with positive peer regard (i.e., Likeability). Factors of personality (e.g. agreeableness, hostility) were not associated with either of the strategies. The utility of an evolutionary perspective to resource control and social competence is discussed.
153 citations (Crossref) [2023-10-31]
Keywords: article; controlled study; dept.psy; female; group psychology; hostility; human; hypothesis; male; parent; personality; persuasive communication; play; prediction; preschool child; social adaptation; social behavior; social dominance; sociology; teacher

Concurrent-chain performance in transition: effects of terminal-link duration and individual reinforcers. - Mazur, James E (Animal learning & behavior, 2002)
Pigeons responded on concurrent-chain schedules with variable-interval initial links and equal delays as terminal links. The terminal-link delays were 1 sec in some conditions and 20 sec in other conditions. The percentages of reinforcers delivered for responses on the left key were 10%, 30%, 70%, or 90%, and this percentage was switched every five to nine sessions. The rate of change in the pigeons' response percentages after a switch was the same whether the terminal-link delays were 1 sec or 20 sec. Analysis of the effects of individual reinforcers showed that after a response on one key had been reinforced, response percentages on that key were higher for at least the next 100 responses. Small effects of individual reinforcers were evident after eight or nine additional reinforcers had been delivered. The effects of individual reinforcers were about equally large during times of transition and during periods in which overall response percentages were relatively stable.
6 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Psychology Department, Southern Connecticut State University, New Haven, CT 06515, USA. mazur@southernct.edu
Keywords: *Behavior; Animal; *Reinforcement; Psychology; Animalia; Animals; Columba; Columbidae; Random Allocation; Reaction Time; Reinforcement Schedule; animal experiment; article; conditioned reflex; conditioning; decision making; dept.psy; nonhuman; pigeon; reinforcement; task performance

Transitional choice behavior in concurrent-chain schedules - Mazur, James E; Blake, Nancy; Mcmanus, Courtney (Behavioural Processes, 2001)
The choice responses of four pigeons were examined in 20 periods of transition in a concurrent-chain procedure with variable-interval schedules as initial links and fixed delays to reinforcement as terminal links. In some conditions, the delays to reinforcement were different for the two terminal links, and changes in preference were recorded after the delays for the two response keys were switched. In other conditions, the reinforcer delays were equal for the two keys, but which key delivered 80% of the reinforcers was periodically switched. Choice proportions changed more quickly after a switch in reinforcement percentages chan after a switch in the delays, thereby contradicting the hypothesis that faster changes would occur when the switch in conditions was easier to discriminate. Analyses of response sequences showed that the effects: of individual reinforcers were larger and lasted longer in conditions with changing reinforcement percentages than in conditions with changing terminal-link delays. Rates of change in choice behavior do not appear to be limited by the unpredictability of variable reinforcement schedules, because the changes in behavior were slow and gradual even when there was a large and sudden change in reinforcer delays. (C) 2001 Elsevier Science B.V. All rights: reserved.
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-721-068-778-123 tex.type: [object Object]
Keywords: Columba; Concurrent-chain schedules; Transitional choice behavior; animal experiment; article; behavior; controlled study; decision making; dept.psy; instrumental conditioning; nonhuman; pigeon; reinforcement; stimulus response

Hyperbolic value addition and general models of animal choice - Mazur, James E. (Psychological Review, 2001)
Three mathematical models of choice-the contextual-choice model (R. Grace, 1994), delay-reduction theory (N. Squires & E. Fantino, 1971). and a new model called the hyperbolic value-added model-were compared in their ability to predict the results from a wide variety of experiments with animal subjects. When supplied with 2 or 3 free parameters, all 3 models made fairly accurate predictions for a large set of experiments that used concurrent-chain procedures. One advantage of the hyperbolic value-added model is that it is derived from a simpler model that makes accurate predictions for many experiments using discrete-trial adjusting-delay procedures. Some results favor the hyperbolic value-added model and delay-reduction theory over the contextual-choice model, but more data are needed from choice situations For which the models make distinctly different predictions.
Place: United States Mazur, J E. Department of Psychology, Southern Connecticut State University, New Haven, Connecticut 06515, USA. mazur@southernct.edu
Keywords: *Behavior; Animal; *Choice Behavior; *Models; Psychological; Animals; Behavior; Animal; Choice Behavior; Columbidae; Conditioning (Psychology); Conditioning; Psychological; Models; Psychological; Reinforcement (Psychology); Reinforcement Schedule; Reinforcement; Psychology; animal; animal behavior; comparative study; conditioning; decision making; dept.psy; pigeons and doves; psychological model; reinforcement; review; ⚠️ Invalid DOI

Two- versus three-alternative concurrent-chain schedules: a test of three models. - Mazur, James E (Journal of Experimental Psychology: Animal Behavior Processes, 2000)
Two experiments with pigeons used concurrent-chain procedures with variable-interval schedules as initial links and different delays to food as terminal links. Two schedules were present in all sessions. but a 3rd schedule was alternately present and absent in successive sessions. When the 3rd schedule delivered food with no terminal-link delay, the presence of this schedule led to an increase in preference for the schedule with the shorter terminal link of the 2 unchanged schedules. When the terminal-link delay for the 3rd schedule was 30 s, the presence of this schedule led to a decrease in preference for the schedule with the shorter terminal link of the 2 unchanged schedules. These results are inconsistent with the predictions of R. Grace's (1994) contextual-choice model, but they are consistent with 2 other mathematical models-delay-reduction theory and the hyperbolic value-added model.
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/030-282-629-182-734 tex.type: [object Object]
Keywords: *Choice Behavior; *Columbidae; *Conditioning; Operant; Analysis of Variance; Animals; Choice Behavior; Columbidae; Conditioning; Operant; Models; Psychological; analysis of variance; animal; article; decision making; dept.psy; instrumental conditioning; pigeons and doves; psychological model

Tradeoffs among delay, rate, and amount of reinforcement - Mazur, James E (Behavioural Processes, 2000)
In Experiment I, an adjusting-delay procedure was used to measure pigeons' choices between a single delayed reinforcer and a range of different variable-time schedules. Indifference points showed an inverse relation between rate of reinforcement and delay that was well described by a hyperbolic equation. An adjusting-amount procedure was used in Experiment 2, in which pigeons chose between an adjusting amount of food delivered after a 0.5-s delay and 3 s of food delivered after a range of different delays, and the effects of delay were similar to those found in Experiment 1. The results from both experiments indicated that, for pigeons, the strength of a reinforcer decreased rapidly with increasing delay. Estimates of a decay rate parameter in the hyperbolic equation were similar to those found in other studies with pigeons, but the rates of temporal discounting were three or four times faster than those found in studies with rats, suggesting a possible species difference. (C) 2000 Published by Elsevier Science B.V. All rights reserved.
64 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/026-033-972-981-013 tex.type: [object Object]
Keywords: Adjusting procedure; Amount of reinforcement; Delay; Discounting; Key peck; Pigeons; Rate of reinforcement; animal experiment; article; behavior; controlled study; dept.psy; dose time effect relation; nonhuman; pigeon; reinforcement; technique; variance

Contextual choice and other models of preference - Mazur, JE (Behavioral and Brain Sciences, 2000)
Grace's contextual-choice model can account for the results from many studies on choice under concurrent-chain schedules. However, other models, including one that I call the “hyperbolic value-added model” can also account for these results. Preference and resistance to change may indeed be related, but the best model of preference remains to be determined.
0 citations (Crossref) [2023-10-31] tex.researcherid-numbers: Mazur, James/AAA-6971-2019 tex.unique-id: ISI:000088647900058
Keywords: dept.psy

Early and chronic stress and their relation to breast cancer - Jacobs, John R; Bovasso, Gregory B (Psychological Medicine, 2000)
Background. The study examined the role of parental death and chronic depression with severe episodes in affecting risk of breast cancer. This avenue of research is in accord with oncology findings, which suggests that causative factors of breast cancer occur and develop over a period of 20 years or longer. Methods. Participants consisted of 1213 women in the Baltimore Epidemiologic Catchment Area study surveyed in 1980 and followed through 1994-1995. They were assessed for depressive and anxious disorders, paternal death in childhood and relatively recent adverse life events prior to cancer hospitalization. Results. In the course of the study, 29 women were hospitalized for breast cancer and 10 died of breast cancer. The psychosocial variables that predicted increased risk of breast cancer were maternal death in childhood (OR = 2.56, P ¡ 0.001) and chronic depression with severe episodes (OR = 14.0, P ¡ 0.001). Neither relatively recent life events nor other depressive and anxiety disorders were associated with increased risk. Maternal death and chronic depression with severe episodes were reported to have occurred at least 20 years prior to breast cancer hospitalization. Conclusions. Maternal death and chronic and severe depression occurred at least 20 years prior to breast cancer hospitalization and could have been involved in the causation or facilitation of cancer development. The authors suggest that meta-analysis of other prospective studies are needed to create larger groups of individuals with these stresses to confidently establish these variables as risk factors.
83 citations (Crossref) [2023-10-31] Place: England Jacobs, J R. Department of Psychology, Southern Connecticut State University, New Haven 06515, USA. Comment in (CIN)
Keywords: *Breast Neoplasms/et [Etiology]; *Death; *Depressive Disorder/co [Complications]; *Stress; Psychological; Adult; Breast Neoplasms; Breast Neoplasms/px [Psychology]; Death; Depressive Disorder; Epidemiologic Studies; Female; Humans; Life Change Events; Middle Aged; Mother-Child Relations; Risk Factors; Stress; Psychological; adult; anxiety neurosis; article; breast cancer; cancer risk; depression; dept.psy; female; health survey; hospitalization; human; life event; major clinical study; medical psychology; mental stress; parental deprivation

Visual influences on perception of speech and nonspeech vocal-tract events. - Brancazio, Lawrence; Best, Catherine T; Fowler, Carol A (Language and speech, 2006)
We report four experiments designed to determine whether visual information affects judgments of acoustically-specified nonspeech events as well as speech events (the "McGurk effect"). Previous findings have shown only weak McGurk effects for nonspeech stimuli, whereas strong effects are found for consonants. We used click sounds that serve as consonants in some African languages, but that are perceived as nonspeech by American English listeners. We found a significant McGurk effect for clicks presented in isolation that was much smaller than that found for stop-consonant-vowel syllables. In subsequent experiments, we found strong McGurk effects, comparable to those found for English syllables, for click-vowel syllables, and weak effects, comparable to those found for isolated clicks, for excised release bursts of stop consonants presented in isolation. We interpret these findings as evidence that the potential contributions of speech-specific processes on the McGurk effect are limited, and discuss the results in relation to current explanations for the McGurk effect.
7 citations (Crossref) [2023-10-31] Place: England Brancazio, Lawrence. Department of Psychology, Southern Connecticut State University, New Haven 06515, USA. brancazioL1@southernct.edu
Keywords: *Illusions; *Speech Perception/ph [Physiology]; *Visual Perception/ph [Physiology]; Acoustic Stimulation; Attention; Audiovisual speech perception; Clicks; Humans; McGurk effect; Nonspeech; Perceptual Masking; Psychoacoustics; Speech Acoustics; dept.psy

Words that predict outstanding performance - Abe, Jo Ann A. (Journal of Research in Personality, 2009)
This study applied word count strategies developed by expressive writing researchers to examine whether the words students use to describe and reflect on their field practicum experiences would predict practicum supervisors' ratings of their performance. The weekly journals of 66 students who completed a practicum at a mental health or school setting were analyzed using a computerized text-analysis program. As expected, positive emotion words and "insight" words were positively correlated with almost all dimensions of evaluation, with the exception of organizational ability, and "we" words were associated with dimensions that focused on interpersonal relations. These findings further support the view that positive emotion words and "insight" words are powerful markers of cognitive broadening and behavioral flexibility and that "we" words index feelings of affiliation and belonging. As one might expect, there was an increase in "we" words and a decrease in "anxiety" words over the course of the internship. © 2009 Elsevier Inc. All rights reserved.
16 citations (Crossref) [2023-10-31] Citation Key Alias: pop00125 tex.type: [object Object]
Keywords: Experiential learning; Positive emotions; Reflection; Text-analysis; dept.psy; peer-reviewed

Delay-amount tradeoffs in choices by pigeons and rats: hyperbolic versus exponential discounting. - Mazur, James E; Biondi, Dawn R (Journal of the Experimental Analysis of Behavior, 2009)
An adjusting-delay procedure was used to study the choices of pigeons and rats when both delay and amount of reinforcement were varied. In different conditions, the choice alternatives included one versus two reinforcers, one versus three reinforcers, and three versus two reinforcers. The delay to one alternative (the standard alternative) was kept constant in a condition, and the delay to the other (the adjusting alternative) was increased or decreased many times a session so as to estimate an indifference point–a delay at which the two alternatives were chosen about equally often. Indifference functions were constructed by plotting the adjusting delay as a function of the standard delay for each pair of reinforcer amounts. The experiments were designed to test the prediction of a hyperbolic decay equation that the slopes of the indifference functions should increase as the ratio of the two reinforcer amounts increased. Consistent with the hyperbolic equation, the slopes of the indifference functions depended on the ratios of the two reinforcer amounts for both pigeons and rats. These results were not compatible with an exponential decay equation, which predicts slopes of 1 regardless of the reinforcer amounts. Combined with other data, these findings provide further evidence that delay discounting is well described by a hyperbolic equation for both species, but not by an exponential equation. Quantitative differences in the y-intercepts of the indifference functions from the two species suggested that the rate at which reinforcer strength decreases with increasing delay may be four or five times slower for rats than for pigeons.
71 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Department, Southern Connecticut State University, New Haven, CT 06515, USA. mazurj1@southernct.edu
Keywords: *Choice Behavior; *Reinforcement Schedule; Animals; Choice Behavior; Columbidae; Conditioning; Operant; Long Evans rat; Male; Models; Psychological; Rats; Rats; Long-Evans; Reinforcement Schedule; Reward; animal; article; decision making; dept.psy; instrumental conditioning; male; peer-reviewed; pigeons and doves; psychological model; rat; reinforcement; reward

Re-examining the long-term effects of experiencing parental death in childhood on adult psychopathology. - Jacobs, John R; Bovasso, Gregory B (Journal of Nervous and Mental Disease, 2009)
This study examined whether the experience of the death of a parent in childhood increases risk for adult psychopathology. Participants consisted of 3481 men and women gathered through the Baltimore Epidemiologic Catchment Area study in 1981 and followed through 1994-1995. The Diagnostic Interview Survey was administered by trained interviewers and was used to assess DSM-III disorders including major depression, panic, and anxiety disorders. Maternal death was not a predictor of adult psychopathology. The death of the father during childhood more than doubled the risk for major depressive disorder in adulthood. This study did not find any significant interactions between gender of the deceased parent and gender of the participant nor did the current age of the participant or their age at the time of the death of a parent affect risk for adult psychopathology. The long-term effect on adult depression of the experience of the death of the father in childhood is attributed to likely financial stresses, which may have continued for years and possibly into early adulthood, complicating the family's adaptation to the initial loss.
34 citations (Crossref) [2023-10-31] Place: United States Jacobs, John R. Department of Psychology, Southern Connecticut State University, New Haven, Connecticut, USA. jacobsj1@southernct.edu
Keywords: *Bereavement; *Death; *Mental Disorders/et [Etiology]; *Mental Disorders/px [Psychology]; *Parents; *Psychology; Child; Anxiety Disorders; Anxiety Disorders/di [Diagnosis]; Anxiety Disorders/et [Etiology]; Anxiety Disorders/px [Psychology]; Bereavement; Child Psychology; Death; Depression; Depressive Disorder; Major; Depressive Disorder; Major/di [Diagnosis]; Depressive Disorder; Major/ep [Epidemiology]; Depressive Disorder; Major/et [Etiology]; Depressive Disorder; Major/px [Psychology]; Diagnostic and Statistical Manual of Mental Disorders; Economics; Fathers; Female; Humans; Incidence; Male; Mental Disorders; Middle Aged; Mothers; Panic; Parental death; Parents; Prevalence; Risk Factors; Stress; Psychological; Stress; Psychological/et [Etiology]; Time Factors; adaptive behavior; adult; adulthood; anxiety disorder; article; bereavement; child psychology; childhood; death; depression; dept.psy; diagnostic and statistical manual of mental disorders; economics; family stress; father; female; gender; human; incidence; interview; major depression; male; maternal mortality; mental disease; mental stress; middle aged; mother; normal human; panic; parent; parental deprivation; personal experience; prevalence; psychological aspect; risk factor; time; time of death

Training in assessment criteria indicative of deception to improve credibility judgments - Colwell, Kevin; Hiscock-Anisman, Cheryl; Memon, Amina; Colwell, Lori H.; Taylor, Laura; Woods, Debra (Journal of Forensic Psychology Practice, 2009)
The recent attention given to false confessions and convictions underscores the need for a valid and applicable system of credibility assessment. The current study demonstrates the effectiveness of assessment criteria indicative of deception (ACID) training in increasing rater's ability to discriminate between honest and deceptive transcripts. ACID generates credibility assessment through analysis of behaviors related to memory and impression-management as they occur during the course of an investigative interview. Raters were taught that honest responses are longer, more vivid, and more spontaneous than deceptive responses. Conversely, deceptive responses are shorter, less vivid, more rigid, more carefully phrased, and less likely to change during the course of an investigative interview. Trained raters were able to correctly identify 77% of transcripts as honest or deceptive, whereas untrained raters correctly identified 57%. Future research should focus on using the ACID technique in more realistic situations and should involve training of professional investigators.
19 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/078-923-743-395-732 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Credibility; Detecting deception; Investigative interviewing; accuracy; analytic method; article; assessment criteria indicative of deception; behavioral research; controlled study; criminal justice; decision making; dept.psy; honesty; human; interview; self evaluation; training

Does choice of college textbook make a difference in students' comprehension? - Durwin, Cheryl Cisero; Sherman, William M (College Teaching, 2008)
The authors investigate whether the choice of college textbook affects students' comprehension of the material. Forty-eight students from educational psychology courses were randomly assigned to one of two conditions: (1) unfamiliar passages drawn from the textbook used in the course, or (2) comparable passages selected from a competitor textbook. Students read three passages and completed comprehension tests and an opinion survey. No significant differences were found. Implications for textbook selection practices are presented in the discussion section. © 2008, Copyright Taylor & Francis Group, LLC.
18 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/018-371-825-356-615 tex.type: [object Object]
Keywords: comprehension; dept.psy; student preferences; textbook selection

Effects of reinforcer delay and variability in a successive-encounters procedure. - Mazur, James E (Learning & behavior, 2008)
Pigeons responded in a successive-encounters procedure that consisted of a search period, a choice period, and a handling period. The search period was either a fixed-interval or a mixed-interval schedule presented on the center key of a three-key chamber. Upon completion of the search period, the center key was turned off and the two side keys were lit. A pigeon could either accept a delay followed by food (by pecking the right key) or reject this option and return to the search period (by pecking the left key). During the choice period, a red right key represented the long alternative (a long handling delay followed by food), and a green right key represented the short alternative (a short handling delay followed by food). The experiment consisted of a series of comparisons for which optimal diet theory predicted no changes in preference for the long alternative (because the overall rates of reinforcement were unchanged), whereas the hyperbolic-decay model predicted changes in preference (because the delays to the next possible reinforcer were varied). In all comparisons, the results supported the predictions of the hyperbolic-decay model, which states that the value of a reinforcer is inversely related to the delay between a choice response and reinforcer delivery.
1 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Psychology Department, Southern Connecticut State University, New Haven, CT 06515, USA. mazurj1@southernct.edu
Keywords: *Choice Behavior; *Reinforcement; Psychology; Animals; Behavior; Animal; Choice Behavior; Columbidae; Male; Reinforcement (Psychology); Time Factors; animal; animal behavior; animal experiment; article; conditioning; controlled study; decision making; dept.psy; food; male; nonhuman; pigeon; pigeons and doves; psychological theory; reinforcement; time

Rats’ choices between one and two delayed reinforcers - Mazur, James E (Learning & Behavior, 2007)
Rats chose between alternatives that differed in the number of reinforcers and in the delay to each reinforcer. A left leverpress led to two reinforcers, each delivered after a fixed delay. A right leverpress led to one reinforcer after an adjusting delay. The adjusting delay was increased or decreased many times in a session, depending on the rat's choices, in order to estimate an indifference point-a delay at which the two alternatives were chosen about equally often. Both the number of reinforcers and their individual delays affected the indifference points. The overall pattern of results was well described by the hyperbolic-decay model, which states that each additional reinforcer delivered by an alternative increases preference for that alternative but that a reinforcer's effect is inversely related to its delay. Two other possible delay-discounting equations, an exponential equation and a reciprocal equation, did not produce satisfactory predictions for these data. Adding an additional free parameter to the hyperbolic equation as an exponent for delay did not appreciably improve the predictions, suggesting that raising delay to some power other than 1.0 was unnecessary. The results were qualitatively similar to those from a previous experiment with pigeons (Mazur, 1986), but quantitative differences suggested that the rates of delay discounting were several times slower for rats than for pigeons.
24 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/057-943-120-320-01X tex.type: [object Object]
Keywords: *Choice Behavior; *Conditioning; Operant; *Motivation; *Reinforcement Schedule; *Time Perception; Animals; Male; Models; Theoretical; Rats; Rats; Sprague-Dawley; animal behavior; animal experiment; article; conditioning; dept.psy; hyperbolic decay model; mathematical model; nonhuman; pigeon; predictive validity; rat; reinforcement

Species differences between rats and pigeons in choices with probabilistic and delayed reinforcers - Mazur, James E. (Behavioural Processes, 2007)
An adjusting-delay procedure was used to study rats' choices with probabilistic and delayed reinforcers, and to compare them with previous results from pigeons. A left lever press led to a 5-s delay signaled by a light and a tone, followed by a food pellet on 50% of the trials. A right lever press led to an adjusting delay signaled by a light followed by a food pellet on 100% of the trials. In some conditions, the light and tone for the probabilistic reinforcer were present only on trials that delivered food. In other conditions, the light and tone were present on all trials that the left lever was chosen. Similar studies with pigeons [Mazur, J.E., 1989. Theories of probabilistic reinforcement. J. Exp. Anal. Behav. 51, 87-99; Mazur, J.E., 1991. Conditioned reinforcement and choice with delayed and uncertain primary reinforcers. J. Exp. Anal. Behav. 63, 139-150] found that choice of the probabilistic reinforcer increased dramatically when the delay-interval stimuli were omitted on no-food trials, but this study found no such effect with the rats. In other conditions, the probability of food was varied, and comparisons to previous studies with pigeons indicated that rats showed greater sensitivity to decreasing reinforcer probabilities. The results support the hypothesis that rats' choices in these situations depend on the total time between a choice response and a reinforcer, whereas pigeons' choices are strongly influenced by the presence of delay-interval stimuli. (c) 2007 Elsevier B.V. All rights reserved.
23 citations (Crossref) [2023-10-31] Meeting of the Society-for-the-Quantitative-Analyses-of-Behavior (SQAB 2006), Atlanta, GA, MAY 26-27, 2006 Citation Key Alias: lens.org/092-975-244-015-987 tex.organization: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: *Association Learning/ph [Physiology]; *Choice Behavior/ph [Physiology]; *Probability Learning; *Reinforcement; Psychology; *Time Perception/ph [Physiology]; Animals; Columba; Columbidae; Delay-interval stimuli; Delayed reinforcers; Probabilistic reinforcers; Rats; Rats; Sprague-Dawley; Rattus; Species Specificity; Time Factors; animal experiment; article; behavioral response; controlled study; decision making; dept.psy; food; food intake; gamebird; nonhuman; probability; rat; reinforcement; rodent; species difference; stimulus

Assessment Criteria Indicative of Deception (ACID): an integrated system of investigative interviewing and detecting deception - Colwell, Kevin; Hiscock-Anisman, Cheryl; Memon, Amina; Taylor, Laura; Prewett, Jessica (Journal of Investigative Psychology and Offender Profiling, 2007)
65 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/085-187-314-903-015 tex.type: [object Object]
Keywords: dept.psy; peer-reviewed

Choice in a successive-encounters procedure and hyperbolic decay of reinforcement. - Mazur, James E (Journal of the experimental analysis of behavior, 2007)
Pigeons responded in a successive-encounters procedure that consisted of a search state, a choice state, and a handling state. The search state was either a fixed-interval or mixed-interval schedule presented on the center key of a three-key chamber. Upon completion of the search state, the choice state was presented, in which the center key was off and the two side keys were lit. A pigeon could either accept a delay followed by food (by pecking the right key) or reject this option and return to the search state (by pecking the left key). During the choice state, a red right key represented the long alternative (a long handling delay followed by food), and a green right key represented the short alternative (a short handling delay followed by food). In some conditions, both the short and long alternatives were fixed-time schedules, and in other conditions both were mixed-time schedules. Contrary to the predictions of both optimal foraging theory and delay-reduction theory, the percentage of trials on which pigeons accepted the long alternative depended on whether the search and handling schedules were fixed or mixed. They were more likely to accept the long alternative when the search states were fixed-interval rather than mixed-interval schedules, and more likely to reject the long alternative when the handling states were fixed-time rather than mixed-time schedules. This pattern of results was in qualitative agreement with the predictions of the hyperbolic-decay model, which states that the value of a reinforcer is inversely related to the delay between a choice response and reinforcer delivery.
6 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Southern Connecticut State University, Psychology Department, New Haven 06515, USA. mazurj1@southernct.edu
Keywords: *Choice Behavior; *Reinforcement; Psychology; Animals; Choice; Choice Behavior; Columbidae; Delay-reduction theory; Hyperbolic-decay model; Key peck; Male; Optimal foraging theory; Pigeons; Reinforcement (Psychology); Successive-encounters procedure; animal; article; decision making; dept.psy; male; peer-reviewed; pigeons and doves; reinforcement

Mathematical models and the experimental analysis of behaviour - Mazur, James E (Journal of the Experimental Analysis of Behavior, 2006)
The rise of mathematical models in the experimental analysis of behavior has increased over the years, and they offer several advantages. Mathematical models require theorists to be precise and unambiguous, often allowing comparisons of competing theories that sound similar when stated in words. Sometimes different mathematical models may make equally accurate predictions for a large body of data. In Such cases, it is important to find and investigate situations for which the competing models make different predictions because, unless two models are actually mathematically equivalent, they are based on different assumptions about the psychological processes that underlie ail observed behavior. Mathematical models developed in basic behavioral research have been used to predict and control behavior in applied settings, and they have guided research in other areas of psychology. A good mathematical model call provide a common framework for understanding what might otherwise appear to be diverse and unrelated behavioral phenomena. Because psychologists vary in their quantitative skills and in their tolerance for mathematical equations, it is important for those who develop mathematical models of behavior to find ways (such as verbal analogies, pictorial representations, or concrete examples) to communicate the key premises of their models to nonspecialists.
81 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/006-251-406-775-565 tex.type: [object Object]
Keywords: *Models; Theoretical; *Social Behavior; Behavior; Equations; Humans; Mathematical models; Models; Theoretical; Reinforcement; Reinforcement (Psychology); Reinforcement; Psychology; Social Behavior; article; dept.psy; human; peer-reviewed; reinforcement; social behavior; theoretical model

Directed forgetting of a single item - Gottlob, Lawrence R; Golding, Jonathan M; Hauselt, William J (Journal of General Psychology, 2006)
In two experiments, we investigated directed forgetting of a single item. We presented participants with two phone numbers to remember and instructed half of the participants to forget the first phone number. The first number was either learned on a single trial (Experiment 1) or on three trials (Experiment 2). In Experiment 1, there was evidence of directed forgetting as a result of differential encoding; the forget instruction affected recall and recognition for both phone numbers. In Experiment 2, the evidence favored differential rehearsal because the forget instruction affected recall but not recognition. These results indicate that instructions to forget can affect memory of single items.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/082-914-288-498-739 tex.type: [object Object]
Keywords: Cues; Directed forgetting; Forgetting; Humans; Intentional forgetting; Memory; Mental Recall; Recall; Recognition (Psychology); Retention (Psychology); article; association; dept.psy; human; long term memory; recall; recognition

Readiness to change: A longitudinal study of changes in adult identity - Anthis, Kristine; Lavoie, Joseph C (Journal of Research in Personality, 2006)
It has been suggested in the identity literature that a readiness to change may play a role in identity development beyond adolescence, but an empirical investigation of this relationship had yet to be conducted until now. Therefore, the purpose of the current study was to establish a longitudinal relationship between readiness to change and adult identity development. Participants completed measures of readiness to change and identity at both the beginning and the end of the study. The results revealed a relationship between readiness to change and changes in identity exploration over the study interval, and between readiness to change and changes in identity commitment. The findings are discussed in terms of the currently available literature on identity development in adulthood. (c) 2006 Elsevier Inc. All rights reserved.
15 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/086-159-512-069-98X tex.type: [object Object]
Keywords: Adults; Development; Identity; Stages of change; dept.psy; peer-reviewed

Does reflective journal writing improve course performance - Cisero, Cheryl A (College Teaching, 2006)
Abstract. This study investigated whether a reflective journal writing assignment would improve students' course performance. A total of 166 students from undergraduate sections of a course taught by the same instructor over three semesters completed the assignment as part of their requirements. Students (N = 317) from five previous semesters of the same course taught by the same instructor, who were not required to complete the assignment, served as a comparison group. Intervention and comparison groups were comparable on a variety of variables including all assignments, excepting the journal assignment. The findings are interpreted within the context of factors such as students' study habits and motivation. © 2006, Copyright Taylor & Francis Group, LLC.
35 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/104-840-507-385-812 tex.type: [object Object]
Keywords: course performance; dept.psy; journal writing; motivation

Choice between single and multiple reinforcers in concurrent-chains schedules. - Mazur, James E (Journal of the experimental analysis of behavior, 2006)
Pigeons responded on concurrent-chains schedules with equal variable-interval schedules as initial links. One terminal link delivered a single reinforcer after a fixed delay, and the other terminal link delivered either three or five reinforcers, each preceded by a fixed delay. Some conditions included a postreinforcer delay after the single reinforcer to equate the total durations of the two terminal links, but other conditions did not include such a postreinforcer delay. With short initial links, preference for the single-reinforcer alternative decreased when a postreinforcer delay was present, but with long initial links, the postreinforcer delays had no significant effect on preference. In conditions with a postreinforcer delay, preference for the single-reinforcer alternative frequently switched from above 50% to below 50% as the initial links were lengthened. This pattern of results was consistent with delay-reduction theory (Squires & Fantino, 1971), but not with the contextual-choice model (Grace, 1994) or the hyperbolic value-added model (Mazur, 2001) as they have usually been applied. However, the hyperbolic value-added model could account for the results if its calculations were expanded to include reinforcers delivered in later terminal links. The implications of these findings for models of concurrent-chains performance are discussed.
4 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Psychology Department, Southern Connecticut State University, New Haven 06515, USA. mazurj1@southernct.edu
Keywords: *Appetitive Behavior; *Choice Behavior; *Motivation; *Reinforcement Schedule; Animals; Appetitive Behavior; Association Learning; Choice Behavior; Columbidae; Concurrent chains; Contextual-choice model; Delay-reduction theory; Discrimination Learning; Hyperbolic value-added model; Key peck; Motivation; Multiple reinforcers; Pigeons; Psychomotor Performance; Reinforcement Schedule; animal; appetite; article; decision making; dept.psy; discrimination learning; learning; motivation; peer-reviewed; pigeons and doves; psychomotor performance; reinforcement

Impact of enriched environment during adolescence on adult social behavior, hippocampal synaptic density and dopamine D2 receptor expression in rats - Gabriel, Paul; Mastracchio, Toni-Ann; Bordner, Kelly; Jeffrey, Rachel (Physiology & Behavior, 2020)
Environmental enrichment (EE) is one experimental manipulation that induces changes in the brain. However, it is important to distinguish between physical and social components of enrichment. To this end we established four groups of rats reared in different enriched environments during the adolescent period. Our results indicate heightened social memory and increased spine density in dentate gyrus specifically in socially enriched animals. Physical enrichment increased spine density in CA1. Dopamine D2 receptor expression in hippocampus was decreased across all enrichment conditions. Altogether, our results demonstrate differing effects of physical and social enrichment, supporting an important role for environment in synaptogenesis, behavior, and dopaminergic signaling. © 2020 The Authors
17 citations (Crossref) [2023-10-31] tex.ids: gabrielImpactEnrichedEnvironment2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85089521109 type: Article
Keywords: Adolescence; Animals; Article; Dopamine; Environment; Environmental enrichment; Hippocampus; Memory; Rats; Receptors; Dopamine D2; Social Behavior; Social enrichment; Synapse density; animal; animal behavior; animal experiment; controlled study; dentate gyrus; dept.bio; dept.psy; dopamine 2 receptor; dopaminergic transmission; environment; environmental enrichment; female; hippocampal CA1 region; hippocampus; male; memory; nonhuman; peer-reviewed; priority journal; protein expression; rat; social behavior; spine; synapse; synaptogenesis

A preliminary investigation into collegiate student-athletes’ attitudes towards athletic trainers and sport psychology consultants - Ildefonso, Kenneth; Blanton, Jedediah; Durwin, Cheryl; Arvinen-Barrow, Monna; Kamphoff, Cindra (Journal of Sport, 2020)
To investigate if athletes’ attitudes toward athletic trainers and sport psychology consultants differ considering nature of athletic ability beliefs and previous experiences with these professionals; collegiate student-athletes (n = 114 male, n = 81 female, M age = 19.77, SD = 1.43) completed the Conceptions of the Nature of Athletic Ability Questionnaire-2 (Biddle, Wang, Chatzisarantis, & Spray, 2003), Attitudes Toward Athletic Trainers-Form (modified from the Attitudes toward Physiotherapist-Form; Arvinen-Barrow, Clement, & Bayes, 2012), and the Sport Psychology Attitudes Revised-Form (Martin, Kellman, Lavallee, & Page, 2002). Multiple analyses of variance revealed small statistically significant mean differences in attitudes considering ability beliefs, previous athletic training, and sport psychology experiences. Athletes with previous athletic training experience were less confident in their athletic trainer than those without such experience. In contrast, athletes with previous sport psychology experience were more confident in their consultant than those without such experiences. Results suggest athletes’ attitudes towards helping professionals may be partially influenced by subjective norms and expectations about the nature of such relationships.
0 citations (Crossref) [2023-10-31]
Keywords: dept.psy; peer-reviewed

Is women's participation in different types of yoga classes associated with different levels of body awareness and body satisfaction? - Delaney, Kelley; Anthis, Kristine (International Journal of Yoga Therapy, 2010)
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/144-918-740-989-418 tex.type: [object Object]
Keywords: dept.psy

Integrating DSM-IV factors to predict violence in high-risk psychiatric patients - Lynch, Donna M.; Noel, Helen C. (Journal of Forensic Sciences, 2010)
This study incorporated Axis-II and Axis-IV factors in DSM-IV to test the relationship between predicted risk for violence assessed in the psychiatric emergency room and actual violence during hospitalization. Psychiatric nurses lack an objective instrument to use during the acute psychiatric assessment. The retrospective study comprised consecutive psychiatric admissions (n = 161) in one tertiary veterans' hospital. Statistical testing for the predictive power of risk factors, relationships between variables, and violent events included nonparametric tests, factor analysis, and logistic regression. Of the 32 patients who committed violence during hospitalization, 12 had committed violence in the psychiatric emergency room. Statistical significance was shown for violent incidents and dementia, court-ordered admission, mood disorder, and for three or more risk factors. The 13-item Risk of Violence Assessment (ROVA) scale suggests validity and sensitivity for rating DSM-IV factors and psychosocial stressors to predict risk for violence during hospitalization. Replication studies are recommended to strengthen validity of the ROVA scale.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/005-672-952-996-516 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Adult; Aged; Aged; 80 and over; Aggression; Assault; Assessment; Commitment of Mentally Ill; Dementia; Diagnostic and Statistical Manual of Mental Disorders; Diagnostic and statistical manual of mental disorders (DSM-IV); Emergency Services; Psychiatric; Female; Forensic Psychiatry; Forensic science; Hospitals; Veterans; Humans; Instrument; Male; Mental Disorders; Middle Aged; New England; Psychiatric; Psychiatric Status Rating Scales; Reproducibility of Results; Retrospective Studies; Risk Assessment; Risk factors; Self-harm; Suicidal; United States; Violence; adult; aged; article; dementia; dept.psy; diagnostic and statistical manual of mental disorders; emergency health service; female; forensic psychiatry; human; male; mental disease; middle aged; psychological aspect; psychological rating scale; public hospital; reproducibility; retrospective study; risk assessment; violence

The role of conflict in continuity and change: life events associated with identity development in racially and ethnically diverse women - Anthis, Kristine (Identity, 2011)
In this archival study, life events were identified that served as precursors to identity transitions in 149 European American, African American, Mexican American, and Puerto Rican women. The data were collected during a period from the late 1970s to the early 1980s in the United States. Participants were interviewed and asked to describe events that had influenced their understanding of themselves. Events were coded into relational, career, education, personal, health-related, and miscellaneous categories. Results indicated that women were more likely to report life events regarding their relationships than events in other categories. A reexamination of the data revealed that that there were more similarities than differences among the racial and ethnic groups in terms of the life events described. Respondents were more likely to report continuity than change in their identities in response to life events serving as possible precursors to change. Results also revealed that when change did occur, it was associated with high levels of conflict particularly for the domains of relationships and educational achievement expectations. © 2011 Copyright Taylor and Francis Group, LLC.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/090-314-655-157-524 tex.type: [object Object]
Keywords: dept.psy

Mindfulness and modification therapy for behavioral dysregulation: results from a pilot study targeting alcohol use and aggression in women - Wupperman, Peggilee; Marlatt, G. Alan; Cunningham, Amy; Bowen, Sarah; Berking, Matthias; Mulvihill-Rivera, Nicole; Easton, Caroline (Journal of Clinical Psychology, 2012)
Objectives: Increasing evidence suggests that deficits in mindfulness (awareness, attentiveness, and acceptance of the present moment) play a role in a range of disorders involving behavioral dysregulation. This paper adds to that literature by describing a transdiagnostic psychotherapy (Mindfulness & Modification Therapy; MMT) developed to target behavioral dysregulation. Design: An open-treatment pilot-trial investigated the feasibility, acceptability, and pre-post effects of MMT targeting women (N = 14) court-referred for alcohol abuse/dependence and aggression. Results: Pre-post comparisons revealed significant decreases in alcohol use, drug use, and aggression. In addition, the retention rate was 93%. Conclusion: Preliminary evidence suggests that MMT is a feasible and acceptable treatment that decreases dysregulated behaviors such as substance use and aggression, while also potentially increasing retention. (c) 2011 Wiley Periodicals, Inc. J Clin Psychol 67:117, 2011.
48 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/106-354-822-412-533 tex.unique-id: [object Object]
Keywords: Adult; Aggression; Alcoholism; Anger; Attention; Awareness; Behavior dysregulation; Cognitive Therapy; Domestic Violence; Emotion regulation; Emotions; Female; Humans; Intervention; Middle Aged; Mindfulness; Pilot Projects; Substance; Transdiagnostic; Treatment Outcome; Young Adult; adult; aggression; alcoholism; article; attention; awareness; cognitive therapy; dept.psy; domestic violence; emotion; female; human; legal aspect; methodology; middle aged; physiology; pilot study; psychological aspect; treatment outcome

Neuroendocrine profiles associated with discrete behavioural variation in Symphodus ocellatus, a species with male alternative reproductive tactics. - Nugent, Bridget M.; Stiver, Kelly A.; Alonzo, Suzanne H.; Hofmann, Hans A. (Molecular Ecology, 2016)
The molecular mechanisms underlying phenotypic plasticity are not well understood. Identifying mechanisms underlying alternative reproductive tactics (ARTs) in species for which the behavioural and fitness consequences of this variation are well characterized provides an opportunity to integrate evolutionary and mechanistic understanding of the maintenance of variation within populations. In the ocellated wrasse Symphodus ocellatus, the behavioural phenotypes of three distinct male morphs (sneakers, satellites and nesting males), which arise from a single genome, have been thoroughly characterized. To determine the neuroendocrine and genomic mechanisms associated with discrete phenotypic variation and ARTs in S. ocellatus in their natural environment, we constructed a whole-brain de novo transcriptome and compared global patterns of gene expression between sexes and male morphs. Next, we quantified circulating cortisol and 11-ketotestosterone (11-kt), mediators of male reproductive behaviours, as well as stress and gonadal steroid hormone receptor expression in the preoptic area, ventral subpallial division of the telencephalon and dorsolateral telencephalon, critical brain regions for social and reproductive behaviours. We found higher levels of 11-kt in nesting males and higher levels of cortisol in sneaker males relative to other male morphs and females. We also identified distinct patterns of brain region-specific hormone receptor expression between males such that most hormone receptors are more highly expressed in satellites and nesting males relative to sneakers and females. Our results establish the neuroendocrine and molecular mechanisms that underlie ARTs in the wild and provide a foundation for experimentally testing hypotheses about the relationship between neuromolecular processes and reproductive success. Copyright © 2016 John Wiley & Sons Ltd.
13 citations (Crossref) [2023-10-31] Citation Key Alias: pop00070 tex.type: [object Object]
Keywords: *Neurosecretory Systems/ph [Physiology]; *Perciformes/ph [Physiology]; *Reproduction; *Sexual Behavior; Animal; 11-ketotestosterone; Animals; Brain; Brain/me [Metabolism]; Female; Hydrocortisone; Hydrocortisone/bl [Blood]; Male; Nesting Behavior; Neurosecretory Systems; Perciformes; Perciformes/ge [Genetics]; Phenotype; Reproduction; Sexual Behavior; Animal; Testosterone; Testosterone/aa [Analogs & Derivatives]; Testosterone/bl [Blood]; Transcriptome; alternative reproductive tactics; analogs and derivatives; animal; blood; brain; dept.psy; female; gene expression; genetics; hormones; hydrocortisone; male; metabolism; nesting; neurosecretion; peer-reviewed; phenotype; physiology; reproduction; sexual behavior; testosterone; transcriptome

Ocean acidification affects fish spawning but not paternity at CO2 seeps - Milazzo, Marco; Cattano, Carlo; Alonzo, Suzanne H; Foggo, Andrew; Gristina, Michele; Rodolfo-Metalpa, Riccardo; Sinopoli, Mauro; Spatafora, Davide; Stiver, Kelly A; Hall-Spencer, Jason M (Proceedings of the Royal Society B: Biological Sciences, 2016)
Fish exhibit impaired sensory function and altered behaviour at levels of ocean acidification expected to occur owing to anthropogenic carbon dioxide emissions during this century. We provide the first evidence of the effects of ocean acidification on reproductive behaviour of fish in the wild. Satellite and sneaker male ocellated wrasse (Symphodus ocellatus) compete to fertilize eggs guarded by dominant nesting males. Key mating behaviours such as dominant male courtship and nest defence did not differ between sites with ambient versus elevated CO2 concentrations. Dominant males did, however, experience significantly lower rates of pair spawning at elevated CO2 levels. Despite the higher risk of sperm competition found at elevated CO2, we also found a trend of lower satellite and sneaker male paternity at elevated CO2 Given the importance of fish for food security and ecosystem stability, this study highlights the need for targeted research into the effects of rising CO2 levels on patterns of reproduction in wild fish. Copyright © 2016 The Author(s).
32 citations (Crossref) [2023-10-31] Place: England Milazzo, Marco. Department of Earth and Marine Sciences (DiSTeM), CoNISMa, University of Palermo, Palermo 90123, Italy marco.milazzo@unipa.it. Cattano, Carlo. Department of Earth and Marine Sciences (DiSTeM), CoNISMa, University of Palermo, Palermo 90123, Italy. Alonzo, Suzanne H. PBSci-Ecology and Evolutionary Biology Department, Institute of Marine Sciences, University of California Santa Cruz, Santa Cruz, CA 95064, USA. Foggo, Andrew. Marine Biology and Ecology Research Centre, Plymouth University, Plymouth, PL4 8AA, UK. Gristina, Michele. CNR-IAMC, Mazara del Vallo (TP), 91026, Italy. Rodolfo-Metalpa, Riccardo. Institut de Recherche pour le Developpement, UMR 250 ENTROPIE, Noumea, 98848, New Caledonia. Sinopoli, Mauro. Institute for Environmental Protection and Research (ISPRA), Palermo 90143, Italy. Spatafora, Davide. Department of Earth and Marine Sciences (DiSTeM), CoNISMa, University of Palermo, Palermo 90123, Italy. Stiver, Kelly A. Psychology Department, Southern Connecticut State University, New Haven, CT 06515, USA. Hall-Spencer, Jason M. Marine Biology and Ecology Research Centre, Plymouth University, Plymouth, PL4 8AA, UK International Educational and Research Laboratory Program, Shimoda Marine Research Center, University of Tsukuba, 5-10-1 Shimoda, Shizuoka 415-0025, Japan.
Keywords: *Carbon Dioxide/ch [Chemistry]; *Perciformes/ph [Physiology]; *Reproduction/ph [Physiology]; *Seawater/ch [Chemistry]; *Sexual Behavior; Animal; Alternative reproductive tactics; Animals; CO2 vent; Carbon Dioxide; Climate change; Hydrogen-Ion Concentration; Labrid; Labridae; Male; Oceans and Seas; Perciformes; Reproduction; Seawater; Sexual Behavior; Animal; Symphodus ocellatus; acidification; animal; anthropogenic effect; carbon dioxide; carbon emission; chemistry; climate change; concentration (composition); courtship; dept.psy; ecological stability; food security; male; pH; paternity; perciform; physiology; reproduction; reproductive behavior; sea; sea water; sexual behavior; spawning population; sperm competition; wild population

Human choices between variable and fixed rewards in hypothetical variable‐delay and double‐reward discounting procedures - McKerchar, Todd L.; Mazur, James E. (Journal of the Experimental Analysis of Behavior, 2016)
Prior research has shown that nonhumans show an extreme preference for variable-over fixed-delays to reinforcement. This well-established preference for variability occurs because a reinforcer's strength or “value” decreases according to a curvilinear function as its delay increases. The purpose of the present experiments was to investigate whether this preference for variability occurs with human participants making hypothetical choices. In three experiments, participants recruited from Amazon Mechanical Turk made choices between variable and fixed monetary rewards. In a variable-delay procedure, participants repeatedly chose between a reward delivered either immediately or after a delay (with equal probability) and a reward after a fixed delay (Experiments 1 and 2). In a double-reward procedure, participants made choices between an alternative consisting of two rewards, one delivered immediately and one after a delay, and a second alternative consisting of a single reward delivered after a delay (Experiments 1 and 3). Finally, all participants completed a standard delay-discounting task. Although we observed both curvilinear discounting and magnitude effects in the standard discounting task, we found no consistent evidence of a preference for variability-as predicted by two prominent models of curvilinear discounting (i.e., a simple hyperbola and a hyperboloid)-in our variable-delay and double-reward procedures. This failure to observe a preference for variability may be attributed to the hypothetical, rule-governed nature of choices in the present study. In such contexts, participants may adopt relatively simple strategies for making more complex choices.
3 citations (Crossref) [2023-10-31] Citation Key Alias: pop00258 tex.type: [object Object]
Keywords: dept.psy; peer-reviewed

A longitudinal follow-up study of happiness and meaning-making - Abe, Jo Ann A. (The Journal of Positive Psychology, 2016)
The long-term outcomes associated with happiness and meaning-making were examined by following up on participants in previous studies on experiential learning an average of 2.5 years later. Measures of happiness and meaning-making were extracted by analyzing the participants' journals using a computerized text-analysis program. Happiness as assessed by a composite measure of positive emotionality showed weak associations with the measures of adaptive functioning, and was negatively correlated with optimism, as well as positively correlated with emotion suppression. By contrast, meaning-making as assessed by composite measures of cognitive processing and self-distancing was robustly positively correlated with almost all measures of adaptive functioning. Regression analyses revealed that the two measures of meaning and their interaction term accounted for 20-24% of the variance in predicting the outcome measures. This study revealed that there may be at times a trade-off between happiness and meaning-making as well as a reversal in their patterns of long-term outcomes.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/062-977-358-552-036 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: LIWC; dept.psy; follow up; happiness; longitudinal; meaning-making; regression analysis; self-distancing; text-analysis

Ovarian fluid allows directional cryptic female choice despite external fertilization. - Alonzo, Suzanne H; Stiver, Kelly A; Marsh-Rollo, Susan E (Nature Communications, 2016)
In species with internal fertilization, females can favour certain males over others, not only before mating but also within the female's reproductive tract after mating. Here, we ask whether such directional post-mating (that is, cryptic) female mate choice can also occur in species with external fertilization. Using an in vitro sperm competition experiment, we demonstrate that female ovarian fluid (ovarian fluid) changes the outcome of sperm competition by decreasing the importance of sperm number thereby increasing the relative importance of sperm velocity. We further show that ovarian fluid does not differentially affect sperm from alternative male phenotypes, but generally enhances sperm velocity, motility, straightness and chemoattraction. Under natural conditions, female ovarian fluid likely increases the paternity of the preferred parental male phenotype, as these males release fewer but faster sperm. These results imply females have greater control over fertilization and potential to exert selection on males in species with external fertilization than previously thought possible.
81 citations (Crossref) [2023-10-31] Place: England Alonzo, Suzanne H. Department of Ecology and Evolutionary Biology, Yale University, 165 Prospect Street, New Haven, Connecticut 06520, USA. Alonzo, Suzanne H. Department of Ecology and Evolutionary Biology, University of California Santa Cruz, 1156 High Street, Santa Cruz, California 95064, USA. Stiver, Kelly A. Department of Ecology and Evolutionary Biology, Yale University, 165 Prospect Street, New Haven, Connecticut 06520, USA. Stiver, Kelly A. Psychology Department, Southern Connecticut State University, 501 Crescent Street, New Haven, Connecticut 06515, USA. Marsh-Rollo, Susan E. Department of Ecology and Evolutionary Biology, University of California Santa Cruz, 1156 High Street, Santa Cruz, California 95064, USA. Marsh-Rollo, Susan E. Department of Psychology, Neuroscience, and Behaviour, McMaster University, 1280 Main Street W, Hamilton, Ontario, Canada L8S4K1.
Keywords: *Body Fluids/me [Metabolism]; *Choice Behavior/ph [Physiology]; *Fertilization/ph [Physiology]; *Ovary/me [Metabolism]; *Spermatozoa/ph [Physiology]; Animals; Body Fluids; Choice Behavior; Female; Fertilization; Male; Ovary; Perciformes; Perciformes/ph [Physiology]; Reproduction; Reproduction/ph [Physiology]; Sexual Behavior; Animal; Sexual Behavior; Animal/ph [Physiology]; Sperm Count; Spermatozoa; animal; body fluid; decision making; dept.psy; experimental study; female; fertilization; fertilization (reproduction); in vitro study; liquid; male; mate choice; metabolism; ovary; paternity; phenotype; physiology; reproduction; sexual behavior; species; sperm; sperm competition; spermatozoon; spermatozoon count; spermatozoon motility; thinking

Age-related effects of chronic restraint stress on ethanol drinking, ethanol-induced sedation, and on basal and stress-induced anxiety response. - Fernandez, Macarena Soledad; Fabio, Maria Carolina; Miranda-Morales, Roberto Sebastian; Virgolini, Miriam B; De Giovanni, Laura N; Hansen, Cristian; Wille-Bille, Aranza; Nizhnikov, Michael E; Spear, Linda P; Pautassi, Ricardo Marcos (Alcohol, 2016)
Adolescents are sensitive to the anxiolytic effect of ethanol, and evidence suggests that they may be more sensitive to stress than adults. Relatively little is known, however, about age-related differences in stress modulation of ethanol drinking or stress modulation of ethanol-induced sedation and hypnosis. We observed that chronic restraint stress transiently exacerbated free-choice ethanol drinking in adolescent, but not in adult, rats. Restraint stress altered exploration patterns of a light-dark box apparatus in adolescents and adults. Stressed animals spent significantly more time in the white area of the maze and made significantly more transfers between compartments than their non-stressed peers. Behavioral response to acute stress, on the other hand, was modulated by prior restraint stress only in adults. Adolescents, unlike adults, exhibited ethanol-induced motor stimulation in an open field. Stress increased the duration of loss of the righting reflex after a high ethanol dose, yet this effect was similar at both ages. Ethanol-induced sleep time was much higher in adult than in adolescent rats, yet stress diminished ethanol-induced sleep time only in adults. The study indicates age-related differences that may increase the risk for initiation and escalation in alcohol drinking. Copyright © 2016 Elsevier Inc. All rights reserved.
27 citations (Crossref) [2023-10-31] Place: United States Fernandez, Macarena Soledad. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC - CONICET-Universidad Nacional de Cordoba), Cordoba, Argentina; Center for Development and Behavioral Neuroscience, Binghamton University, Binghamton, NY, USA. Fabio, Maria Carolina. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC - CONICET-Universidad Nacional de Cordoba), Cordoba, Argentina; Center for Development and Behavioral Neuroscience, Binghamton University, Binghamton, NY, USA. Miranda-Morales, Roberto Sebastian. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC - CONICET-Universidad Nacional de Cordoba), Cordoba, Argentina. Virgolini, Miriam B. Instituto de Farmacologia Experimental de Cordoba (IFEC-CONICET), Cordoba, Argentina; Departamento de Farmacologia, Facultad de Ciencias Quimicas, UNC, Cordoba, Argentina. De Giovanni, Laura N. Instituto de Farmacologia Experimental de Cordoba (IFEC-CONICET), Cordoba, Argentina; Departamento de Farmacologia, Facultad de Ciencias Quimicas, UNC, Cordoba, Argentina. Hansen, Cristian. Laboratorio de Analisis Clinicos Especializados (LACE), Cordoba, Argentina. Wille-Bille, Aranza. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC - CONICET-Universidad Nacional de Cordoba), Cordoba, Argentina. Nizhnikov, Michael E. Southern Connecticut State University, New Haven, CT, USA. Spear, Linda P. Center for Development and Behavioral Neuroscience, Binghamton University, Binghamton, NY, USA. Pautassi, Ricardo Marcos. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC - CONICET-Universidad Nacional de Cordoba), Cordoba, Argentina; Facultad de Psicologia, Universidad Nacional de Cordoba (UNC), Cordoba, Argentina. Electronic address: rpautassi@gmail.com.
Keywords: *Alcohol Drinking/px [Psychology]; *Anxiety/px [Psychology]; *Ethanol/ad [Administration & Dosage]; *Hypnotics and Sedatives/ad [Administration & Dosage]; *Stress; Psychological/px [Psychology]; Adolescent; Adult; Age Factors; Alcohol Drinking; Alcohol Drinking/ae [Adverse Effects]; Alcohol Drinking/bl [Blood]; Animals; Anxiety; Anxiety/bl [Blood]; Anxiety/et [Etiology]; Article; Chronic Disease; Ethanol; Ethanol/to [Toxicity]; Hypnotics and Sedatives; Hypnotics and Sedatives/to [Toxicity]; Male; Rat; Rats; Rats; Sprague-Dawley; Rats; Wistar; Restraint stress; Sprague Dawley rat; Stress; Psychological; Stress; Psychological/bl [Blood]; Stress; Psychological/co [Complications]; Wistar rat; acute stress; adverse effects; age; age distribution; alcohol; alcohol blood level; alcohol consumption; animal; animal behavior; anxiety; blood; body weight; chronic disease; complication; controlled study; corticosterone; corticosterone blood level; dept.psy; drinking behavior; etiology; hypnosis; hypnotic sedative agent; locomotion; male; mental stress; motor activity; mouse; nonhuman; open field test; peer-reviewed; psychology; rat; restrain stress; righting reflex; sedation; sex difference; sleep time; stimulus response; stress

The role of genes involved in stress, neural plasticity, and brain circuitry in depressive phenotypes: Convergent findings in a mouse model of neglect. - Montalvo-Ortiz, Janitza L; Bordner, Kelly A; Carlyle, Becky C; Gelernter, Joel; Simen, Arthur A; Kaufman, Joan (Behavioural brain research, 2016)
Early life neglect increases risk for the development of psychopathologies during childhood and adulthood, including depression and anxiety disorders. We recently reported epigenetic changes in DNA derived from saliva in three genes predicted depression in a cohort of maltreated children: DNA-binding protein inhibitor ID-3 (ID3), Glutamate NMDA Receptor (GRIN1), and Tubulin Polymerization Promoting Protein (TPPP). To validate the role of these genes in depression risk, secondary analyses were conducted of gene expression data obtained from medial prefrontal cortex (mPFC) tissue of mice subjected to a model of maternal neglect which included maternal separation and early weaning (MSEW). Anxiety and depression-like phenotype data derived using the elevated plus maze (EPM) and forced swimming test (FST), respectively, were also available for secondary analyses. Behavioral tests were conducted in MSEW and control adult male mice when they were between 65 and 80days old. ID3, GRIN1 and TPPP gene expression in the mPFC were found to significantly predict behavioral differences in the EPM and FST. These results further support the role of these genes in the etiology of depressive and anxiety phenotypes following early life stress. Copyright © 2016. Published by Elsevier B.V.
26 citations (Crossref) [2023-10-31] Place: Netherlands Montalvo-Ortiz, Janitza L. Department of Psychiatry, Yale University, New Haven, CT, 06520, United States. Bordner, Kelly A. Southern Connecticut State University, New Haven, CT, United States. Carlyle, Becky C. Department of Psychiatry, Yale University, New Haven, CT, 06520, United States. Gelernter, Joel. Department of Psychiatry, Yale University, New Haven, CT, 06520, United States; Veterans Administration, West Haven, CT, United States. Simen, Arthur A. Neuroscience Research Unit, Pfizer Worldwide Research & Development, Cambridge, MA, United States. Kaufman, Joan. Center for Child and Family Traumatic Stress, Kennedy Krieger Institute, United States; Department of Psychiatry, Johns Hopkins School of Medicine, United States. Electronic address: joan.kaufman@kennedykrieger.org.
Keywords: *Depression/pa [Pathology]; *Gene Expression Regulation/ph [Physiology]; *Maternal Deprivation; *Neuronal Plasticity/ph [Physiology]; *Prefrontal Cortex/me [Metabolism]; *Stress; Psychological/pa [Pathology]; Animals; Article; C57BL mouse; DBA mouse; DNA-binding protein inhibitor ID-3 (ID3); Depression; Disease Models; Animal; GRIN1 gene; Gene Expression Regulation; Glutamate NMDA receptor (GRIN1); Gprin1 protein; mouse; ID3 gene; Idb3 protein; mouse; Inhibitor of Differentiation Proteins; Inhibitor of Differentiation Proteins/ge [Genetics]; Inhibitor of Differentiation Proteins/me [Metabolism]; Male; Maternal Deprivation; Maze Learning; Maze Learning/ph [Physiology]; Methylation; Mice; Mice; Inbred C57BL; Mice; Inbred DBA; Microarray Analysis; Neglect; Nerve Tissue Proteins; Nerve Tissue Proteins/ge [Genetics]; Nerve Tissue Proteins/me [Metabolism]; Neuronal Plasticity; Prefrontal Cortex; RNA; Messenger; RNA; Messenger/me [Metabolism]; Receptors; N-Methyl-D-Aspartate; Receptors; N-Methyl-D-Aspartate/ge [Genetics]; Receptors; N-Methyl-D-Aspartate/me [Metabolism]; Stress; Psychological; Swimming; Swimming/px [Psychology]; TPPP protein; mouse; Tubulin polymerization promoting protein (TPPP); animal; animal experiment; animal model; animal tissue; anxiety; connectome; controlled study; depression; dept.psy; disease activity; disease model; early life stress; gene; gene expression regulation; gene function; gene identification; gene location; genetics; inhibitor of differentiation protein; male; maternal deprivation; maze test; medial prefrontal cortex; mental stress; messenger RNA; metabolism; microarray analysis; molecular dynamics; molecular pathology; mouse; n methyl dextro aspartic acid receptor; nerve cell plasticity; nerve protein; nonhuman; pathology; peer-reviewed; phenotype; physiology; prediction; prefrontal cortex

Transgenerational transmission of the effect of gestational ethanol exposure on ethanol Use‐Related behavior - Nizhnikov, Michael E; Popoola, Daniel O; Cameron, Nicole M (Alcoholism: Clinical and Experimental Research, 2016)
Background: Prenatal alcohol exposure (PAE) enhances the risk for alcoholism by increasing the propensity to consume alcohol and altering neurophysiological response to alcohol challenge. Trans-generationally transmittable genetic alterations have been implicated in these behavioral changes. To date, transgenerational transmission of PAE-induced behavioral responses to alcohol has never been experimentally investigated. Therefore, we explored the transgenerational transmission of PAE-induced behavioral effects across 3 generations. Methods: Pregnant Sprague Dawley dams received 1 g/kg ethanol (EtOH) or water daily on gestational days 17 through 20 via gavage, or remained untreated in their home cages. To produce second filial (F2) or F3 generations, similarly treated adult F1 or F2 offspring were mated and left undisturbed through gestation. On postnatal day (PND) 14, male and female F1, F2, and F3 offspring were tested for consumption of 5% (w/v) EtOH (in water), or water. Using the loss of righting reflex (LORR) paradigm on PND 42, F1 and F2 adolescent male offspring were tested for sensitivity to acute EtOH-induced sedation-hypnosis at 3.5 or 4.5 g/kg dose. F3 male adolescents were similarly tested at 3.5 g/kg dose. Blood EtOH concentration (BEC) was measured at waking. Results: EtOH exposure increased EtOH consumption compared to both water and untreated control groups in all generations. EtOH-treated group F1 and F2 adolescents displayed attenuated LORR duration compared to the water group. No attenuated LORR was observed in the F3 generation. BEC at waking corroborated with the significant LORR duration differences while also revealing differences between untreated control and water groups in F1 and F2 generations. Conclusions: Our results provide novel behavioral evidence attesting that late gestational moderate EtOH exposure increases EtOH intake across 3 generations and may alter sensitivity to EtOH-induced sedation-hypnosis across 2 generations. © 2016 Research Society on Alcoholism.
25 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/013-977-782-274-445 tex.type: [object Object]
Keywords: Alcohol Drinking; Animals; Animals; Newborn; Article; Ethanol; Female; Infant; Intake; Loss of Righting Reflex; Male; Pregnancy; Prenatal Exposure Delayed Effects; Rat; Rats; Rats; Sprague-Dawley; Sprague Dawley rat; adult; alcohol; alcoholism; animal; animal experiment; behavior; behavior change; chemically induced; dept.psy; drinking behavior; epigenetics; female; genetics; hypnosis; male; newborn; nonhuman; pregnancy; prenatal exposure; priority journal; progeny; psychology; rat; righting reflex; sedation; transgenerational transmission; wakefulness; water

Very-Brief, Web-Based Interventions for Reducing Alcohol Use and Related Problems among College Students: A Review. - Leeman, Robert F; Perez, Elliottnell; Nogueira, Christine; DeMartini, Kelly S (Frontiers in psychiatry, 2015)
Very-brief, web-based alcohol interventions have great potential due to their convenience, ease of dissemination, and college students' stated preference for this intervention modality. To address the efficacy of these interventions, we conducted a review of the literature to identify randomized controlled trials (RCTs). Fifteen published reports were included. All RCTs meeting criteria for inclusion tested an intervention that featured personalized feedback on students' patterns of alcohol consumption. This review found some evidence to support the efficacy of very-brief, web-based interventions among college students for alcohol use reduction. Several trials, however, reported no evidence of efficacy and the methods of multiple trials raised concerns about potential bias that may have influenced study results. By contrast, this review did not yield evidence to support the efficacy of very-brief, web-based interventions for reduction of alcohol–related problems among college students. We found evidence to support the efficacy of two main types of intervention content: (a) focused solely on personalized normative feedback designed to correct misconceptions about peer alcohol consumption and (b) multi-component interventions. Future research is needed to test enhancements to very-brief, web-based interventions that feature personalized feedback on patterns of alcohol use and to determine for which types of college drinkers (e.g., heavier or lighter drinkers) these interventions are most efficacious. In addition, future studies are needed to test novel, very-brief, web-based interventions featuring approaches other than personalized feedback. In summary, this review yielded some evidence supporting very-brief, web-based interventions in reducing alcohol use but not related problems in college students. Very-brief, web-based interventions are worth pursuing given their convenience, privacy, and potential public health benefit.
21 citations (Crossref) [2023-10-31] Place: Switzerland Leeman, Robert F. Department of Psychiatry, Yale School of Medicine, New Haven, CT, USA. Perez, Elliottnell. Department of Psychology, Southern Connecticut State University, New Haven, CT, USA. Nogueira, Christine. Department of Psychiatry, Yale School of Medicine, New Haven, CT, USA. DeMartini, Kelly S. Department of Psychiatry, Yale School of Medicine, New Haven, CT, USA.
Keywords: Computer; Effectiveness; Intervention; Motivational interviewing; Prevention; Review; Technology; Young adult; Youth; alcohol consumption; attitude to health; college student; dept.psy; evidence based practice; follow up; human; outcome assessment; peer group; peer-reviewed; personalized feedback; public health service; randomized controlled trial (topic); sample size; systematic error; very brief web based intervention

Age-related effects of restraint stress on ethanol intake and ethanol-induced narcosis - Pautassi, R. M.; Fernandez, M.; Nizhnikov, M.; Spear, L. P. (Alcohol and Alcoholism, 2015)
tex.eissn: 1464-3502 tex.meeting: P-31 tex.orcid-numbers: Pautassi, Ricardo/0000-0003-1876-2321 tex.researcherid-numbers: Pautassi, Ricardo/G-7261-2018 tex.unique-id: ISI:000361525900202
Keywords: dept.psy; ⛔ No DOI found

Should police use ACID? Training and credibility assessment using transcripts versus recordings - Colwell, Kevin; James-Kangal, Neslihan; Hiscock-Anisman, Cheryl; Phelan, Vivian (Journal of Forensic Psychology Practice, 2015)
There is a need for an applicable system of investigative interviewing and credibility assessment that extends science to practice. Experiment 1: Officers assessed the credibility of colleagues in a face-to-face interaction. Fourteen of sixteen officers were wrong in determining whether their colleague was responding honestly to them or lying to them. Experiment 2 compared untrained officers to officers trained in Assessment Criteria Indicative of Deception (ACID) in their ability to assess the credibility of statements regarding real and mock crimes by analyzing either verbatim transcripts or audio recordings. Officers who were trained in ACID performed significantly better after training than before, and significantly better than a group of officers who were never trained in ACID (89% correct versus 53% correct). No differences emerged due to analyzing transcripts versus recordings. The practical aspects of these results are discussed, including success rate, ease of application, and ease of training. The theoretical discussion includes differential recall enhancement and impression management. Finally, limitations and suggestions for future research are presented.
11 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/172-830-993-603-666 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Article; Assessment Criteria Indicative of Deception (ACID); adult; assessment criteria indicative of deception; audio recording; clinical assessment tool; controlled study; credibility assessment; criminal justice; deception; decision making; dept.psy; diagnostic accuracy; differential recall enhancement; human; human experiment; investigative interviewing; police; recall; scoring system; task performance; training; verbal behavior; videorecording; visual stimulation; word recognition; written language

Prenatal ethanol increases ethanol intake throughout adolescence, alters ethanol-mediated aversive learning, and affects μ but not δ or κ opioid receptor mRNA expression - Fabio, María Carolina; Macchione, Ana Fabiola; Nizhnikov, Michael E.; Pautassi, Ricardo Marcos (European Journal of Neuroscience, 2015)
Animal models of prenatal ethanol exposure (PEE) have indicated a facilitatory effect of PEE on adolescent ethanol intake, but few studies have assessed the effects of moderate PEE throughout adolescence. The mechanisms underlying this facilitatory effect remain largely unknown. In the present study, we analysed ethanol intake in male and female Wistar rats with or without PEE (2.0 g/kg, gestational days 17-20) from postnatal days 37 to 62. The results revealed greater ethanol consumption in PEE rats than in controls, which persisted throughout adolescence. By the end of testing, ethanol ingestion in PEE rats was nearly 6.0 g/kg. PEE was associated with insensitivity to ethanol-induced aversion. PEE and control rats were further analysed for levels of μ, δ and κ opioid receptor mRNA in the infralimbic cortex, nucleus accumbens shell, and ventral tegmental area. Similar levels of mRNA were observed across most areas and opioid receptors, but μ receptor mRNA in the ventral tegmental area was significantly increased by PEE. Unlike previous studies that assessed the effects of PEE on ethanol intake close to birth, or in only a few sessions during adolescence, the present study observed a facilitatory effect of PEE that lasted throughout adolescence. PEE was associated with insensitivity to the aversive effect of ethanol, and increased levels of μ opioid receptor transcripts. PEE is a prominent vulnerability factor that probably favors the engagement of adolescents in risky trajectories of ethanol use. © 2015 Federation of European Neuroscience Societies and John Wiley & Sons Ltd.
45 citations (Crossref) [2023-10-31] Citation Key Alias: pop00123 tex.type: [object Object]
Keywords: *Alcohol Drinking/pp [Physiopathology]; *Avoidance Learning/de [Drug Effects]; *Central Nervous System Depressants/to [Toxicity]; *Ethanol/to [Toxicity]; *Prenatal Exposure Delayed Effects/ci [Chemically Induced]; *Receptors; Opioid; delta/me [Metabolism]; *Receptors; Opioid; kappa/me [Metabolism]; Adolescent; Age Factors; Alcohol Drinking; Animals; Article; Aversive conditioning; Avoidance Learning; Central Nervous System Depressants; Ethanol; Ethanol intake; Female; Male; Opioid receptors; Pregnancy; Prenatal Exposure Delayed Effects; Prenatal Exposure Delayed Effects/pp [Physiopathology]; Prenatal ethanol; RNA isolation; RNA; Messenger; RNA; Messenger/me [Metabolism]; Rats; Rats; Wistar; Receptors; Opioid; delta; Receptors; Opioid; delta/ge [Genetics]; Receptors; Opioid; kappa; Receptors; Opioid; kappa/ge [Genetics]; Wistar rat; adolescence; adolescent; age; alcohol; alcohol consumption; alcohol intoxication; animal; animal experiment; animal model; aversion; aversive behavior; aversive conditioning; avoidance behavior; body weight; central depressant agent; chemically induced; controlled study; delta opiate receptor; dept.psy; drinking behavior; drug effects; ethanol intake; facilitation; female; fluid intake; genetics; glyceraldehyde 3 phosphate dehydrogenase; kappa opiate receptor; male; messenger RNA; metabolism; microdissection; motivation; mu opiate receptor; nonhuman; opioid receptors; pathophysiology; place preference; polymerase chain reaction; pregnancy; prenatal ethanol; prenatal ethanol exposure; prenatal exposure; priority journal; protein expression; quantitative analysis; rat; reinforcement; reverse transcription; sigma opiate receptor; sugar intake

Differential emotions theory as a theory of personality development - Abe, Jo Ann A. (Emotion Review, 2015)
In The Face of Emotions, which was Carroll Izard's first major attempt at elaborating his differential emotions theory (DET), he stated that the book presents a theoretical framework for the study of emotions and their role in personality and interpersonal processes. Yet, over the years, his contribution to personality theory has generally been overshadowed by the attention focused on his views on facial expressions and the structure of emotions. This article will begin with a brief overview of the DET perspective on personality development. Then, it will examine how the DET framework can be used to organize recent findings from three lines of research on adult personality. It will conclude with suggestions for future research as well as some personal recollections.
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/140-465-546-229-306 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.psy; differential emotions theory; emotions; personality development

Introduction: special section to honor carroll izard - Abe, Jo Ann A.; Schultz, David (Emotion Review, 2015)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/152-927-568-508-807 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.psy

Endogenous opioids as substrates for ethanol intake in the neonatal rat: The impact of prenatal ethanol exposure on the opioid family in the early postnatal period. - Bordner, Kelly; Deak, Terrence (Physiology & Behavior, 2015)
BACKGROUND: Despite considerable knowledge that prenatal ethanol exposure can lead to devastating effects on the developing fetus, alcohol consumption by pregnant women remains strikingly prevalent. Both clinical and basic research has suggested that, in addition to possible physical, behavioral, and cognitive deficits, gestational exposure to alcohol may lead to an increased risk for the development of later alcohol-related use and abuse disorders. The current work sought to characterize alterations in endogenous opioid signaling peptides and gene expression produced by ethanol exposure during the last days of gestation., METHODS: Experimental subjects were 4-, 8-, and 12-day old infant rats obtained from pregnant females that were given daily intubations of 0, 1, or 2g/kg ethanol during the last few days of gestation (GDs 17-20). Using real-time RT-PCR, western blotting analysis, and enzyme immunoassays, we examined mRNA and protein for three opioid receptors and ligands in the nucleus accumbens, ventral tegmental area, and hypothalamus., RESULTS: Three main trends emerged - (1) mRNA for the majority of factors was found to upregulate across each of the three postnatal ages assessed, indicative of escalating ontogenetic expression of opioid-related genes; (2) prenatal ethanol significantly reduced many opioid peptides, suggesting a possible mechanism by which prenatal exposure can affect future responsiveness towards ethanol; and (3) the nucleus accumbens emerged as a key site for ethanol-dependent effects, suggesting a potential target for additional assessment and intervention towards understanding the ethanol's ability to program the developing brain., CONCLUSION: We provide a global assessment of relatively long-term changes in both opioid gene expression and protein following exposure to only moderate amounts of ethanol during a relatively short window in the prenatal period. These results suggest that, while continuing to undergo ontogenetic changes, the infant brain is sensitive to prenatal ethanol exposure and that such exposure may lead to relatively long-lasting changes in the endogenous opioid system within the reward circuitry. These data indicate a potential mechanism and target for additional assessments of ethanol's ability to program the brain, affecting later responsiveness towards the drug. Copyright © 2015 Elsevier Inc. All rights reserved.
23 citations (Crossref) [2023-10-31] Place: United States Bordner, Kelly. Department of Psychology, Southern Connecticut State University, New Haven, CT 06515, United States; Behavioral Neuroscience Program, Department of Psychology, Binghamton University-SUNY, Binghamton, NY 13902, United States. Electronic address: bordnerk2@southernct.edu. Deak, Terrence. Behavioral Neuroscience Program, Department of Psychology, Binghamton University-SUNY, Binghamton, NY 13902, United States; Developmental Exposure Alcohol Research Center (DEARC), Center for Development and Behavioral Neuroscience, Binghamton University-SUNY, Binghamton, NY 13902, United States.
Keywords: *Alcohol Drinking/pp [Physiopathology]; *Central Nervous System Depressants/pd [Pharmacology]; *Ethanol/pd [Pharmacology]; *Gene Expression Regulation; Developmental/de [Drug Effects]; *Prenatal Exposure Delayed Effects/pp [Physiopathology]; *Receptors; Opioid/me [Metabolism]; Age Factors; Alcohol Drinking; Analysis of Variance; Animals; Animals; Newborn; Article; Brain; Brain/gd [Growth & Development]; Brain/me [Metabolism]; Central Nervous System Depressants; Dynorphins; Dynorphins/ge [Genetics]; Dynorphins/me [Metabolism]; Enkephalins; Enkephalins/ge [Genetics]; Enkephalins/me [Metabolism]; Ethanol; Female; Gene Expression Regulation; Developmental; Gestational Age; MRNA; Male; Ontogeny; Opioids; Pregnancy; Prenatal Exposure Delayed Effects; Pro-Opiomelanocortin; Pro-Opiomelanocortin/ge [Genetics]; Pro-Opiomelanocortin/me [Metabolism]; Protein; Protein Precursors; Protein Precursors/ge [Genetics]; Protein Precursors/me [Metabolism]; RNA; Messenger; RNA; Messenger/me [Metabolism]; Rat; Rats; Rats; Sprague-Dawley; Receptors; Opioid; Receptors; Opioid/ge [Genetics]; Sprague Dawley rat; Western blotting; age; alcohol; alcohol consumption; analysis of variance; animal; animal experiment; animal tissue; beta endorphin; brain; brain development; central depressant agent; controlled study; delta opiate receptor; dept.psy; drinking behavior; drug effects; dynorphin; endorphin; enkephalin; enzyme immunoassay; female; gene expression; gene expression regulation; genetics; gestation period; gestational age; growth; development and aging; hypothalamus; infant; kappa opiate receptor; male; messenger RNA; metabolism; mu opiate receptor; newborn; nonhuman; nucleus accumbens; ontogeny; opiate receptor; pathophysiology; peer-reviewed; perinatal period

Change in the hedonic value of an aversive stimulus in the presence of a pre-exposed odor. - Kamenetzky, Giselle V; Suarez, Andrea B; Pautassi, Ricardo M; Mustaca, Alba E; Nizhnikov, Michael E (Physiology & behavior, 2015)
Rats exhibit a sensitive period from the time of birth until postnatal day 10 during which they develop preferences for odors even if those odors are paired with a moderately aversive stimulus. It is still unknown whether pre-exposure to an odor produces alterations on intake responses of basic tastants, and on other patterns that indicate a change in the hedonic value of reward, such as nipple grasping behavior. The current study assessed the effect of pre-exposure to an odor immediately after birth on intake responses of appetitive and aversive tastants. The objectives were to assess if 3-hour-old rats adjust their behaviors to obtain different values of appetitive and aversive rewards in the presence of a familiar odor. Specifically we wanted to determine whether the intake of saccharin or quinine, administered through the artificial nipple, increases in the presence of the familiar odor. Results showed that 3-hour-old rats differentially respond to two different concentrations of saccharin and two concentrations of quinine. In the presence of the pre-exposed odor newborn rats increased intake and grasp responses to the artificial nipple containing quinine. This effect disappeared with a higher concentration of quinine. These results suggest that the pre-exposed odor generated a change in the hedonic value of the aversive reward. Copyright © 2014 Elsevier Inc. All rights reserved.
12 citations (Crossref) [2023-10-31] Place: United States Kamenetzky, Giselle V. Laboratorio de Psicologia Experimental y Aplicada, IDIM, CONICET, UBA, Centro de Altos Estudios en Ciencias Humanas y de la Salud (CAECIHS-UAI), Universidad Abierta Interamericana, Buenos Aires, Argentina. Electronic address: yoselevich@hotmail.com. Suarez, Andrea B. Laboratorio de Psicologia Experimental y Aplicada, IDIM, CONICET, UBA, Centro de Altos Estudios en Ciencias Humanas y de la Salud (CAECIHS-UAI), Universidad Abierta Interamericana, Buenos Aires, Argentina. Pautassi, Ricardo M. Instituto de Investigacion Medica Mercedes y Martin Ferreyra, CONICET, Universidad Nacional de Cordoba, Cordoba, Argentina. Mustaca, Alba E. Laboratorio de Psicologia Experimental y Aplicada, IDIM, CONICET, UBA, Centro de Altos Estudios en Ciencias Humanas y de la Salud (CAECIHS-UAI), Universidad Abierta Interamericana, Buenos Aires, Argentina. Nizhnikov, Michael E. Southern Connecticut State University, United States.
Keywords: *Avoidance Learning/ph [Physiology]; *Conditioning; Psychological/ph [Physiology]; *Discrimination; Psychological/ph [Physiology]; *Emotions/ph [Physiology]; *Odorants; *Smell/ph [Physiology]; Age Factors; Analgesics; Non-Narcotic; Animals; Animals; Newborn; Appetitive Behavior; Appetitive Behavior/ph [Physiology]; Article; Aversive solutions; Avoidance Learning; Conditioning (Psychology); Discrimination (Psychology); Dose-Response Relationship; Drug; Emotions; Female; Male; Newborn rats; Odors; Olfactory learning; Ontogeny; Quinine; Quinine/ad [Administration & Dosage]; Rats; Rats; Sprague-Dawley; Reaction Time; Reaction Time/de [Drug Effects]; Reaction Time/ph [Physiology]; Saccharin; Saccharin/ad [Administration & Dosage]; Smell; Sprague Dawley rat; Sweetening Agents; age; analgesic agent; animal; animal behavior; animal experiment; appetite; aversion; avoidance behavior; birth; bitter taste; conditioning; controlled study; dept.psy; dose response; drug effects; emotion; exposure; female; food intake; grip strength; gustatory system; male; newborn; nipple; nonhuman; odor; peer-reviewed; perceptive discrimination; physiology; priority journal; quinine; rat; reaction time; reward; saccharin; stimulus; sweetening agent; taste

Can low-level ethanol exposure during pregnancy influence maternal care? An investigation using two strains of rat across two generations. - Popoola, Daniel O; Borrow, Amanda P; Sanders, Julia E; Nizhnikov, Michael E; Cameron, Nicole M (Physiology & behavior, 2015)
Gestational alcohol use is well documented as detrimental to both maternal and fetal health, producing an increase in offspring's tendency for alcoholism, as well as in behavioral and neuropsychological disorders. In both rodents and in humans, parental care can influence the development of offspring physiology and behavior. Animal studies that have investigated gestational alcohol use on parental care and/or their interaction mostly employ heavy alcohol use and single strains. This study aimed at investigating the effects of low gestational ethanol dose on parental behavior and its transgenerational transmission, with comparison between two rat strains. Pregnant Sprague Dawley (SD) and Long Evans (LE) progenitor dams (F0) received 1g/kg ethanol or water through gestational days 17-20 via gavage, or remained untreated in their home cages. At maturity, F1 female offspring were mated with males of the same strain and treatment and were left undisturbed through gestation. Maternal behavior was scored in both generations during the first six postnatal days. Arch-back nursing (ABN) was categorized as: 1, when the dam demonstrated minimal kyphosis; 2, when the dam demonstrated moderate kyphosis; and 3, when the dam displayed maximal kyphosis. Overall, SD showed greater amounts of ABN than LE dams and spent more time in contact with their pups. In the F0 generation, water and ethanol gavage increased ABN1 and contact with pups in SD, behaviors which decreased in treated LE. For ABN2, ethanol-treated SD dams showed more ABN2 than water-treated dams, with no effect of treatment on LE animals. In the F1 generation, prenatal exposure affected retrieval. Transgenerational transmission of LG was observed only in the untreated LE group. Strain-specific differences in maternal behavior were also observed. This study provides evidence that gestational gavage can influence maternal behavior in a strain-specific manner. Our results also suggest that the experimental procedure during gestation and genetic variations between strains may play an important role in the behavioral effects of prenatal manipulations. Copyright © 2015 Elsevier Inc. All rights reserved.
16 citations (Crossref) [2023-10-31] Place: United States Popoola, Daniel O. Psychology Department, Center for Development and Behavioral Neuroscience, Binghamton University - SUNY, NY, USA. Borrow, Amanda P. Psychology Department, Center for Development and Behavioral Neuroscience, Binghamton University - SUNY, NY, USA. Sanders, Julia E. Psychology Department, Center for Development and Behavioral Neuroscience, Binghamton University - SUNY, NY, USA. Nizhnikov, Michael E. Psychology Department, Southern Connecticut State University, CT, USA. Cameron, Nicole M. Psychology Department, Center for Development and Behavioral Neuroscience, Binghamton University - SUNY, NY, USA. Electronic address: ncameron@binghamton.edu.
Keywords: *Central Nervous System Depressants/to [Toxicity]; *Ethanol/to [Toxicity]; *Maternal Behavior; *Prenatal Exposure Delayed Effects/ci [Chemically Induced]; Alcohol Drinking; Alcohol Drinking/pp [Physiopathology]; Analysis of Variance; Animals; Animals; Newborn; Article; Central Nervous System Depressants; Ethanol; Female; Grooming; Intragastric gavage; Long Evans rat; Male; Maternal Behavior; Maternal care; Posture; Pregnancy; Prenatal Exposure Delayed Effects; Prenatal Exposure Delayed Effects/nu [Nursing]; Prenatal Exposure Delayed Effects/pp [Physiopathology]; Rat; Rats; Rats; Long-Evans; Rats; Sprague-Dawley; Species Specificity; Sprague Dawley rat; Time Factors; Transgenerational; alcohol; alcohol consumption; analysis of variance; animal; animal experiment; animal model; body posture; central depressant agent; chemically induced; controlled study; dept.psy; drinking behavior; female; genetic variability; grooming; kyphosis; licking; male; maternal behavior; maternal care; mating; newborn; nonhuman; nursing; parental behavior; pathophysiology; peer-reviewed; pregnancy; prenatal exposure; priority journal; progeny; rat; species difference; time

Neural gene expression profiles and androgen levels underlie alternative reproductive tactics in the ocellated wrasse, symphodus ocellatus - Stiver, Kelly A.; Harris, Rayna M.; Townsend, Jeffrey P.; Hofmann, Hans A.; Alonzo, Suzanne H. (Ethology, 2014)
Discrete variation in reproductive behavior and physiology is observed in diverse taxa. Although it is known that most within-sex alternative reproductive tactics arise as a consequence of phenotypic plasticity, relatively little is known about differential neural gene expression among plastic alternative reproductive phenotypes. In the ocellated wrasse Symphodus ocellatus, males exhibit one of three alternative tactics (nesting, satellite, and sneaker) within a reproductive season, but switch tactics between years. Satellites and sneakers spawn parasitically in dominant (nesting) males' nests, but only nesting males provide parental care. Nesting and satellite males show transient cooperative defense of nests against sneakers. Here, we analyze circulating sex steroid hormone levels and neural gene expression profiles in these three male phenotypes and in females. 11-ketotestosterone (but not testosterone) was highest in nesting males, while estradiol was highest in females. Brain transcriptomes of satellites and females were most similar to each other and intermediate to nesting and sneaker males. Sneakers showed more total expression differences, whereas nesting males showed higher magnitude expression differences. Our findings reveal the surprising extent to which neural gene expression patterns vary across reproductive tactics that vary in a number of social traits, including aggression, territoriality, and cooperation, providing important insights into the molecular mechanisms that may underlie variation in cooperative and reproductive behavior. © 2014 Blackwell Verlag GmbH.
31 citations (Crossref) [2023-10-31] Citation Key Alias: pop00079 tex.type: [object Object]
Keywords: Androgens; Competition; Cooperation; Mating tactic; Microarray; Reproduction; Symphodus ocellatus; dept.psy

Rats' choices with token stimuli in concurrent variable- interval schedules - Mazur, James E. (Journal of the Experimental Analysis of Behavior, 2014)
Four rats responded on concurrent variable-interval schedules that delivered token stimuli (stimulus lights arranged vertically above each of two side levers). During exchange periods, each token could be exchanged for one food pellet by responding on a center lever, with one response required for each pellet delivery. In different conditions, the exchange requirements (number of tokens that had to be earned before they could be exchanged for food) varied between one and four for the two response levers. The experiments were closely patterned after research with pigeons by Mazur and Biondi (), and the results from the rats in the present experiment were similar. Response percentages on the two levers changed as each additional token was earned, and these patterns indicated that choice was controlled by both the time to the exchange periods and the number of food pellets that were delivered in the exchange period. In some conditions, the exchange requirement was three tokens for each lever, but the token lights were not turned on as they were earned for one of the two keys. The rats showed a slight preference for the lever without the token lights, which may indicate that the token lights were not serving as conditioned reinforcers (a result also found by Mazur and Biondi with pigeons). Overall, these results suggest that, in this choice procedure, the token stimuli served primarily as discriminative stimuli that signaled the temporal proximity and quantity of the primary reinforcer, food.
0 citations (Crossref) [2023-10-31] tex.eissn: 1938-3711 tex.researcherid-numbers: Mazur, James/AAA-6971-2019 tex.unique-id: ISI:000341714000004
Keywords: Animals; Choice Behavior; Concurrent variable-interval schedules; Conditioned reinforcers; Conditioning; Operant; Cues; Discriminative stimuli; Hyperbolic discounting; Lever press; Long Evans rat; Male; Rats; Rats; Long-Evans; Reinforcement Schedule; Token Economy; Token stimuli; animal; association; decision making; dept.psy; instrumental conditioning; male; peer-reviewed; rat; reinforcement

Hope, will, purpose, competence, and fidelity: ego strengths as predictors of career identity - Anthis, Kristine (Identity, 2014)
This correlational study examined the relationships among ego strengths and career identity. Self-report data were collected from a sample of university undergraduates (N = 239). Participants completed the Psychosocial Inventory of Ego Strengths and the Vocational Identity Status Assessment. The results revealed gender differences, primarily in career identity. The findings also showed that the unique variance explained in career identity by each ego strength was modest, indicating that the best predictor of career identity is the overall level of ego strengths. Suggestions for future research, such as longitudinal designs to establish ego strengths as developmental precursors of career identity, are provided. © 2014 Copyright Taylor & Francis Group, LLC.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/002-943-105-701-206 tex.type: [object Object]
Keywords: dept.psy

Adaptation and Sexual Offending - Camilleri, Joseph A.; Stiver, Kelly A. (Evolutionary Perspectives on Human Sexual Psychology and Behavior, 2014)
Agreement on the causes of sexual offending has eluded scholars because of an emphasis on studying proximate causes—as with crime in general, there are numerous variables that correlate with sexual offending. A more consilient view of sexual offending includes an evolutionary approach that attempts to answer ultimately why such behavior exists. To guide this research, Camilleri (The Oxford handbook of evolutionary perspectives on violence, homicide, and war, New York, 173–196) proposed a typology of sexual offenders that classifies offending based on two dimensions: (1) whether the behavior is an adaptation, by-product, or disorder and (2) if the mechanism is obligate or facultative. Categories resulting from this typology seem to capture the variability of sexual offending behavior. This chapter mostly reviews evidence of how sexual offending could function as an adaptation, draws links from nonhuman behavior literature, and briefly reviews alternative explanations, including by-products and disorders.
Citation Key Alias: lens.org/022-262-555-836-521
Keywords: Antisocial Behavior; Nonhuman Animal; Psychopathic Trait; Sexual Coercion; Sexual Offender; dept.psy

Brief prenatal ethanol exposure alters behavioral sensitivity to the kappa opioid receptor agonist (U62,066E) and antagonist (Nor‐BNI) and reduces kappa opioid receptor expression - Nizhnikov, Michael E; Pautassi, Ricardo Marcos; Carter, Jenna M; Landin, Justine D; Varlinskaya, Elena I; Bordner, Kelly A; Werner, David F; Spear, Norman E (Alcoholism: Clinical and Experimental Research, 2014)
Background: Approximately 10 to 15% of women consume alcohol (ethanol [EtOH]) during pregnancy in the United States. Even low amounts of EtOH consumption during pregnancy can elicit long-term consequences. Prenatal experience with as few as 3 drinks has been associated with increase problem drinking in adulthood. Such effects are corroborated in rodents; however, the underlying neural adaptations contributing to this effect are not clear. In the current set of experiments, we investigated whether changes in EtOH responding following prenatal EtOH exposure involved kappa opioid receptor activation and expression. Methods: Sprague-Dawley rats were prenatally exposed to low levels of alcohol (1.0 g/kg) during late gestation (gestational days 17 to 20 [GD17-20]) via intragastric intubation of pregnant dams. Following birth, EtOH intake, kappa- and mu-opioid-induced place conditioning, and kappa opioid receptor expression in mesolimbic brain regions were assessed in infant rats (postnatal days 14 to 15 [PD14-15]) that were offspring of dams given EtOH, vehicle, or untreated, during pregnancy. Results: Animals exposed to prenatal alcohol drank more alcohol later in life and exhibited significant changes in the kappa opioid system. While control subjects found kappa opioid activation aversive, animals exposed to EtOH prenatally exhibited either no aversion or appetitive responding. Further analysis revealed that synaptosomal kappa opioid receptor expression was significantly decreased in brain areas implicated in responding to EtOH. Conclusions: Overall, these data suggest that prenatal EtOH affects kappa opioid function and expression and that these changes may be involved in increased drinking later in life. © 2014 by the Research Society on Alcoholism.
31 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/047-356-148-046-471 tex.type: [object Object]
Keywords: Alcohol Drinking; Animals; Brain Chemistry; Conditioning (Psychology); Ethanol; Female; Gene Expression; Infant; Kappa; Male; Naltrexone; Opioid; Pregnancy; Prenatal Exposure Delayed Effects; Pyrrolidines; Rats; Rats; Sprague-Dawley; Receptors; Opioid; kappa; Sprague Dawley rat; Western blotting; agonists; alcohol; alcohol abuse; alcohol consumption; analogs and derivatives; animal; animal experiment; animal tissue; antagonists and inhibitors; article; behavioral science; biosynthesis; brain level; chemically induced; conditioning; controlled study; dept.psy; drinking behavior; drug effects; drug therapy; female; fluid intake; gene expression; gestation period; kappa opiate receptor; kappa opiate receptor antagonist; limbic cortex; male; metabolism; naltrexone; nonhuman; nor bni; norbinaltorphimine; pregnancy; prenatal exposure; priority journal; protein expression; pyrrolidine derivative; rat; spiradoline; spiradoline mesilate; unclassified drug

Development of phonological constancy: 19-Month-Olds, but not 15-Month-Olds, identify words in a non-native regional accent - Mulak, Karen E.; Best, Catherine T.; Tyler, Michael D.; Kitamura, Christine; Irwin, Julia R. (Child Development, 2013)
By 12months, children grasp that a phonetic change to a word can change its identity (phonological distinctiveness). However, they must also grasp that some phonetic changes do not (phonological constancy). To test development of phonological constancy, sixteen 15-month-olds and sixteen 19-month-olds completed an eye-tracking task that tracked their gaze to named versus unnamed images for familiar words spoken in their native (Australian) and an unfamiliar non-native (Jamaican) regional accent of English. Both groups looked longer at named than unnamed images for Australian pronunciations, but only 19-month-olds did so for Jamaican pronunciations, indicating that phonological constancy emerges by 19months. Vocabulary size predicted 15-month-olds' identifications for the Jamaican pronunciations, suggesting vocabulary growth is a viable predictor for phonological constancy development.
55 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/034-753-306-501-490 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Acoustic Stimulation; Female; Fixation; Ocular; Humans; Infant; Language Development; Male; Perceptual Masking; Phonetics; Psychomotor Performance; Recognition (Psychology); Speech Perception; Vocabulary; article; auditory stimulation; dept.psy; eye fixation; female; human; infant; language development; linguistics; male; perception; phonetics; physiology; psychomotor performance; recognition; speech perception

Pigeons' choices with token stimuli in concurrent variable-interval schedules: concurrent vi schedules with tokens - Mazur, James E; Biondi, Dawn R (Journal of the Experimental Analysis of Behavior, 2013)
Twelve pigeons responded on concurrent variable-interval schedules that delivered token stimuli (stimulus lights for some pigeons, and white circles on the response keys for others). During exchange periods, each token could be exchanged for food on a fixed-ratio 1 schedule. Across conditions, the exchange requirements ( number of tokens that had to be earned before they could be exchanged for food) varied between one and four for the two response keys. The main findings were that the pigeons' response percentages varied as a function of the number of tokens earned at any given moment, and they were determined by both the delays to food and by the number of food deliveries in the exchange periods. In some conditions, tokens had to be earned but were not visible during the variable-interval schedules for one or both keys. When one key had visible tokens and the other did not, the pigeons showed a preference for the key without visible tokens. A model based on the matching law and a hyperbolic delay-discounting equation could account for the main patterns of choice responding, and for how response percentages changed as successive tokens were earned. The results are consistent with the view that the token stimuli served as discriminative stimuli that signaled the current delays to food.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/055-953-404-245-599, lens.org/132-483-465-914-642 tex.type: [object Object]
Keywords: *Choice Behavior; *Token Economy; Animals; Columbidae; Concurrent variable-interval schedules; Conditioning; Operant; Generalized matching law; Hyperbolic discounting; Keypeck; Male; Models; Psychological; Pigeons; Reinforcement Schedule; Token stimuli; dept.psy; peer-reviewed

Assessment Criteria Indicative of Deception: An Example of the New Paradigm of Differential Recall Enhancement - Colwell, Kevin; Hiscock-Anisman, Cheryl; Fede, Jacquelyn (Applied Issues in Investigative Interviewing, Eyewitness Memory, and Credibility Assessment, 2013)
The present chapter details the historical and conceptual evolution of a new paradigm in statement analysis that has developed over the past 20 years. There has been an increasing awareness of the importance of interviewing designed to facilitate the detection of deception as a necessary component of statement analysis (Colwell, Hiscock, & Memon, 2002; Hartwig & Bond, 2011; Hernández-Fernaud & Alonso-Quecuty, 1997; Koehnken, Schimossek, Ascherman, & Hofer, 1995; Vrij, Fisher, Mann, & Leal, 2006). Subsequently, the work of multiple researchers has created a zeitgeist that has nurtured and informed the development of this new paradigm. This chapter begins by providing a quick overview of the various lines of research that comprise this paradigm. Attention is then given to credibility assessment and statement content criteria that discriminate honest from deceptive responding. Then, the focus is on strategies of impression management and the subjective experience of respondents during an investigative interview. This sets the stage for a discussion of investigative interviewing structure and techniques that facilitate the detection of deception through the process of differential recall enhancement (DRE: Colwell et al., 2012). Finally, this chapter considers in detail an approach to interviewing and assessment that is representative of the new paradigm.
Citation Key Alias: lens.org/131-463-202-689-32X
Keywords: Content Criterion; Free Recall; Impression Management; Present Volume; Target Event; dept.psy

Sharing of potential nest sites by Etheostoma olmstedi males suggests mutual tolerance in an alloparental species. - Stiver, Kelly A; Wolff, Stephen H; Alonzo, Suzanne H (PloS one, 2013)
When reproductive competitors tolerate or cooperate with one another, they may gain particular benefits, such as collectively guarding resources or attracting mates. Shared resources may be those essential to reproduction, such as a breeding site or nest. Using the tessellated darter, a species where males but not females compete over potential nest sites, we examined site use and sharing under controlled conditions of differing competitor density. Sharing was observed even when competitor density was low and individuals could have each occupied a potential nest site without same-sex sharing. Males were more likely to share a nest site with one other when the difference in size between them was larger rather than smaller. There was no evidence that female sharing was dependent on their relative size. Fish were generally more likely to use and share larger sites, in accordance with the greater relative surface area they offered. We discuss how one or both sharing males may potentially benefit, and how male sharing of potential nest sites could relate to female mating preferences. Tessellated darter males are known to provide alloparental care for eggs but this occurs without any social contact between the alloparent and the genetic father of the young. Thus, the suggestion that they may also share sites and maintain social contact with reproductive competitors highlights the importance of increased focus on the potential complexity of reproductive systems.
6 citations (Crossref) [2023-10-31] Place: United States Stiver, Kelly A. Psychology Department, Southern Connecticut State University, New Haven, Connecticut, USA. stiverk1@southernct.edu
Keywords: *Behavior; Animal; *Nesting Behavior; *Perches/ph [Physiology]; *Reproduction; Animals; Behavior; Animal; Etheostoma olmstedi; Female; Male; Nesting Behavior; Perches; Reproduction; Sexual Behavior; Animal; animal behavior; article; competitor species; controlled study; dept.psy; female; fish; male; male animal; mate choice; nesting; nonhuman; peer-reviewed; population density; population size; sex difference; social behavior; symbiosis

Maternal separation with early weaning: A rodent model providing novel insights into neglect associated developmental deficits - Carlyle, Becky C.; Duque, Alvaro; Kitchen, Robert R.; Bordner, Kelly A.; Coman, Daniel; Doolittle, Eliza; Papademetris, Xenophonios; Hyder, Fahmeed; Taylor, Jane R.; Simen, Arthur A. (Development and Psychopathology, 2012)
Child neglect is the most prevalent form of child maltreatment in the United States, and poses a serious public health concern. Children who survive such episodes go on to experience long-lasting psychological and behavioral problems, including higher rates of post-traumatic stress disorder symptoms, depression, alcohol and drug abuse, attention-deficit/hyperactivity disorder, and cognitive deficits. To date, most research into the causes of these life-long problems has focused on well-established targets such as stress responsive systems, including the hypothalamus-pituitary-adrenal axis. Using the maternal separation and early weaning model, we have attempted to provide comprehensive molecular profiling of a model of early-life neglect in an organism amenable to genomic manipulation: the mouse. In this article, we report new findings generated with this model using chromatin immunoprecipitation sequencing, diffuse tensor magnetic resonance imaging, and behavioral analyses. We also review the validity of the maternal separation and early weaning model, which reflects behavioral deficits observed in neglected humans including hyperactivity, anxiety, and attentional deficits. Finally, we summarize the molecular characterization of these animals, including RNA profiling and label-free proteomics, which highlight protein translation and myelination as novel pathways of interest.
66 citations (Crossref) [2023-10-31] tex.eissn: 1469-2198 tex.orcid-numbers: Hyder, Fahmeed/0000-0001-7822-4002 Carlyle, Becky/0000-0003-1491-3217 tex.researcherid-numbers: Hyder, Fahmeed/A-2644-2015 tex.unique-id: ISI:000309925800019
Keywords: Animals; Anxiety; Attention; Behavior; Animal; Brain; C57BL mouse; Child; Child Abuse; Chromatin Immunoprecipitation; Developmental Disabilities; Diffusion Tensor Imaging; Disease Models; Animal; Epigenesis; Genetic; Humans; Maternal Deprivation; Mice; Mice; Inbred C57BL; Prefrontal Cortex; Proteomics; RNA; Weaning; animal; animal behavior; anxiety; article; attention; brain; child; child abuse; chromatin immunoprecipitation; dept.psy; developmental disorder; diffusion tensor imaging; disease model; genetic epigenesis; genetics; human; maternal deprivation; metabolism; mouse; pathophysiology; peer-reviewed; prefrontal cortex; proteomics; psychological aspect; weaning

Choice behavior of pigeons (Columba livia), college students, and preschool children (Homo sapiens) in the Monty Hall dilemma. - Mazur, James E; Kahlbaugh, Patricia E (Journal of Comparative Psychology, 2012)
In the Monty Hall dilemma, an individual chooses between three options, only one of which will deliver a prize. After the initial choice, one of the nonchosen options is revealed as a losing option, and the individual can choose to stay with the original choice or switch to the other remaining option. Previous studies have found that most adults stay with their initial choice, although the chances of winning are 2/3 for switching and 1/3 for staying. Pigeons, college students, and preschool children were given many trials on this task to examine how their choices might change with experience. The college students began to switch on a majority of trials much sooner than the pigeons, contrary to the findings by Herbranson and Schroeder (2010) that pigeons perform better than people on this task. In all three groups, some individuals approximated the optimal strategy of switching on every trial, but most did not. Many of the preschoolers immediately showed a pattern of always switching or always staying and continued this pattern throughout the experiment. In a condition where the probability of winning was 90% after a switch, all college students and all but one pigeon learned to switch on nearly every trial. The results suggest that one main impediment to learning the optimal strategy in the Monty Hall task, even after repeated trials, is the difficulty in discriminating the different reinforcement probabilities for switching versus staying.
10 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Department of Psychology, Southern Connecticut State University, New Haven, CT 06515, USA. mazurj1@southernct.edu
Keywords: *Choice Behavior; *Columbidae; Adolescent; Animals; Child; Preschool; Choice Behavior; College students; Columbidae; Female; Games; Experimental; Humans; Male; Monty hall dilemma; Pigeons; Preschool children; Probability; Reinforcement Schedule; Reinforcement probability; Reward; Students; Students/px [Psychology]; Young Adult; adolescent; adult; animal; article; decision making; dept.psy; female; game; human; male; pigeons and doves; preschool child; probability; psychological aspect; reinforcement; reward; student

What lexical decision and naming tell us about reading - Katz, Leonard; Brancazio, Larry; Irwin, Julia; Katz, Stephen; Magnuson, James; Whalen, D. H. (Reading and Writing, 2012)
The lexical decision (LD) and naming (NAM) tasks are ubiquitous paradigms that employ printed word identification. They are major tools for investigating how factors like morphology, semantic information, lexical neighborhood and others affect identification. Although use of the tasks is widespread, there has been little research into how performance in LD or NAM relates to reading ability, a deficiency that limits the translation of research with these tasks to the understanding of individual differences in reading. The present research was designed to provide a link from LD and NAM to the specific variables that characterize reading ability (e.g., decoding, sight word recognition, fluency, vocabulary, and comprehension) as well as to important reading-related abilities (phonological awareness and rapid naming). We studied 99 adults with a wide range of reading abilities. LD and NAM strongly predicted individual differences in word identification, less strongly predicted vocabulary size and did not predict comprehension. Fluency was predicted but with differences that depended on the way fluency was defined. Finally, although the tasks did not predict individual differences in rapid naming or phonological awareness, the failures nevertheless assisted in understanding the cognitive mechanisms behind these reading-related abilities. The results demonstrate that LD and NAM are important tools for the study of individual differences in reading.
39 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/048-008-052-505-413 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Lexical decision; Naming; RT; Reading ability; dept.hls; dept.psy; peer-reviewed

Cognitive-affective styles associated with position on war - Abe, Jo Ann A. (Journal of Language and Social Psychology, 2012)
This study examined cognitive-affective styles associated with position on the Iraq war by analyzing responses posted on an online discussion forum using a computerized text-analysis program (Linguistic Inquiry and Word Count). Overall, the results were consistent with those obtained in narrative-coding studies. The pro-war group was associated with an external focus and a simplistic style of information processing. The anti-war group was associated with an internal focus and high levels of cognitive processing and negative emotion words. The “neither” group scored the highest on cognitive complexity and positive emotion words, and it was also the most balanced in terms of internal and external focus.
22 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/059-657-472-642-587 tex.unique-id: [object Object]
Keywords: Linguistic Inquiry and Word Count (LIWC); affective style; attitudes toward Iraq War; cognitive style; dept.psy; peer-reviewed

Eye movement dynamics and cognitive self-organization in typical and atypical development - Mirman, Daniel; Irwin, Julia R.; Stephen, Damian G. (Cognitive Neurodynamics, 2012)
This study analyzed distributions of Euclidean displacements in gaze (i.e. “gaze steps”) to evaluate the degree of componential cognitive constraints on audio-visual speech perception tasks. Children performing these tasks exhibited distributions of gaze steps that were closest to power-law or lognormal distributions, suggesting a multiplicatively interactive, flexible, self-organizing cognitive system rather than a component-dominant stipulated cognitive structure. Younger children and children diagnosed with an autism spectrum disorder (ASD) exhibited distributions that were closer to power-law than lognormal, indicating a reduced degree of self-organized structure. The relative goodness of lognormal fit was also a significant predictor of ASD, suggesting that this type of analysis may point towards a promising diagnostic tool. These results lend further support to an interaction-dominant framework that casts cognitive processing and development in terms of self-organization instead of fixed components and show that these analytical methods are sensitive to important developmental and neuropsychological differences.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/129-377-170-010-77X tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Autism; Development; Eye movements; Interaction-dominance; Self-organization; article; autism; cognition; dept.psy; eye movement; human; neuropsychology; speech perception

Teaching professionals to detect deception: the efficacy of a brief training workshop - Colwell, Lori H.; Colwell, Kevin; Hiscock-Anisman, Cheryl; Hartwig, Maria; Cole, Lindsey D.; Werdin, Kathryn; Youschak, Kimberly E. (Journal of Forensic Psychology Practice, 2012)
Despite the importance of credibility assessments in forensic settings, research shows that forensic professionals are mediocre at this task. This study tested the efficacy of a 2.5-hour training workshop on Assessment Criteria Indicative of Deception (ACID), a system of investigative interviewing and credibility assessment using verbal content analysis, in a sample of 99 forensic professionals at a maximum-security forensic hospital in the United States. Accuracy in detecting deception was assessed before and after training via written transcripts. Results showed that training improved participants' accuracy, with accuracy rates increasing from 61% to 70%. Implications of the findings and recommendations for future research are discussed.
9 citations (Crossref) [2023-10-31] Citation Key Alias: pop00268 tex.type: [object Object]
Keywords: United States; accuracy; adult; article; assessment criterion indicative of deception; clinical assessment tool; deception; deception detection; dept.psy; female; hospital; human; male; nursing staff; psychiatrist; psychologist; registered nurse; social worker; training; verbal cues; vocational education; workshop

A latent class analysis of DSM-IV alcohol use disorder criteria and binge drinking in undergraduates - Beseler, Cheryl L.; Taylor, Laura A.; Kraemer, Deborah T.; Leeman, Robert F. (Alcoholism-Clinical and Experimental Research, 2012)
Background: Adolescent and adult samples have shown that the Diagnostic and Statistical Manual of Mental Disorders-IV (DSM-IV) abuse and dependence criteria lie on a continuum of alcohol problem severity, but information on criteria functioning in college students is lacking. Prior factor analyses in a college sample (Beseler et al., 2010) indicated that a 2-factor solution fit the data better than a single-factor solution after a binge drinking criterion was included. The second dimension may indicate a clustering of criteria related to excessive alcohol use in this college sample. Methods: The present study was an analysis of data from an anonymous, online survey of undergraduates (N = 361) that included items pertaining to the DSM-IV alcohol use disorder (AUD) diagnostic criteria and binge drinking. Latent class analysis (LCA) was used to determine whether the criteria best fit a categorical model, with and without a binge drinking criterion. Results: In an LCA including the AUD criteria only, a 3-class solution was the best fit. Binge drinking worsened the fit of the models. The largest class (class 1, n = 217) primarily endorsed tolerance (18.4%); none were alcohol dependent. The middle class (class 2, n = 114) endorsed primarily tolerance (81.6%) and drinking more than intended (74.6%); 34.2% met criteria for dependence. The smallest class (class 3, n = 30) endorsed all criteria with high probabilities (30 to 100%); all met criteria for dependence. Alcohol consumption patterns did not differ significantly between classes 2 and 3. Class 3 was characterized by higher levels on several variables thought to predict risk of alcohol-related problems (e. g., enhancement motives for drinking, impulsivity, and aggression). Conclusions: Two classes of heavy-drinking college students were identified, one of which appeared to be at higher risk than the other. The highest risk group may be less likely to “mature out” of high-risk drinking after college.
39 citations (Crossref) [2023-10-31] tex.eissn: 1530-0277 tex.unique-id: ISI:000298730200018
Keywords: Adolescent; Alcohol Typology; Alcohol Use Disorders; Alcohol-Related Disorders; College Students; Cross-Sectional Studies; Diagnostic and Statistical Manual of Mental Disorders; Ethanol; Female; Health Surveys; Humans; Impulsivity; Latent Class Analysis; Male; Risk Factors; Students; Universities; Young Adult; adult; aggression; alcohol consumption; alcohol use disorder criterion; alcoholism; article; binge drinking; clinical assessment tool; college student; controlled study; dept.psy; diagnostic and statistical manual of mental disorders; disease severity; drinking behavior; female; human; impulsiveness; major clinical study; male; motivation; priority journal; psychological model; undergraduate student

Scaffolding: Relationships among online quiz parameters and classroom exam scores - Anthis, Kristine; Adams, Lisa (Teaching of Psychology, 2012)
The current study examined relationships among online quiz parameters and students' classroom exam scores. The authors analyzed data from undergraduate courses across four semesters. The results revealed that regardless of the different parameters set for the online quizzes, the number of attempts that students made on quizzes was unrelated to their classroom exam scores, yet the amount of time they spent on quizzes was correlated negatively with their classroom exam scores. The results also revealed that students' scores on the online quizzes predicted their classroom exam scores, above and beyond the number of attempts, length of time allowed on quizzes, as well as their SAT Reading and SAT Math scores. The implications of these results are discussed subsequently. Future researchers may wish to provide empirical evidence on how not counting all of students' online quiz scores toward their final grade may influence students' quiz performance, given the anxiety that time limits can foster.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/167-128-998-329-431 tex.type: [object Object]
Keywords: attempts; dept.psy; exam scores; online quizzes; time limits

Effects of pre-trial response requirements on self-control choices by rats and pigeons. - Mazur, James E (Journal of the experimental analysis of behavior, 2012)
Parallel experiments with rats and pigeons examined whether the size of a pre-trial ratio requirement would affect choices in a self-control situation. In different conditions, either 1 response or 40 responses were required before each trial. In the first half of each experiment, an adjusting-ratio schedule was used, in which subjects could choose a fixed-ratio schedule leading to a small reinforcer, or an adjusting-ratio schedule leading to a larger reinforcer. The size of the adjusting ratio requirement was increased and decreased over trials based on the subject's responses, in order to estimate an indifference point-a ratio at which the two alternatives were chosen about equally often. The second half of each experiment used an adjusting-delay procedure-fixed and adjusting delays to the small and large reinforcers were used instead of ratio requirements. In some conditions, particularly with the reinforcer delays, the rats had consistently longer adjusting delays with the larger pre-trial ratios, reflecting a greater tendency to choose the larger, delayed reinforcer when more responding was required to reach the choice point. No consistent effects of the pre-trial ratio were found for the pigeons in any of the conditions. These results may indicate that rats are more sensitive to the long-term reinforcement rates of the two alternatives, or they may result from a shallower temporal discounting rate for rats than for pigeons, a difference that has been observed in previous studies.
10 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Psychology Department, Southern Connecticut State University, New Haven, CT 06515, USA. mazurj1@southernct.edu
Keywords: *Choice Behavior; *Conditioning; Operant; *Reinforcement Schedule; Animals; Choice Behavior; Columbidae; Conditioning; Operant; Long Evans rat; Male; Rats; Rats; Long-Evans; Reinforcement Schedule; animal; article; decision making; dept.psy; instrumental conditioning; male; peer-reviewed; pigeons and doves; rat; reinforcement

Positive emotions, emotional intelligence, and successful experiential learning - Abe, Jo Ann A. (Personality and Individual Differences, 2011)
This study explored the role that positive emotions and emotional intelligence play in experiential learning. Students' field practicum journals were analyzed using the Linguistic Inquiry and Word Count Program (LIWC) and a measure of emotional intelligence was obtained using the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT). Positive emotion words were robustly associated with almost all dimensions of supervisors' ratings of students' performance, but showed weak associations with students' ratings of perceived benefits associated with their practicum experiences. Overall El scores were correlated with several of the supervisor rating items and the Facilitating Thought and Managing Emotions subscales of the El were robustly correlated with many of the student rating items. This study thus yielded a more differentiated view of the role of positive emotions and emotional intelligence in adaptive functioning and underscored the importance of using multiple informants to assess a complex construct such as successful experiential learning. (C) 2011 Elsevier Ltd. All rights reserved.
46 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/031-469-367-529-721 tex.unique-id: [object Object]
Keywords: Emotional intelligence; Experiential learning; LIWC; MSCEIT; Positive emotions; dept.psy

Functional activation for imitation of seen and heard speech - Irwin, Julia R.; Frost, Stephen J.; Mencl, W. Einar; Chen, Helen; Fowler, Carol A. (Journal of Neurolinguistics, 2011)
This study examined fMRI activation when perceivers either passively observed or observed and imitated matched or mismatched audiovisual (”McGurk”) speech stimuli. Greater activation was observed in the inferior frontal gyrus (IFG) overall for imitation than for perception of audiovisual speech and for imitation of the McGurk-type mismatched stimuli than matched audiovisual stimuli. This unique activation in the IFG during imitation of incongruent audiovisual speech may reflect activation associated with direct matching of incongruent auditory and visual stimuli or conflict between category responses. This study provides novel data about the underlying neurobiology of imitation and integration of AV speech. (C) 2011 Elsevier Ltd. All rights reserved.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/171-648-177-093-410 tex.unique-id: [object Object]
Keywords: Audiovisual; FMRI; Imitation; McGurk effect; Speech perception; Speech production; adult; article; auditory stimulation; brain function; brain region; controlled study; dept.psy; female; functional magnetic resonance imaging; human; human experiment; inferior frontal gyrus; male; priority journal; speech discrimination; speech perception; superior temporal gyrus; task performance; visual stimulation

Effects of neurofibromatosis type 1 on children's development - Haynes, Norris M.; Kirwan, Jacqueline R.; McCrohan, Kelly (Social Work in Public Health, 2011)
In-depth study of the human genome holds the potential to provide needed focus on genetic disorders that affect hundreds of thousands of children and significantly affect their development. Neurofibromatosis Type-1 (NF-1) is one of the most common genetic disorders that affect neurological, cognitive, social, and physical development. NF-1 affects all racial groups and both genders equally. NF-1 occurs in about 1 in 2,500 to 3,300 individuals in the population. The incidence rate at birth is about 0.0004 births in the United States and is growing in prevalence. Children with NF-1 experience a range of psychomotor and cognitive impairments that affect the quality of their social lives and their learning and academic achievements. Interventions to address the psychosocial and educational needs of children with NF-1 include a range of social and academic support services, which are most effective when they are comprehensive, involve a multidisciplinary team of educational and health experts, and include a focus on supporting and empowering family members to be effective caregivers. Efforts to address the needs of children with NF-1 and to provide adequate support to their families have significant policy implications for local, state, and federal officials.
1 citations (Crossref) [2023-10-31] Citation Key Alias: pop00264 tex.type: [object Object]
Keywords: *Child Development; *Genome; Human; *Neurofibromatosis 1/px [Psychology]; *School Health Services; Adolescent; Adult; Aged; Child; Child Development; Child Welfare; Child; Preschool; Emotions; Female; Genome; Human; Humans; Infant; Infant; Newborn; Male; Middle Aged; Neurofibromatosis; Neurofibromatosis 1; Neurofibromatosis 1/di [Diagnosis]; Neurofibromatosis 1/ep [Epidemiology]; Neurofibromatosis 1/ge [Genetics]; Patient Education as Topic; Power (Psychology); Power; Psychological; Prevalence; Risk Factors; School Health Services; Social Change; Social Work; United States; United States/ep [Epidemiology]; Young Adult; adolescent; adult; aged; article; behavior; birth rate; child; child development; child health; child welfare; cognition; dept.psy; disease incidence; disease prevalence; emotion; family empowerment; female; genetics; genome; heritability; human; human genome; infant; male; mental health; middle aged; neurofibromatosis; newborn; patient education; peer-reviewed; preschool child; prevalence; psychological aspect; psychology; risk factor; school health service; school psychologists; school-based interventions; social and emotional development; social change; social policy; social work

Augmenting acid with affective details to assess credibility - Ansarra, Ryan; Colwell, Kevin; Hiscock-Anisman, Cheryl; Hines, Amber; Fleck, Roland; Cole, Lindsey; Belarde, Delyana (European Journal of Psychology Applied to Legal Context, 2011)
There is a need within the criminal justice systems of many countries to create a valid and applicable system of investigative interviewing and credibility assessment. The present study assesses the general validity one such system, called Assessment Criteria Indicative of Deception (ACID). ACID comprises interviewing strategies that facilitate the detection of deception and content criteria that highlight differences in verbal behavior. Sixty university undergraduates performed a staged theft under time pressure and with incentives designed to increase external validity. The participants were interviewed and assessed using the ACID procedure. Half of them were instructed to answer honestly and the other half to deny his/her participation in the theft. Results showed that honest statements were longer, more vividly detailed, and more spontaneously structured than deceptive statements. Also, the addition of affective details as a dependent measure significantly improved the ACID system. Overall, 48 of 60 statements were accurately classified (26 of 30 honest statements and 22 of 30 deceptive statements). The ACID procedure was effective and benefited from the addition of affective details. The strengths and weaknesses of this study are discussed in light of basic research into deception and potential forensic application.
tex.unique-id: ISI:000306783700004
Keywords: Content analysis; Credibility assessment; Detecting deception; Investigative interviewing; Testimony; dept.psy; ⛔ No DOI found

Changes in alan greenspan's language use across the economic cycle: A text analysis of his testimonies and speeches - Abe, Jo Ann A. (Journal of Language and Social Psychology, 2011)
This study examined changes in Alan Greenspan's language use across the economic cycle by analyzing his testimonies and speeches using the Linguistic Inquiry and Word Count Program (LIWC), which is a widely used text analysis program. Consistent with expectations, Greenspan showed an increase in the composite measure of psychological distancing as well as a decline in the measure of cognitive complexity between the economic expansion and downturn periods. Interestingly, these patterns of changes became more pronounced during the purported economic recovery period. In contrast to the measures of psychological distancing and cognitive complexity, the measure of emotionality remained relatively stable across the economic cycle.
37 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/132-038-801-626-709 tex.unique-id: [object Object]
Keywords: Greenspan; LIWC; cognitive complexity; computerized text analysis; dept.psy; peer-reviewed; psychological distancing

Effect of night smoking, sleep disturbance, and their co-occurrence on smoking outcomes - Peters, Erica N.; Fucito, Lisa M.; Novosad, Claire; Toll, Benjamin A.; O'Malley, Stephanie S. (Psychology of Addictive Behaviors, 2011)
Recent evidence suggests that smoking during the night is an indicator of nicotine dependence and predicts smoking cessation failure. Night smokers are likely to experience disturbance to their sleep cycle when they wake to smoke, but we are not aware of the prevalence of night smokers' self-reported sleep disturbance. Because sleep disturbance also predicts smoking cessation failure, we examined how the pre-cessation risk factors of night smoking and sleep disturbance, and their co-occurrence, predict smoking cessation failure in a 6-week double-blind randomized controlled trial examining whether naltrexone augments the efficacy of the nicotine patch (O'Malley et al., 2006). Smokers (N = 385) completed the Pittsburgh Sleep Quality Index (Buysse, Reynolds, Monk, Berman, & Kupfer, 1989) and a single item of waking at night to smoke pre-cessation. Smoking status was determined at weeks 1, 6, 24, and 48 weeks after quitting. The two main findings were: (a) night smokers reported significantly greater sleep disturbance than nonnight smokers; and (b) smokers with co-occurring night smoking and sleep disturbance experienced significantly greater risk for smoking than smokers with neither risk factor. Results suggest that individuals who both wake during the night to smoke and report clinically-significant sleep disturbance represent a high-risk group of smokers. Future smoking cessation treatment might incorporate strategies related to managing these smokers' sleep habits and physiological dependence on nicotine in order to bolster their cessation outcomes.
41 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-028-794-958-718 tex.unique-id: [object Object]
Keywords: Adult; Double-Blind Method; Female; Humans; Male; Middle Aged; Night smoking; Outcome predictors; Pittsburgh Sleep Quality Index; Prevalence; Self Report; Sleep Disorders; Sleep disturbance; Smoking; Smoking Cessation; Smoking cessation; Tobacco Use Disorder; Treatment Outcome; adult; article; cigarette smoking; comorbidity; controlled study; dept.psy; double blind procedure; drug dose comparison; female; high risk patient; human; major clinical study; male; naltrexone; named inventories; questionnaires and rating scales; nicotine patch; night; placebo; prediction; randomized controlled trial; risk factor; sleep disorder; smoking cessation; smoking habit; tobacco dependence; treatment failure; wakefulness

AVSP - Do infants detect A→V articulator congruency for non-native click consonants? - Best, Catherine T.; Kroos, Christian; Irwin, Julia (2011)
Keywords: dept.psy

Effects of time between trials on rats' and pigeons' choices with probabilistic delayed reinforcers. - Mazur, James E; Biondi, Dawn R (Journal of the Experimental Analysis of Behavior, 2011)
Parallel experiments with rats and pigeons examined reasons for previous findings that in choices with probabilistic delayed reinforcers, rats' choices were affected by the time between trials whereas pigeons' choices were not. In both experiments, the animals chose between a standard alternative and an adjusting alternative. A choice of the standard alternative led to a short delay (1 s or 3 s), and then food might or might not be delivered. If food was not delivered, there was an "interlink interval," and then the animal was forced to continue to select the standard alternative until food was delivered. A choice of the adjusting alternative always led to food after a delay that was systematically increased and decreased over trials to estimate an indifference point–a delay at which the two alternatives were chosen about equally often. Under these conditions, the indifference points for both rats and pigeons increased as the interlink interval increased from 0 s to 20 s, indicating decreased preference for the probabilistic reinforcer with longer time between trials. The indifference points from both rats and pigeons were well described by the hyperbolic-decay model. In the last phase of each experiment, the animals were not forced to continue selecting the standard alternative if food was not delivered. Under these conditions, rats' choices were affected by the time between trials whereas pigeons' choices were not, replicating results of previous studies. The differences between the behavior of rats and pigeons appears to be the result of procedural details, not a fundamental difference in how these two species make choices with probabilistic delayed reinforcers.
15 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Psychology Department, Southern Connecticut State University, New Haven, CT 06515, USA. mazurj1@southernct.edu
Keywords: *Choice Behavior; *Memory; Short-Term; *Probability Learning; *Reinforcement Schedule; Animals; Choice Behavior; Columbidae; Conditioning; Operant; Long Evans rat; Male; Memory; Short-Term; Motivation; Probability Learning; Psychomotor Performance; Rats; Rats; Long-Evans; Reinforcement Schedule; Species Specificity; Time Perception; animal; article; decision making; dept.psy; instrumental conditioning; learning; male; motivation; peer-reviewed; pigeons and doves; psychomotor performance; rat; reinforcement; short term memory; species difference; time perception

Is it the clicker, or is it the question? Untangling the effects of student response system use - Anthis, Kristine (Teaching of Psychology, 2011)
Previous research on the effectiveness of clickers has found their use to be positively associated with exam scores but not without methodological issues that hinder the conclusions that can be drawn. To address these limitations, the current studies isolated the effects of clickers from the effects of questions presented with clickers. Study 1 showed that students who did not use clickers to respond to questions but raised their hands performed better on exams than students who saw the same questions and responded with clickers. Study 2 found no relationship between clicker use and exam scores, which suggests that prior research claims about the effectiveness of clickers may have been premature given that clicker use was confounded with question use in those studies. Suggestions for future research are also provided.
44 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/100-584-314-043-220 tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: SRS; clickers; dept.psy; metacognition

Do infants detect A→V articulator congruency for non-native click consonants? - Best, Catherine T; Kroos, Christian; Irwin, Julia (Proceedings of the International Conference on Audio-Visual Speech Processing (AVSP2011), Aug 31 - Sep 3, 2011, Volterra, Italy, 2011)
Keywords: dept.psy; ⛔ No DOI found

Assessing feigned cognitive impairment in defendants hospitalized for competency restoration: further validation of the TOMI - Colwell, Lori H.; Colwell, Kevin (Journal of Forensic Psychology Practice, 2011)
Valid screens for feigned cognitive impairment are a fundamental component of any forensic assessment. The TOMI is a verbally administered, two-alternative forced-choice screen for feigned cognitive impairment in competence to stand trial (CST) evaluations. The present study provided further validation for the use of this tool in a sample of 82 forensic inpatients, the second investigation of the TOMI in a real-world, psycholegal context. Using three independent external criteria-the Test of Memory Malingering (TOMM) Trial 2 score, TOMM Retention Trial score, and a clinical treatment team decision-and these combined criteria-the Legal Knowledge scale (TOMI-L) evidenced high levels of sensitivity and specificity and excellent negative predictive power (NPP). The General Knowledge scale (TOMI-G) demonstrated poor sensitivity but high specificity and NPP. The authors discuss the utility of both scales in guiding and streamlining more thorough assessments of response styles in CST evaluations.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/139-925-559-807-493 tex.unique-id: [object Object]
Keywords: Competency; Forensic assessment; Legal Knowledge scale; Malingering; Test of Malingered Incompetence; Twoalternative forced-choice; adult; analytic method; article; clinical assessment tool; clinical decision making; clinical treatment team decision; cognitive defect; competence; dept.psy; forensic medicine; human; legal aspect; major clinical study; male; psychological aspect; sensitivity and specificity; validation process

Can children with autism spectrum disorders “Hear” a speaking face? - Irwin, Julia; Tornatore, Lauren A; Brancazio, Lawrence; Whalen, D H (Child Development, 2011)
This study used eye-tracking methodology to assess audiovisual speech perception in 26 children ranging in age from 5 to 15 years, half with autism spectrum disorders (ASD) and half with typical development. Given the characteristic reduction in gaze to the faces of others in children with ASD, it was hypothesized that they would show reduced influence of visual information on heard speech. Responses were compared on a set of auditory, visual, and audiovisual speech perception tasks. Even when fixated on the face of the speaker, children with ASD were less visually influenced than typical development controls. This indicates fundamental differences in the processing of audiovisual speech in children with ASD, which may contribute to their language and communication impairments.
85 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/088-396-626-758-638 tex.type: [object Object]
Keywords: Adolescent; Child; Child Development Disorders; Pervasive; Child; Preschool; Communication; Female; Humans; Language Development Disorders; Lipreading; Male; Pattern Recognition; Visual; Perceptual Masking; Reference Values; Speech Perception; Verbal Behavior; adolescent; article; autism; child; dept.hls; dept.psy; female; human; interpersonal communication; language disability; lip reading; male; pattern recognition; perception; preschool child; psychological aspect; reference value; speech perception; verbal behavior

Effects of playing wii on well-being in the elderly: physical activity, loneliness, and mood - Kahlbaugh, Patricia E; Sperandio, Amanda J; Carlson, Ashley L; Hauselt, Jerry (Activities, Adaptation & Aging, 2011)
Effects of compensatory strategies offered by Wii technology on physical activity, loneliness, and mood are investigated. Thirty-five individuals (M = 82 years) were randomly assigned to either playing Wii or watching television with a partner for 10 weeks. Physical activity, loneliness, mood, life satisfaction, and health were assessed. The elderly playing Wii had lower loneliness and a pattern of greater positive mood compared to the television group. No differences in life satisfaction or physical activity were found, but loneliness predicted positive mood, and positive mood predicted physical activity. This investigation points to the benefits of using Wii for well-being, particularly social connection and enjoyment. © 2011 Copyright Taylor and Francis Group, LLC.
101 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/154-270-739-188-836 tex.type: [object Object]
Keywords: dept.psy; integrative game playing; loneliness; mood; older adult recreation; well-being

The effect of playing the wii on loneliness and mood in the elderly - Kahlbaugh, P. E.; Sperandio, A. J.; Carlson, A. (Gerontologist, 2010)
tex.unique-id: ISI:000286006702491
Keywords: dept.psy; peer-reviewed; ⛔ No DOI found

Distinguishing truthful from invented accounts using reality monitoring criteria - Memon, Amina; Fraser, Joanne; Colwell, Kevin; Odinot, Geralda; Mastroberardino, Serena (Legal and Criminological Psychology, 2010)
Purpose. Previous research has suggested that true and invented memories can be distinguished between using the reality monitoring criteria. Two different coding schemes were used to examine the correct classification of reports as truthful or deceptive on the basis of individual reality-monitoring (RM) criteria. Method. Drawing upon the RM framework the present experiment examined transcripts of verbal accounts of eyewitnesses to a staged event or made up details about the incident. The statements were elicited during a face-to-face cognitive interview (CI) and were analysed by coders trained in the identification of criteria indicative of self-experienced and invented accounts (referred to here as Version 1) and a similar coding method (referred to here as Version 2). Results. A distinction was made between `external memories' (affective, perceptual, and contextual details) and `internal' memories (cognitive operations). For Version 1, the results indicated a higher number of contextual and external details in the descriptions of experienced events and as is commonly found in the deception literature, truthful accounts were longer. For Version 2, temporal and auditory details were more frequent in true accounts. Contrary to prediction, there were also more references to cognitive operations in true accounts. Conclusions. Any forensic application of RM should consider how external factors (characteristics of the event, motivation to deceive, and questioning style) influence the presence of RM criteria.
30 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-995-094-360-184 tex.unique-id: [object Object]
Keywords: adult; article; coding; cognition; controlled study; dept.psy; female; human; interview; major clinical study; male; memory; monitoring; priority journal; questionnaire; reality monitoring; self concept; verbal communication; witness

Distributed versus exclusive preference in discrete-trial choice. - Mazur, James E (Journal of Experimental Psychology: Animal Behavior Processes, 2010)
Two experiments on discrete-trial choice examined the conditions under which pigeons would exhibit exclusive preference for the better of two alternatives as opposed to distributed preference (making some choices for each alternative). In Experiment 1, pigeons chose between red and green response keys that delivered food after delays of different durations, and in Experiment 2 they chose between red and green keys that delivered food with different probabilities. Some conditions of Experiment 1 had fixed delays to food and other conditions had variable delays. In both experiments, exclusive or nearly exclusive preference for the better alternative was found in some conditions, but distributed preference was found in other conditions, especially in Experiment 2 when key location varied randomly over trials. The results were used to evaluate several different theories about discrete-trial choice. The results suggest that exclusive preference for one alternative is a frequent outcome in discrete-trial choice. When distributed preference does occur, it is not the result of inherent tendencies to sample alternatives or to match response percentages to the values of the alternatives. Rather, distributed preference may occur when two factors (such as reinforcer delay and position bias) compete for the control of choice, or when the consequences for the two alternatives are similar and difficult to discriminate.
9 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Psychology Department, Southern Connecticut State University, New Haven, CT 06515, USA. mazurj1@southernct.edu
Keywords: *Choice Behavior/ph [Physiology]; *Conditioning; Operant/ph [Physiology]; *Reinforcement Schedule; *Reinforcement; Psychology; Animals; Choice Behavior; Columba; Columbidae; Conditioning; Operant; Discrete-trial choice; Exclusive preference; Male; Pigeons; Probability; Reaction Time; Reaction Time/ph [Physiology]; Reinforcement (Psychology); Reinforcement Schedule; Reinforcer delay; Time Factors; animal; article; decision making; dept.psy; instrumental conditioning; male; physiology; pigeons and doves; probability; reaction time; reinforcement; time

Impression management strategies of deceivers and honest reporters in an investigative interview - Hines, Amber; Colwell, Kevin; Hiscock-Anisman, Cheryl; Garrett, Erika; Ansarra, Ryan; Montalvo, Larissa (European Journal of Psychology Applied to Legal Context, 2010)
Understanding the subjective experience of respondents attempting to convince an investigator will enhance our theoretical knowledge of deception and improve assessment techniques. Discrepancies between respondents' understanding and actual credibility criteria are especially important. Sixty-six participants engaged in a small crime, and were interviewed following a week's preparation. All were provided incentive for convincing the interviewer of the veracity of their statement. Thirty-two were honestly reporting the theft, and thirty-four were responding to avoid being found guilty. After a Reality Interview (a derivative of the Cognitive Interview), participants were asked to describe what was important in convincing the interviewer through open-ended and Liken-type questions. These strategies of impression management are presented here. The basic task of convincing appeared similar for both groups, with participants focused on providing clear and careful stories without contradictions rather than attempting to provide vivid and spontaneously-constructed statements. Deceivers attached more importance to: I) preparing in advance, 2) monitoring and controlling information, and 3) maintaining eye contact. Honest respondents were more concerned with providing correct peripheral detail. Importantly, both groups were reporting much more similarity than difference, and the strategies described are not likely to succeed against verbal content analysis.
tex.unique-id: ISI:000208403400006
Keywords: Credibility; Deception; Interrogation; Testimony; Verbal communication; dept.psy; ⛔ No DOI found

Book Review: Elaine f. weiss, fruits of victory: the woman's land army of america in the great war - Irwin, Julia F (First World War Studies, 2010)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/038-758-477-281-478 tex.type: [object Object]
Keywords: book.review; dept.psy

Seeing to hear? Patterns of gaze to speaking faces in children with autism spectrum disorders. - Irwin, Julia R; Brancazio, Lawrence (Frontiers in Psychology, 2014)
Using eye-tracking methodology, gaze to a speaking face was compared in a group of children with autism spectrum disorders (ASD) and a group with typical development (TD). Patterns of gaze were observed under three conditions: audiovisual (AV) speech in auditory noise, visual only speech and an AV non-face, non-speech control. Children with ASD looked less to the face of the speaker and fixated less on the speakers' mouth than TD controls. No differences in gaze were reported for the non-face, non-speech control task. Since the mouth holds much of the articulatory information available on the face, these findings suggest that children with ASD may have reduced access to critical linguistic information. This reduced access to visible articulatory information could be a contributor to the communication and language problems exhibited by children with ASD.
23 citations (Crossref) [2023-10-31] Place: Switzerland Irwin, Julia R. Haskins Laboratories New Haven, CT, USA ; Department of Psychology, Southern Connecticut State University New Haven, CT, USA. Brancazio, Lawrence. Haskins Laboratories New Haven, CT, USA ; Department of Psychology, Southern Connecticut State University New Haven, CT, USA.
Keywords: Audiovisual speech perception; Autism spectrum disorders; Communication development; Eyetracking; Lipreading; Speech in noise; dept.hls; dept.hms; dept.psy; peer-reviewed

Development of an audiovisual speech perception app for children with autism spectrum disorders - Irwin, Julia; Preston, Jonathan; Brancazio, Lawrence; D'Angelo, Michael; Turcios, Jacqueline (Clinical Linguistics & Phonetics, 2015)
Perception of spoken language requires attention to acoustic as well as visible phonetic information. This article reviews the known differences in audiovisual speech perception in children with autism spectrum disorders (ASD) and specifies the need for interventions that address this construct. Elements of an audiovisual training program are described. This researcher-developed program delivered via an iPad app presents natural speech in the context of increasing noise, but supported with a speaking face. Children are cued to attend to visible articulatory information to assist in perception of the spoken words. Data from four children with ASD ages 8-10 are presented showing that the children improved their performance on an untrained auditory speech-in-noise task.
16 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/022-073-168-350-692 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Attention; Audiovisual Aids; Audiovisual app; Autism spectrum disorder; Child; Child Development Disorders; Pervasive; Comprehension; Humans; Lipreading; Male; Mobile Applications; Pattern Recognition; Visual; Phonetics; Semantics; Speech Perception; Speech perception; attention; audiovisual aid; child; comprehension; dept.cmd; dept.hls; dept.psy; human; lip reading; male; mobile application; pattern recognition; phonetics; psychology; semantics; speech perception

Neurophysiology of speech differences in childhood apraxia of speech - Preston, Jonathan L; Molfese, Peter J; Gumkowski, Nina; Sorcinelli, Andrea; Harwood, Vanessa; Irwin, Julia; Landi, Nicole (Developmental Neuropsychology, 2014)
Event-related potentials (ERPs) were recorded during a picture naming task of simple and complex words in children with typical speech and with childhood apraxia of speech (CAS). Results reveal reduced amplitude prior to speaking complex (multisyllabic) words relative to simple (monosyllabic) words for the CAS group over the right hemisphere during a time window thought to reflect phonological encoding of word forms. Group differences were also observed prior to production of spoken tokens regardless of word complexity during a time window just prior to speech onset (thought to reflect motor planning/programming). Results suggest differences in pre-speech neurolinguistic processes.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/138-494-990-805-630 tex.type: [object Object]
Keywords: Adolescent; Apraxias; Child; Evoked Potentials; Female; Humans; Linguistics; Male; Neurophysiology; Speech; adolescent; apraxia; article; child; comparative study; dept.cmd; dept.psy; evoked response; female; human; linguistics; male; neurophysiology; pathophysiology; physiology; speech

Can color-coded word-families flashcards facilitate word recognition in kindergarteners? - Durwin, Cheryl C.; Moore, Dina (Reading Improvement, 2019)
Three novel experiments investigated the effectiveness of color-coded word-families flashcards for facilitating kindergarteners' word recognition skills. Flashcards were constructed with the rime of the word family (vowel and remaining consonant sounds) printed in black ink, indicating that words with this spelling pattern sound the same, and the onsets (initial consonant sounds) shown in different colors, indicating the sound changes from word to word. All experiments involved preand post-testing on word recognition and phonological awareness and random assignment to intervention or control conditions. The length of intervention and type of control condition differed among experiments. Results suggested that word-families may facilitate word recognition skill development and that factors such as amount of practice, phonological awareness, and socioeconomic status impact the efficacy of the intervention.
tex.ids: durwinCanColorcodedWordfamilies2020
Keywords: dept.psy; early literacy; elementary schools; peer-reviewed; phonological awareness; reading instructors; reading intervention; ⛔ No DOI found

Child and Adolescent Development: A Social Justice Approach - Anthis, Kristine (Cognella, 2021)
Child and Adolescent Development: A Social Justice Approach features portraits of development at each stage interwoven with the findings of developmental science research on how inequitable resources and opportunities, which are influenced by social, economic, and political factors, can impact development. The text also presents findings on how such data can be used to reduce inequities for children and their families, thereby optimizing development and allowing individuals to reach their full potential no matter who they are. The text begins with a chapter that briefly describes the stages, domains, and patterns of child and adolescent development, as well as traditional and contemporary theories. Subsequent chapters provide insight into the research methods of developmental science and explain how epigenetic influences affect development. The book then progresses chronologically, discussing the physical, cognitive, and emotional changes that occur within each stage, guiding readers through a tapestry of development from conception through adolescence. Throughout, Pan & Zoom sections supply both big-picture and microscopic understandings of development, Tech & Media asides highlight the influences that technology and media can have on child and adolescent development, and Mentor Minutes provide readers with practical wisdom through interviews with diverse professionals working in the field. Featuring a timely and much-needed perspective on development, Child and Adolescent Development is an ideal resource for courses in psychology, education, counseling, human services, and social work.
SCSU Faculty Scholar Award
Keywords: Child development; Youth development; SCSU Faculty Scholar Award; award_winner; dept.psy

Experimentally induced variation in neuroendocrine processes affects male reproductive behaviour, sperm characteristics and social interactions - Nugent, Bridget M.; Stiver, Kelly A.; Hofmann, Hans A.; Alonzo, Suzanne H. (Molecular Ecology, 2019)
While extensive research has focused on how social interactions evolve, the fitness consequences of the neuroendocrine mechanisms underlying these interactions have rarely been documented, especially in the wild. Here, we measure how the neuroendocrine mechanisms underlying male behaviour affect mating success and sperm competition in the ocellated wrasse (Symphodus ocellatus). In this species, males exhibit three alternative reproductive types. “Nesting males” provide parental care, defend territories and form cooperative associations with unrelated “satellites,” who cheat by sneaking fertilizations but help by reducing sperm competition from “sneakers” who do not cooperate or provide care. To measure the fitness consequences of the mechanisms underlying these social interactions, we used “phenotypic engineering” that involved administering an androgen receptor antagonist (flutamide) to wild, free-living fish. Nesting males treated with flutamide shifted their aggression from sneakers to satellite males and experienced decreased submissiveness by sneaker males (which correlated with decreased nesting male mating success). The preoptic area (POA), a region controlling male reproductive behaviours, exhibited dramatic down-regulation of androgen receptor (AR) and vasotocin 1a receptor (V1aR) mRNA following experimental manipulation of androgen signalling. We did not find a direct effect of the manipulation on male mating success, paternity or larval production. However, variation in neuroendocrine mechanisms generated by the experimental manipulation was significantly correlated with changes in behaviour and mating success: V1aR expression was negatively correlated with satellite-directed aggression, and expression of its ligand arginine vasotocin (AVT) was positively correlated with courtship and mating success, thus revealing the potential for sexual selection on these mechanisms. © 2018 John Wiley & Sons Ltd
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/019-033-927-344-660, pop00082 tex.type: [object Object]
Keywords: 11-ketotestosterone; Androgen Receptor Antagonists; Animals; Brain; Female; Flutamide; Male; Neurosecretory Systems; Perciformes; RNA; Messenger; Receptors; Androgen; Reproduction; Sexual Behavior; Animal; Social Behavior; Spermatozoa; Testosterone; alternative reproductive tactics; androgen receptor; androgen receptor antagonist; androgens; animal; brain; dept.psy; drug effect; female; flutamide; genetics; male; messenger RNA; metabolism; neuroendocrine; neuroendocrine system; peer-reviewed; physiology; reproduction; sexual behavior; sexual selection; social behavior; social behaviour; spermatozoon; teleosts; testosterone

Neuropeptide manipulation has behavioural and cascading fitness consequences in wild-living fish - Stiver, Kelly A.; Marsh-Rollo, Susan E.; Alonzo, Suzanne H. (Animal Behaviour, 2019)
Due to the difficulty of simultaneously assessing variation in individual physiology, behaviour and fitness, we often know little about the mechanistic basis of life-history trade-offs and fitness variation. It is similarly challenging to examine how physiological variation in one individual has cascading fitness consequences for others in the social environment. Using a wild-living fish (ocellated wrasse, Symphodus ocellatus), we manipulated a neuropeptide pathway associated with courtship, aggression and parental care in vertebrates (arginine vasotocin, AVT) and directly examined the behavioural and fitness consequences. Nesting males injected with the AVT antagonist increased their paternal care, resulting in increased hatching of offspring and increased reproductive success of all individuals that mated at his nest. By directly examining physiology, behaviour and reproductive success, we revealed how a small change in individual physiology has clear and direct fitness consequences for multiple individuals. © 2019 The Association for the Study of Animal Behaviour
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-297-635-637-918, pop00078 tex.type: [object Object]
Keywords: Symphodus ocellatus; Vertebrata; arginine vasotocin; behavioral response; dept.psy; fitness; fitness consequences; life history; nonapeptide; parental care; parental investment; paternal care; peer-reviewed; peptide; phenotype; phenotypic engineering; physiological manipulation; physiology; proximate mechanisms; reproductive cost; reproductive investment; reproductive success; trade-off; trade-offs; wild population

The efficacy of free-recall, cognitive load, and closed-ended questions when children are asked to falsely testify about a crime - Wyman, Joshua; Foster, Ida; Crossman, Angela; Colwell, Kevin; Talwar, Victoria (Applied Cognitive Psychology, 2019)
The current study evaluated the benefits of free-recall, cognitive load, and closed-ended questions on children's (ages 6 to 11; N = 147) true and false eyewitness disclosures. Children witnessed an experimenter find a stranger's wallet and were then asked to make a false denial, false accusation, true denial, or true accusation regarding an alleged theft. Overall, the free-recall question resulted in longer, more forthcoming and more detailed disclosures from older children and those who made a truthful accusation; however, children under the age of 9 and lie-tellers mostly relied on the closed-ended questions to discuss the theft. Although the cognitive load questions resulted in newly recalled information, there were no significant narrative differences between true and false statements on these questions. These findings suggest that forensic professionals should consider a child's developmental level, statement veracity, and disclosure-type (denial vs. accusation) when examining the efficacy of these commonly used questioning strategies.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/099-941-587-941-770 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: article; child; children; cognitive load; dept.psy; drug efficacy; eyewitness reports; false reports; female; free-recall; human; human experiment; major clinical study; male; narrative; peer-reviewed; recall; theft; witness

The language of wisdom understood through an analysis of wise quotes - DeFrank, Melanie; Bivona, Marissa; Chiaraluce, Brianna; Kahlbaugh, Patricia (Journal of Language and Social Psychology, 2019)
Wise quotes carry advice about how to navigate life's difficult decisions or feelings, allowing cultures to pass wisdom through generations. Qualities of wisdom have been identified by careful examination of wise individuals. Similarly, wise sayings and quotations can be analyzed and interpreted as emblematic of cultural beliefs about wisdom. The present research examines thematic and linguistic qualities of 157 wise quotes nominated as wise by 194 undergraduates. Thematic analysis of wise quotes centered on five dimensions of wisdom: Humor, Emotion, Review, Openness and Experience. Humor and Emotion were found to be the least represented while Review and Experience were the most represented. Linguistic analysis compared strong (n = 101) versus weak (n = 56) wise quotes and found that strong wise quotes were more linguistically complex and less likely to use the first-person pronouns. Analyzing the language of wisdom through quotes can provide additional insight into cultural representations of wisdom.
2 citations (Crossref) [2023-10-31] tex.address: 2455 TELLER RD, THOUSAND OAKS, CA 91320 USA tex.affiliation: DeFrank, M (Reprint Author), Southern Connecticut State Univ, Dept Psychol, 501 Crescent St, New Haven, CT 06515 USA. DeFrank, Melanie; Bivona, Marissa; Chiaraluce, Brianna; Kahlbaugh, Patricia, Southern CT State Univ, New Haven, CT USA. tex.author-email: defrankm1@southernct.edu tex.da: 2019-10-31 tex.doc-delivery-number: HW1CV tex.eissn: 1552-6526 tex.journal-iso: J. Lang. Soc. Psychol. tex.keywords-plus: LIFE; REMINISCENCE; DISTANCE; PEOPLE tex.number-of-cited-references: 39 tex.publisher: SAGE PUBLICATIONS INC tex.research-areas: Communication; Linguistics; Psychology tex.times-cited: 0 tex.type: Article tex.unique-id: ISI:000466421200006 tex.usage-count-last-180-days: 4 tex.usage-count-since-2013: 4 tex.web-of-science-categories: Communication; Linguistics; Psychology, Social
Keywords: adult; article; communicating wisdom; controlled study; dept.psy; female; human; human experiment; humor; language; major clinical study; male; peer-reviewed; quotes; text analysis; thematic analysis; wisdom

Tests of an indifference rule in variable-delay and double-reward choice procedures with humans - McKerchar, Todd L.; Mazur, James E. (Journal of the Experimental Analysis of Behavior, 2019)
Four hundred and fifty participants were recruited from Amazon Mechanical Turk across 3 experiments to test the predictions of a hyperbolic discounting equation in accounting for human choices involving variable delays or multiple rewards (Mazur, 1984, 1986). In Experiment 1, participants made hypothetical choices between 2 monetary alternatives, 1 consisting of a fixed delay and another consisting of 2 delays of equal probability (i.e., a variable-delay procedure). In Experiment 2, participants made hypothetical monetary choices between a single, immediate reward and 2 rewards, 1 immediate and 1 delayed (i.e., a double-reward procedure). Experiment 3 also used a double-reward procedure, but with 2 delayed rewards. Participants in all 3 experiments also completed a standard delay-discounting task. Finally, 3 reward amounts were tested in each type of task ($100, $1000, and $5000). In the double-reward conditions (Experiments 2 and 3), the results were in good qualitative and quantitative agreement with Mazur's model (1984, 1986). In contrast, when participants made choices involving variable delays (Experiment 1), there was relatively poor qualitative and quantitative agreement with this model. These results, along with our previous findings, suggest the structure of questions in hypothetical tasks with humans can be a strong determinant of the choice pattern.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/054-652-829-640-61X tex.address: [object Object] tex.affiliation: [object Object] tex.author-email: [object Object] tex.da: [object Object] tex.doc-delivery-number: [object Object] tex.eissn: [object Object] tex.journal-iso: [object Object] tex.keywords-plus: [object Object] tex.number-of-cited-references: [object Object] tex.publisher: [object Object] tex.research-areas: [object Object] tex.researcherid-numbers: [object Object] tex.times-cited: [object Object] tex.type: [object Object] tex.unique-id: [object Object] tex.usage-count-last-180-days: [object Object] tex.usage-count-since-2013: [object Object] tex.web-of-science-categories: [object Object]
Keywords: Adult; Choice Behavior; Delay Discounting; Female; Humans; Male; Models; Psychological; Probability; Reward; adult; choice; decision making; delay discounting; dept.psy; female; human; humans; hyperbolic discounting; male; mathematical model; peer-reviewed; probability; psychological model; reward

Using the reality interview improves the accuracy of the Criteria‐Based content analysis and reality monitoring - Bogaard, Glynis; Colwell, Kevin; Crans, Samantha (Applied Cognitive Psychology, 2019)
Active interviewing approaches can exploit the verbal differences between truthtellers and liars, thus improving detecting deception. One such method is the Reality Interview (RI) aimed to facilitate recall from truthtellers, while increasing the difficulty for liars. This study investigated whether the RI could improve the diagnostic accuracy of the Reality Monitoring and the Criteria-Based Content Analysis. Liars and truthtellers were either asked to freely recall an event or interviewed with the RI. As hypothesized, the RI improved the discriminability of Reality Monitoring and Criteria-Based Content Analysis over Free Recall. Honest responses were longer, and the RI increased the word count difference between honest and false statements. However, after correcting for word count, results were no longer significant, showing its importance for deception detection. Nonetheless, the RI increased verbal differences between truthtellers and liars, demonstrating that using the RI with verbal credibility assessment tools is a powerful combination for investigative interviewing. © 2019 The Authors Applied Cognitive Psychology Published by John Wiley & Sons Ltd.
12 citations (Crossref) [2023-10-31] Citation Key Alias: pop00213 tex.type: [object Object]
Keywords: Criteria-Based Content Analysis; Reality Interview; Reality Monitoring; article; content analysis; credibility assessment; deception; deception detection; dept.psy; diagnostic accuracy; diagnostic test accuracy study; human; human experiment; interview; monitoring; peer-reviewed; recall

Social anxiety and employment interviews: does nonverbal feedback differentially predict cortisol and performance? - Budnick, Christopher J.; Anderson, Eden M.; Santuzzi, Alecia M.; Grippo, Angela J.; Matuszewich, Leslie (Anxiety Stress and Coping, 2019)
Background & Objectives: Interviewers often provide positive nonverbal feedback to reduce interviewees' anxiety. Socially anxious individuals typically harbor negative self-views discrepant with positive feedback. We examined whether nonverbal feedback and social anxiety jointly influence cortisol responses to, and performance during, interviews. Design: An experimental between-subjects design randomly assigned participants to feedback condition. Methods: Undergraduate students (N = 130) provided saliva and completed social anxiety, interview anxiety, and affective measures before a simulated interview. Following a standardized script, a confederate interviewer provided positive, ambiguous, or negative nonverbal feedback. Participants then provided saliva and completed self-focused attention and self-awareness measures. Confederate interviewers and an external rater evaluated participants' anxiety displays, assertive behavior, and performance. Results: Positive feedback decreased cortisol and improved performance for low social anxiety participants. Socially anxious participants exhibited higher cortisol but did not exhibit significant differences in performance after positive compared to negative feedback. Conclusions: Consistent with previous findings, positive feedback did not benefit socially anxious interviewees. Positive feedback increased physiological arousal relative to negative feedback but did not hinder performance among people high in social anxiety. These results provide novel information about the interactive influence of social anxiety and nonverbal interviewer feedback on arousal, self-focus, and interview performance.
6 citations (Crossref) [2023-10-31] tex.address: 2-4 PARK SQUARE, MILTON PARK, ABINGDON OR14 4RN, OXON, ENGLAND tex.affiliation: Budnick, CJ (Reprint Author), Northern Illinois Univ, Dept Psychol, De Kalb, IL 60115 USA. Budnick, CJ (Reprint Author), Southern Connecticut State Univ, Dept Psychol, New Haven, CT 06515 USA. Budnick, Christopher J.; Anderson, Eden M.; Santuzzi, Alecia M.; Grippo, Angela J.; Matuszewich, Leslie, Northern Illinois Univ, Dept Psychol, De Kalb, IL 60115 USA. Budnick, Christopher J., Southern Connecticut State Univ, Dept Psychol, New Haven, CT 06515 USA. Anderson, Eden M., Marquette Univ, Dept Biomed Sci, Milwaukee, WI 53233 USA. tex.author-email: budnickc1@southernct.edu tex.da: 2019-10-31 tex.doc-delivery-number: HC5HI tex.eissn: 1477-2205 tex.funding-acknowledgement: National Science Foundation Graduate Research Fellowship ProgramNational Science Foundation (NSF) [G1A 62516] tex.funding-text: This material is based on work supported by the National Science Foundation Graduate Research Fellowship Program under grant number [G1A 62516] awarded to the first author while at Northern Illinois University. Any opinions, findings, and conclusions or recommendations expressed in this material are those of the author(s) and do not necessarily reflect the views of the National Science Foundation; Division of Graduate Education tex.journal-iso: Anxiety Stress Coping tex.keywords-plus: SELF-VERIFICATION PROCESSES; MEMORY PERFORMANCE; FOCUSED ATTENTION; STRESS; NOREPINEPHRINE; CONSCIOUSNESS; RESPONSES tex.number-of-cited-references: 48 tex.publisher: TAYLOR & FRANCIS LTD tex.research-areas: Neurosciences & Neurology; Psychiatry; Psychology tex.times-cited: 0 tex.type: Article tex.unique-id: ISI:000451833700005 tex.usage-count-last-180-days: 1 tex.usage-count-since-2013: 14 tex.web-of-science-categories: Neurosciences; Psychiatry; Psychology, Multidisciplinary
Keywords: Anxiety; Arousal; Attention; Feedback; Female; Humans; Hydrocortisone; Interviews as Topic; Job Application; Male; Saliva; Social anxiety; anxiety; arousal; attention; chemistry; controlled study; cortisol; dept.psy; feedback system; female; human; hydrocortisone; interview; interview anxiety; interviews; job finding; male; pathophysiology; peer-reviewed; psychology; randomized controlled trial; saliva; self-verification

Restraint stress exacerbates cell degeneration induced by acute binge ethanol in the adolescent, but not in the adult or middle-aged, brain - Fernandez, Macarena Soledad; de Olmos, Soledad; Nizhnikov, Michael E; Pautassi, Ricardo Marcos (Behavioural brain research, 2019)
Restraint stress (RS) induces neurotoxicity in the hippocampus, yet most of the studies have employed protracted RS (i.e., = 21 days). Binge ethanol can induce brain toxicity, an effect affected by age. It could be postulated that RS may facilitate ethanol-induced neurotoxicity, perhaps to a greater extent in adolescent vs. older subjects. We analyzed whether adolescent, adult or middle-aged male rats exposed to five episodes of RS followed, 72h later, by binge ethanol (i.e., two administrations of 2.5 g/kg ethanol) exhibited hippocampal neurotoxicity. Adolescents, but not adult or middle-aged rats, exhibited sensitivity to the neurotoxic effects of ethanol at dorsal CA2, ventral CA3 and ventral DG, and a neurotoxic effect of stress at dorsal CA1. Moreover, the combination of ethanol and stress exerted a synergistic effect upon cell degeneration at ventral CA1 and CA2, which was restricted to adolescents. Ethanol also increased cell degeneration, irrespective of age or stress, in dorsal CA3 and in dorsal DG; and ethanol and stress had, across all ages, a synergistic effect upon cell degeneration at the dorsal CA1. The greater neurotoxic response of adolescents to ethanol, stress, or ethanol+stress can put them at risk for the development of alcohol problems. Copyright © 2019 Elsevier B.V. All rights reserved.
8 citations (Crossref) [2023-10-31] Place: Netherlands Fernandez, Macarena Soledad. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC - CONICET-Universidad Nacional de Cordoba), Cordoba, C.P 5000, Argentina; Facultad de Psicologia, Universidad Nacional de Cordoba, Cordoba, C.P 5000, Argentina. Electronic address: mfernandez@immf.uncor.edu. de Olmos, Soledad. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC - CONICET-Universidad Nacional de Cordoba), Cordoba, C.P 5000, Argentina. Nizhnikov, Michael E. Department of Psychology, Southern Connecticut State University, New Haven, CT, United States. Pautassi, Ricardo Marcos. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC - CONICET-Universidad Nacional de Cordoba), Cordoba, C.P 5000, Argentina; Facultad de Psicologia, Universidad Nacional de Cordoba, Cordoba, C.P 5000, Argentina.
Keywords: *Age Factors; *Binge Drinking/pp [Physiopathology]; *Ethanol/ae [Adverse Effects]; Adolescent; Adult rats; Age Factors; Animals; Article; Binge Drinking; Binge Drinking/me [Metabolism]; Brain; Brain/de [Drug Effects]; Dentate Gyrus; Dentate Gyrus/de [Drug Effects]; Ethanol; Ethanol/pd [Pharmacology]; Hippocampus; Hippocampus/de [Drug Effects]; Male; Middle-Aged rats; Neurotoxicity; Rats; Rats; Wistar; Restraint; Physical; Wistar rat; adolescent; adult; adult animal; age; alcohol; animal; animal behavior; animal cell; animal experiment; animal model; animal tissue; binge drinking; brain; controlled study; dentate gyrus; dept.psy; dorsal hippocampus; drinking behavior; drug effect; exercise; hippocampal CA1 region; hippocampal CA2 region; hippocampal CA3 region; hippocampus; immobilization stress; male; metabolism; middle aged; nerve cell degeneration; neurotoxicity; nonhuman; pathophysiology; peer-reviewed; priority journal; rat; sensitivity analysis; underage drinking; ventral dentate gyrus; ventral hippocampus

Offspring of male rats exposed to binge alcohol exhibit heightened ethanol intake at infancy and alterations in T-maze performance. - Hollander, Jessica; McNivens, Megan; Pautassi, Ricardo M; Nizhnikov, Michael E (Alcohol, 2019)
Alcohol use is associated with a variety of negative consequences, including heightened likelihood of cognitive impairment, proclivity to alcohol use disorders (AUD), and alterations in the drinker's offspring. Children and rodents exposed to alcohol during pregnancy, or those whose fathers consumed alcohol prior to mating, often exhibit neurodevelopmental, physiological, and behavioral deficits. The present study assessed cognitive function and alcohol intake in male and female rats that were offspring of alcohol-exposed fathers. Adult male rats were exposed to alcohol or vehicle (0.0 or 2.0 g/kg, respectively; twice daily for 2 days followed by a rest day, for a total of eight alcohol or vehicle exposure days), or were left untreated and then mated with non-manipulated females. The offspring were assessed for alcohol intake, via intraoral infusion, followed by cognitive assessment via an alternating T-maze task. The results indicated that paternal ethanol exposure, prior to breeding, resulted in offspring that consumed significantly more ethanol than vehicle or untreated controls. Furthermore, the offspring of alcohol-exposed fathers exhibited a significant failure to initiate and complete the T-maze performance tests. Although, when they did engage in the tests they performed at the level of controls (i.e., 80% correct). The present results add to a growing body of literature suggesting that paternal pre-conception alcohol exposure can have deleterious effects on the offspring. Copyright © 2018 Elsevier Inc. All rights reserved.
11 citations (Crossref) [2023-10-31] Place: United States Hollander, Jessica. Department of Psychology, Southern Connecticut State University, New Haven, CT, United States. McNivens, Megan. Department of Psychology, Southern Connecticut State University, New Haven, CT, United States. Pautassi, Ricardo M. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC-CONICET), Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina; Facultad de Psicologia, Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina. Nizhnikov, Michael E. Department of Psychology, Southern Connecticut State University, New Haven, CT, United States. Electronic address: nizhnikovm1@southernct.edu.
Keywords: *Alcohol Drinking/px [Psychology]; *Binge Drinking/px [Psychology]; *Fathers/px [Psychology]; *Maze Learning/de [Drug Effects]; *Prenatal Exposure Delayed Effects/px [Psychology]; Alcohol Drinking; Alcohol intake; Animals; Article; Binge Drinking; Fathers; Female; Male; Maze Learning; Paternal alcohol exposure; Pregnancy; Prenatal Exposure Delayed Effects; Rats; T-maze; T-maze test; adult; alcohol; alcohol consumption; animal; animal experiment; binge drinking; cognition; controlled study; dept.psy; drinking behavior; drug effect; father; female; male; maze test; nonhuman; paternal exposure; peer-reviewed; pregnancy; prenatal exposure; psychology; rat

The fear of missing out at work: Examining costs and benefits to employee health and motivation - Budnick, Christopher J.; Rogers, Arielle P.; Barber, Larissa K. (Computers in Human Behavior, 2020)
The popular business media argues that the “fear of missing out” (FoMO) on work-related opportunities harms employees’ health and performance. Yet, these claims rely on the study of FoMO in college students in non-work contexts. Therefore, we explored workplace FoMO among employees across three studies. We first developed a measure and provided validation evidence for workplace FoMO among diverse employees (N = 324; Study 1) and MBA students (N = 223; Study 2). Using a third large employee sample (N = 300; Study 3), we tested whether workplace FoMO predicted health (i.e., work burnout and work well-being) and motivational outcomes (i.e., message-checking behaviors and work engagement). We also examined whether family-supportive organizational perceptions (FSOP) moderated these relationships. Results indicated that workplace FoMO is a distinct construct from other measures, including general FoMO. Workplace FoMO also predicted work burnout and message checking behavior, but not work well-being. Lower levels of FSOP strengthened the positive relationship between workplace FoMO and message checking behavior, but also produced a positive relationship between workplace FoMO and work well-being. Overall, FoMO appears to be relevant to the work context and predicts both employee well-being and behavior outcomes. © 2019 Elsevier Ltd
34 citations (Crossref) [2023-10-31] tex.ids: budnickFearMissingOut2020a, pop00228 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85073522410 tex.type: Journal article type: Article
Keywords: Behavioral research; College students; Costs and benefits; Employee health; Fear of missing out; Health; Job satisfaction; Motivation; Students; Technology use; Technology use at work; Well being; Work engagements; Work-related; article; burnout; controlled study; dept.psy; fear of missing out; human; major clinical study; motivation; peer-reviewed; perception; wellbeing; work engagement

Language choice matters: when profanity affects how people are judged - DeFrank, Melanie; Kahlbaugh, Patricia E (Journal of Language and Social Psychology, 2019)
Swearing is prevalent in our society, but the influence of such language choices on judgments of others is not well understood. This study examines how the composition of conversational dyads, speaker's gender, and use of profanity influence impressions. Participants (N = 138) were randomly assigned to read two conversations and rate target speakers (one male, one female). The conversations had neither, one, or both speakers using profanity and consisted of same- or mixed-gender dyads. The result is a 2 (target speaker, male/female) x 2 (dyad composition) x 3 (profanity) mixed design with speaker gender as the repeated measure. Speakers using profanity had poorer impression ratings on several variables, including overall impression, intelligence, and trustworthiness. Speakers swearing in mixed-gender dyads were rated as less sociable, and males swearing in mixed-gender dyads were rated as more offensive. Language choices matter, and more research is needed to understand the unconscious biases held against those who use profanity.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/017-757-464-111-633 tex.type: [object Object]
Keywords: adult; article; controlled study; conversation; dept.psy; ego development; female; gender; human; human experiment; impression formation; intelligence; language; major clinical study; male; peer-reviewed; profanity; randomized controlled trial

A comparison of different investigative interviewing techniques in generating differential recall enhancement and detecting deception - De Rosa, Jacob; Hiscockanisman, Cheryl; Blythe, Adam; Bogaard, Glynis; Hally, Ashley; Colwell, Kevin (Journal of Investigative Psychology and Offender Profiling, 2019)
This study compared the Stepwise Interview, Cognitive Interview, and Reality Interview in detecting deception with inmates. The dependent measures were the amount of unique details provided during the free narrative and mnemonics and the number of words provided during the free narrative and mnemonics of each interview. The Stepwise Interview generated 58.3% accuracy, the Cognitive Interview generated 70.0% accuracy, and the Reality Interview generated 93.3% accuracy. The different tasks of these interviews increased the differences between honest and deceptive statements and therefore, increased the accuracy in detection of deception. Differential recall enhancement is used to explain the findings.
4 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000459742000004, lens.org/168-236-602-671-439 tex.type: [object Object]
Keywords: credibility assessment; dept.psy; detecting deception; investigative interviewing; peer-reviewed

Does eyewitness and interviewer gender influence children’s reports? An experimental analysis of eyewitness and interviewer gender on children’s testimony - Foster, Ida; Wyman, Joshua; Tong, Donia; Colwell, Kevin; Talwar, Victoria (Psychiatry, Psychology and Law, 2019)
This study examines how children's age, gender and interviewer gender affected children's testimony after witnessing a theft. Children (N=127, age = 6-11 years) witnessed an experimenter (E1) find money, which he/she may/may not have taken. E1 then asked the children to falsely deny that the theft occurred, falsely accuse E1 of taking the money, or tell the truth when interviewed by a second experimenter. Falsely denying or falsely accusing influenced children's forthcomingness and quality of their testimony. When accusing, boys were significantly more willing than girls to disclose about the theft earlier and without being asked directly. When truthfully accusing, children gave lengthier testimony to same-gendered adults. When denying, children were significantly more willing to disclose the theft earlier to male interviewers than to females. As children aged, they were significantly less likely to lie, more likely to disclose earlier when accusing, and give lengthier and more consistent testimony.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/021-752-791-677-978 tex.address: [object Object] tex.affiliation: [object Object] tex.author-email: [object Object] tex.da: [object Object] tex.doc-delivery-number: [object Object] tex.eissn: [object Object] tex.funding-acknowledgement: [object Object] tex.funding-text: [object Object] tex.journal-iso: [object Object] tex.keywords-plus: [object Object] tex.number-of-cited-references: [object Object] tex.publisher: [object Object] tex.research-areas: [object Object] tex.times-cited: [object Object] tex.type: [object Object] tex.unique-id: [object Object] tex.usage-count-last-180-days: [object Object] tex.usage-count-since-2013: [object Object] tex.web-of-science-categories: [object Object]
Keywords: adult; article; child; children; dept.psy; disclosures; false accusations; false denials; female; gender; girl; human; interviewer gender; lying; major clinical study; male; money; peer-reviewed; preschool child; theft; witness

Audiovisual speech perception in children with autism spectrum disorders - Irwin, Julia R.; Avery, T; Kleinman, D; Landi, N (PROCEEDINGS of the 23rd International Congress on Acoustics, 2019)
In face-to-face conversation, when a speaker talks, the outcome of their speech can both be heard (audio) and seen (visual). We employed a novel visual phonemic restoration paradigm to assess neural signatures (event related potentials [ERPs]) of audiovisual processing in typically developing children and in children with ASD. During EEG recording, two types of auditory stimuli were alternately presented with video of a speaker saying the consonant-vowel syllable /ba/: 1) a synthesized consonant-vowel syllable /ba/ or 2) a synthesized syllable derived from /ba/ in which auditory cues for the consonant are substantially weakened, such that it sounds more like /a/. The auditory stimuli are easily discriminable, however, in the context of a visual /ba/, the auditory /a/ is typically perceived as /ba/, producing a visual phonemic restoration. In an ERP context, we have shown that this restoration leads to an attenuated phoneme discrimination response in an active task in typical adults and children. To explore the hypothesis that children with autism spectrum disorder (ASD) have atypical AV speech integration under pre-attentive processing conditions, we tested whether children with ASD would show a reduction in this restoration effect under passive listening conditions. Indeed, in this task, children with ASD showed a large /ba/-/a/ discrimination response, even in the presence of a speaker producing /ba/, suggesting reduced influence of visual speech. © 2019 Proceedings of the International Congress on Acoustics. All rights reserved.
Keywords: Audiovisual; Autism; Phonemic Restoration; Speech; dept.psy

Personality and political preferences: the 2016 U.S. presidential election - Abe, Jo Ann A (Journal of Research in Personality, 2018)
This study examined whether personality variables would account for political preferences during the 2016 U.S. Presidential Election using a demographically diverse sample of participants (N = 897). Study A revealed participants' ratings of their own personality and emotions were weakly associated with political preferences, but their ratings of candidates' personality showed robust associations, and were far more predictive of voting intention than all of the demographic variables, political affiliation, and racial attitudes combined. In Study B, linguistic analysis of narratives revealed words reflective of liberal values were correlated with positive evaluations of Clinton's personality, whereas words reflective of conservative values and “populist” sentiment were correlated with positive evaluations of Trump's personality, suggesting appraisals of candidates may be associated with values. (C) 2018 Elsevier Inc. All rights reserved.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/058-761-611-227-871 tex.type: [object Object]
Keywords: Five Factor Model of Personality (FFM); Liberal and conservative values; Linguistic analysis; Political preferences; dept.psy; peer-reviewed; “Populist” sentiment

Personality, Well-Being, and Cognitive-Affective Styles: A Cross-Sectional Study of Adult Third Culture Kids - Abe, Jo Ann A. (Journal of Cross-Cultural Psychology, 2018)
Third Culture Kids (TCKs) and their adult counterparts (ATCKs) refer to individuals who spent part of their developmental years abroad and are an important demographic to study in this rapidly globalizing world. To date, the bulk of the research on (A)TCKs has been descriptive and little is known about their developmental trajectories in adulthood. The major objective of this study was to examine the personality traits, dimensions of well-being, and cognitive-affective styles of ATCKs across the adult life span using well-validated psychological measures. A subsidiary goal was to develop a new multidimensional international experiences scale to assess levels of multicultural engagement in ATCKs. The participants in this study (N = 700+; age = 18-80+) were recruited from the Alumni Office of an international school in Japan. Somewhat contrary to how they are often depicted in the news media and in qualitative studies, the ATCKs showed normative changes in personality and well-being in the direction of greater maturity and adjustment during adulthood, with those reporting higher levels of multicultural engagement generally exhibiting a more resilient personality profile, higher levels of well-being, and more adaptive cognitive and affective styles.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/029-254-445-940-525 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: adult third culture kids; dept.psy; five-factor model of personality; need for closure; peer-reviewed; well-being

Influence of prenatal pre-exposure to an odor on intake behavior of an aversive solution in newborn rats. - Kamenetzky, Giselle V; Suarez, Andrea B; Ifran, Maria Celeste; Nizhnikov, Michael E; Pautassi, Ricardo M (Neuroscience letters, 2018)
Early pre- or postnatal sensory experiences significantly influence flavor preference and food intake, and can induce liking for innately unpalatable flavors. Previous work found that newborn rats stimulated with an odor experienced shortly after birth exhibited heightened intake and seeking towards an artificial nipple containing quinine. This result suggests that odors made familiar trough early postnatal pre-exposure can shift the motivational value of unconditional stimuli. The objective of the current study was to assess the effect of an odor (lemon) experienced in-utero on the first intake responses towards an artificial nipple supplying quinine. The hypothesis, which was corroborated, was that stimulation with the olfactory stimulus experienced in-utero would increase the newborn's intake and grasp responses to the artificial nipple containing quinine. Exposure to the odor that had been pre-exposed in utero increased quinine intake and seeking (i.e., latency to grasp and total time in contact with the nipple, as well as number of and mean duration of nipple grasps) in 3-h-old pups. These results replicate those previously found with postnatal odor pre-exposure, and extend the phase for pre-exposure to the prenatal stage. Copyright © 2018 Elsevier B.V. All rights reserved.
5 citations (Crossref) [2023-10-31] Place: Ireland Kamenetzky, Giselle V. Laboratorio de Psicologia Experimental y Aplicada, Universidad de Buenos Aires, Instituto de Investigaciones Medicas (IDIM - CONICET - UBA), Argentina; Centro de Altos Estudios en Ciencias Humanas y de la Salud (CAECIHS-UAI), Universidad Abierta Interamericana, Buenos Aires, Argentina. Suarez, Andrea B. Laboratorio de Psicologia Experimental y Aplicada, Universidad de Buenos Aires, Instituto de Investigaciones Medicas (IDIM - CONICET - UBA), Argentina; Centro de Altos Estudios en Ciencias Humanas y de la Salud (CAECIHS-UAI), Universidad Abierta Interamericana, Buenos Aires, Argentina. Ifran, Maria Celeste. Laboratorio de Psicologia Experimental y Aplicada, Universidad de Buenos Aires, Instituto de Investigaciones Medicas (IDIM - CONICET - UBA), Argentina; Centro de Altos Estudios en Ciencias Humanas y de la Salud (CAECIHS-UAI), Universidad Abierta Interamericana, Buenos Aires, Argentina. Electronic address: MariaCeleste.Ifran@Alumnos.uai.edu.ar. Nizhnikov, Michael E. Department of Psychology, Southern Connecticut State University, United States. Pautassi, Ricardo M. Instituto de Investigacion Medica Mercedes y Martin Ferreyra, CONICET, Universidad Nacional de Cordoba, Cordoba, Argentina; Facultad de Psicologia, Universidad Nacional de Cordoba, Cordoba, C.P 5000, Argentina.
Keywords: *Eating; *Feeding Behavior; *Odorants; *Prenatal Exposure Delayed Effects; *Quinine/ad [Administration & Dosage]; Animals; Animals; Newborn; Animals; Suckling; Article; Eating; Feeding Behavior; Female; Male; Neonate rat; Odor pre-exposure; Odorants; Pregnancy; Prenatal Exposure Delayed Effects; Prenatal exposure; Quinine; Rats; Sprague-Dawley; Smell; Sprague Dawley rat; animal; animal experiment; aversive agent; controlled study; dept.psy; eating; feeding behavior; female; food intake; fragrance; learning; male; newborn; nipple; nonhuman; odor; peer-reviewed; pregnancy; prenatal exposure; priority journal; quinine; rat; smelling; stimulation; suckling animal

Intentional multiple mating by females in a species where sneak fertilization circumvents female choice for parental males - Stiver, Kelly A.; Kindsvater, Holly K.; Tamburello, Natascia; Heckman, Kellie L.; Klein, Joanne; Alonzo, Suzanne H. (Journal of Fish Biology, 2018)
This paper describes how individual female ocellated wrasse Symphodus ocellatus distribute their spawning among males and nests in space and time. It is based on previously collected genetic data of larvae from ten different nests (used to reconstruct half and full-sibling groupings both within and among nests on multiple days) and behavioural data of marked females across the reproductive season. Both the genetic analyses and behavioural observations confirm that female S. ocellatus intentionally engage in multiple mating, by repeatedly spawning at the same nest on different days and at several different nests (up to 12 spawning events over 3 weeks), leading to mixed paternity among her young. The main benefit of such high and intentional multiple mating is probably insurance against brood failure due to nest predation, desertion or poor paternal care by the male. These findings reveal that even in systems where females attempt to avoid male-controlled mixed paternity, they may still engage in intentional multiple mating due to these potential benefits. © 2018 The Fisheries Society of the British Isles
8 citations (Crossref) [2023-10-31]
Keywords: Animals; Female; Fertilization; Male; Mating Preference; Animal; Paternity; Perciformes; Reproduction; Sexual Behavior; Animal; Symphodus ocellatus; animal; behaviour; dept.psy; female; fertilization; male; mate choice; mating systems; paternity; peer-reviewed; reproduction; sexual behavior; sexual conflict; sexual selection; trade-offs

Substance use, anxiety, and depressive symptoms among college students - Walters, Kenneth S.; Bulmer, Sandra Minor; Troiano, Peter F.; Obiaka, Uzoma; Bonhomme, Rebecca (Journal of Child & Adolescent Substance Abuse, 2018)
Research on college substance use and mental illness is limited and inconsistent. Measures of substance use, and anxiety and depressive symptoms, were completed by 1,316 undergraduates within a major drug transportation corridor. Hierarchical linear regressions were used to test associations between anxious and depressive symptoms and substance use (i.e., alcohol, cannabis, tobacco, cocaine, other amphetamines, sedatives, hallucinogens, and designer drugs). Depressive symptoms were associated with use of cannabis, tobacco, amphetamines, cocaine, sedatives, and hallucinogens. Anxiety symptoms were unrelated to substance use. These findings support the need for education and prevention at universities, emphasizing tobacco, cannabis, and certain “harder” drugs.
58 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/158-625-507-666-259, pop00148 tex.type: [object Object]
Keywords: anxiety; college students; depression; dept.hhs; dept.psy; mental health; peer-reviewed; substance use

Electrophysiological Indices of Audiovisual Speech Perception: Beyond the McGurk Effect and Speech in Noise. - Irwin, Julia; Avery, Trey; Brancazio, Lawrence; Turcios, Jacqueline; Ryherd, Kayleigh; Landi, Nicole (Multisensory research, 2018)
Visual information on a talker's face can influence what a listener hears. Commonly used approaches to study this include mismatched audiovisual stimuli (e.g., McGurk type stimuli) or visual speech in auditory noise. In this paper we discuss potential limitations of these approaches and introduce a novel visual phonemic restoration method. This method always presents the same visual stimulus (e.g., /ba/) dubbed with a matched auditory stimulus (/ba/) or one that has weakened consonantal information and sounds more /a/-like). When this reduced auditory stimulus (or /a/) is dubbed with the visual /ba/, a visual influence will result in effectively 'restoring' the weakened auditory cues so that the stimulus is perceived as a /ba/. An oddball design in which participants are asked to detect the /a/ among a stream of more frequently occurring /ba/s while either a speaking face or face with no visual speech was used. In addition, the same paradigm was presented for a second contrast in which participants detected /pa/ among /ba/s, a contrast which should be unaltered by the presence of visual speech. Behavioral and some ERP findings reflect the expected phonemic restoration for the /ba/ vs. /a/ contrast; specifically, we observed reduced accuracy and P300 response in the presence of visual speech. Further, we report an unexpected finding of reduced accuracy and P300 response for both speech contrasts in the presence of visual speech, suggesting overall modulation of the auditory signal in the presence of visual speech. Consistent with this, we observed a mismatch negativity (MMN) effect for the /ba/ vs. /pa/ contrast only that was larger in absence of visual speech. We discuss the potential utility for this paradigm for listeners who cannot respond actively, such as infants and individuals with developmental disabilities.
8 citations (Crossref) [2023-10-31] Place: Netherlands Irwin, Julia. Haskins Laboratories, New Haven, CT, USA. Irwin, Julia. Southern Connecticut State University, New Haven, CT, USA. Avery, Trey. Haskins Laboratories, New Haven, CT, USA. Brancazio, Lawrence. Haskins Laboratories, New Haven, CT, USA. Brancazio, Lawrence. Southern Connecticut State University, New Haven, CT, USA. Turcios, Jacqueline. Haskins Laboratories, New Haven, CT, USA. Turcios, Jacqueline. Southern Connecticut State University, New Haven, CT, USA. Ryherd, Kayleigh. Haskins Laboratories, New Haven, CT, USA. Ryherd, Kayleigh. University of Connecticut, Storrs, CT, USA. Landi, Nicole. Haskins Laboratories, New Haven, CT, USA. Landi, Nicole. University of Connecticut, Storrs, CT, USA.
Keywords: Audio-visual speech; Audio-visual stimulus; Audiovisual; Audiovisual speech perception; Auditory stimuli; Developmental disability; ERP; Electrophysiology; Enterprise resource planning; Mismatch negativity; Phonemic restoration; Potential utility; Restoration; Speech; Speech recognition; Visual information; dept.psy; peer-reviewed; phonemic restoration

A familiarization protocol facilitates the participation of children with asd in electrophysiological research - Turcios, Jacqueline; Cook, Barbara; Irwin, Julia; Rispoli, Taylor; Landi, Nicole (JoVE (Journal of Visualized Experiments), 2017)
This paper includes a detailed description of a familiarization protocol, which is used as an integral component of a larger research protocol to collect electroencephalography (EEG) data and Event-Related Potentials (ERPs). At present, the systems available for the collection of high-quality EEG/ERP data make significant demands on children with developmental disabilities, such as those with an Autism Spectrum Disorder (ASD). Children with ASD may have difficulty adapting to novel situations, tolerating uncomfortable sensory stimuli, and sitting quietly. This familiarization protocol uses Evidence-Based Practices (EBPs) to increase research participants' knowledge and understanding of the specific activities and steps of the research protocol. The tools in this familiarization protocol are a social narrative, a visual schedule, the Premack principle, role-playing, and modeling. The goal of this familiarization protocol is to increase understanding and agency and to potentially reduce anxiety for child participants, resulting in a greater likelihood of the successful completion of the research protocol for the collection of EEG/ERP data.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/080-947-783-936-351, pop00167 tex.type: [object Object]
Keywords: dept.cmd; dept.psy

Personality, Emotional Qualities of Leisure, and Subjective Well-Being in the Elderly. - Kahlbaugh, Patricia; Huffman, Loreen (International journal of aging & human development, 2017)
In this study, we examined personality traits of older adults and their emotional experiences associated with engaging in specific leisure activities. Older individuals (17 males, 32 females), ages ranging from 65 to 97 years (mean age 74), completed measures of Big Five personality traits, positive and negative affect, subjective well-being (SWB), independent functioning, and an emotion-activity inventory. As expected, Extraversion, Agreeableness, Conscientiousness, and Openness to experience were related to positive affect, while Neuroticism was related to negative affect. Openness and Agreeableness were related to positive emotions experienced in social and cognitive domains, and Agreeableness was related to greater SWB, greater positive affect, and more positively experienced activities. Neuroticism was related to lower SWB and fewer positively experienced activities. These findings suggest that assessing the fit between personality and emotions experienced during activities should be considered when creating programs tailored to elderly individuals, with the goal of encouraging more active and rewarding lives.
17 citations (Crossref) [2023-10-31] Place: United States Kahlbaugh, Patricia. 1 Psychology Department, Southern Connecticut State University, New Haven, CT, USA. Huffman, Loreen. 2 Psychology Department, Missouri Southern State University, Joplin, MO, USA.
Keywords: *Aging/px [Psychology]; *Emotions; *Leisure Activities; *Personal Satisfaction; *Personality; Affect; Aged; Aged; 80 and over; Aging; Emotions; Female; Humans; Leisure Activities; Male; Personal Satisfaction; Personality; affect; aged; aging; dept.psy; emotion; emotions; female; human; leisure; male; personality; psychology; satisfaction; subjective well-being; successful aging; very elderly

Restraint stress enhances alcohol intake in adolescent female rats but reduces alcohol intake in adolescent male and adult female rats. - Wille-Bille, Aranza; Ferreyra, Ana; Sciangula, Martina; Chiner, Florencia; Nizhnikov, Michael E; Pautassi, Ricardo Marcos (Behavioural brain research, 2017)
Adolescents may be more sensitive to stress-induced alcohol drinking than adults, which would explain the higher prevalence of alcohol abuse and dependence in late adolescence than in adulthood. The present study analyzed the impact of restraint stress on the initiation of alcohol intake across 2 weeks of intermittent, two-bottle choice intake in male and female adolescent rats and adult female rats. Restraint stress significantly increased alcohol intake and preference in female adolescent rats but decreased alcohol intake and preference in male adolescent and female adult rats. The effects of restraint stress on alcohol intake were mitigated in adolescent females following administration of the kappa opioid receptor antagonist norbinaltorphimine. Adolescent but not adult female rats that were subjected to restraint stress spent more time on the open arms of the elevated plus maze. Female adolescents exposed to stress also exhibited greater risk-taking behaviors in a concentric square field test compared with non-stressed controls. These results indicate age- and sex-related differences in the sensitivity to alcohol-stress interactions that may facilitate the initiation of alcohol use in female adolescents. The facilitatory effect of stress on alcohol intake was related to greater exploratory and risk-taking behaviors in young females after stress exposure. Copyright © 2017 Elsevier B.V. All rights reserved.
42 citations (Crossref) [2023-10-31] Place: Netherlands Wille-Bille, Aranza. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC-CONICET), Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina. Ferreyra, Ana. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC-CONICET), Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina; Facultad de Psicologia, Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina. Sciangula, Martina. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC-CONICET), Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina; Facultad de Psicologia, Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina. Chiner, Florencia. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC-CONICET), Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina; Facultad de Psicologia, Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina. Nizhnikov, Michael E. Department of Psychology, Southern Connecticut State University, United States. Pautassi, Ricardo Marcos. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC-CONICET), Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina; Facultad de Psicologia, Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina. Electronic address: rpautassi@gmail.com.
Keywords: *Aging/ph [Physiology]; *Aging/px [Psychology]; *Alcohol Drinking/pp [Physiopathology]; *Alcohol Drinking/px [Psychology]; *Sex Characteristics; *Stress; Psychological/pp [Physiopathology]; Adolescents; Adults; Age differences; Aging; Aging/de [Drug Effects]; Alcohol; Alcohol Drinking; Alcohol Drinking/dt [Drug Therapy]; Animals; Article; Central Nervous System Depressants; Central Nervous System Depressants/ad [Administration & Dosage]; Choice Behavior; Choice Behavior/de [Drug Effects]; Choice Behavior/ph [Physiology]; Disease Models; Animal; Ethanol; Ethanol/ad [Administration & Dosage]; Exploratory Behavior; Exploratory Behavior/de [Drug Effects]; Exploratory Behavior/ph [Physiology]; Female; Male; Motor Activity; Motor Activity/de [Drug Effects]; Motor Activity/ph [Physiology]; Naltrexone; Naltrexone/aa [Analogs & Derivatives]; Naltrexone/pd [Pharmacology]; Narcotic Antagonists; Narcotic Antagonists/pd [Pharmacology]; Rats; Wistar; Receptors; Opioid; kappa; Receptors; Opioid; kappa/ai [Antagonists & Inhibitors]; Receptors; Opioid; kappa/me [Metabolism]; Restraint; Physical; Risk-Taking; Sex Characteristics; Stress; Stress; Psychological; Stress; Psychological/dt [Drug Therapy]; Wistar rat; [kappa] opioid receptors; adolescent; adult; age; aging; alcohol; alcohol consumption; analogs and derivatives; animal; animal experiment; antagonists and inhibitors; behavior assessment; central depressant agent; comparative study; concentric square field test; controlled study; decision making; dept.psy; disease model; drinking behavior; drug effects; drug therapy; elevated plus maze test; exercise; experimental study; exploratory behavior; exploratory behavior test; female; high risk behavior; immobilization stress; kappa opiate receptor; kappa opiate receptor antagonist; male; mental stress; metabolism; motor activity; naltrexone; narcotic antagonist; nonhuman; norbinaltorphimine

Electrophysiological Indices of Audiovisual Speech Perception in the Broader Autism Phenotype. - Irwin, Julia; Avery, Trey; Turcios, Jacqueline; Brancazio, Lawrence; Cook, Barbara; Landi, Nicole (Brain sciences, 2017)
When a speaker talks, the consequences of this can both be heard (audio) and seen (visual). A novel visual phonemic restoration task was used to assess behavioral discrimination and neural signatures (event-related potentials, or ERP) of audiovisual processing in typically developing children with a range of social and communicative skills assessed using the social responsiveness scale, a measure of traits associated with autism. An auditory oddball design presented two types of stimuli to the listener, a clear exemplar of an auditory consonant-vowel syllable /ba/ (the more frequently occurring standard stimulus), and a syllable in which the auditory cues for the consonant were substantially weakened, creating a stimulus which is more like /a/ (the infrequently presented deviant stimulus). All speech tokens were paired with a face producing /ba/ or a face with a pixelated mouth containing motion but no visual speech. In this paradigm, the visual /ba/ should cause the auditory /a/ to be perceived as /ba/, creating an attenuated oddball response; in contrast, a pixelated video (without articulatory information) should not have this effect. Behaviorally, participants showed visual phonemic restoration (reduced accuracy in detecting deviant /a/) in the presence of a speaking face. In addition, ERPs were observed in both an early time window (N100) and a later time window (P300) that were sensitive to speech context (/ba/ or /a/) and modulated by face context (speaking face with visible articulation or with pixelated mouth). Specifically, the oddball responses for the N100 and P300 were attenuated in the presence of a face producing /ba/ relative to a pixelated face, representing a possible neural correlate of the phonemic restoration effect. Notably, those individuals with more traits associated with autism (yet still in the non-clinical range) had smaller P300 responses overall, regardless of face context, suggesting generally reduced phonemic discrimination.
8 citations (Crossref) [2023-10-31] Place: Switzerland Irwin, Julia. Haskins Laboratories, New Haven, CT 06511, USA. julia.irwin@yale.edu. Irwin, Julia. Department of Psychology, Southern Connecticut State University, New Haven, CT 06515, USA. julia.irwin@yale.edu. Avery, Trey. Haskins Laboratories, New Haven, CT 06511, USA. trey.avery@yale.edu. Turcios, Jacqueline. Haskins Laboratories, New Haven, CT 06511, USA. jacqueline.turcios@yale.edu. Turcios, Jacqueline. Department of Communication Disorders, Southern Connecticut State University, New Haven, CT 06515, USA. jacqueline.turcios@yale.edu. Brancazio, Lawrence. Haskins Laboratories, New Haven, CT 06511, USA. brancaziol1@southernct.edu. Brancazio, Lawrence. Department of Psychology, Southern Connecticut State University, New Haven, CT 06515, USA. brancaziol1@southernct.edu. Cook, Barbara. Department of Communication Disorders, Southern Connecticut State University, New Haven, CT 06515, USA. cookb5@southernct.edu. Landi, Nicole. Haskins Laboratories, New Haven, CT 06511, USA. nicole.landi@yale.edu. Landi, Nicole. Psychological Sciences, University of Connecticut, Storrs, CT 06269, USA. nicole.landi@yale.edu.
Keywords: Article; Audiovisual speech perception; Broader autism phenotype; Development; ERP; audiovisual aid; audiovisual equipment; audiovisual speech perception; autism; behavior; broader autism phenotype; child; clinical article; dept.cmd; dept.hls; dept.psy; development; electrophysiology; female; human; male; participant observation; phenotype; social adaptation; social competence; speech perception; stimulus; vision test

Electrophysiology of perception and processing of phonological information as indices of toddlers' language performance - Harwood, Vanessa; Preston, Jonathan; Grela, Bernard; Roy, Dooti; Harold, Olivia; Turcios, Jacqueline; Andrada, Kiyomi; Landi, Nicole (Journal of Speech Language and Hearing Research, 2017)
Purpose: The toddler years are a critical period for language development and growth. We investigated how event-related potentials (ERPs) to repeated and novel nonwords are associated with clinical assessments of language in young children. In addition, nonword repetition (NWR) was used to measure phonological working memory to determine the unique and collective contribution of ERP measures of phonemic discrimination and NWR as predictors of language ability. Method: Forty children between the ages of 24-48 months participated in an ERP experiment to determine phonemic discrimination to repeated and novel nonwords in an old/new design. Participants also completed a NWR task to explore the contribution of phonological working memory in predicting language. Results: ERP analyses revealed that faster responses to novel stimuli correlated with higher language performance on clinical assessments of language. Regression analyses revealed that an earlier component was associated with lower level phonemic sensitivity, and a later component was indexing phonological working memory skills similar to NWR. Conclusion: Our findings suggest that passive ERP responses indexing phonological discrimination and phonological working memory are strongly related to behavioral measures of language.
Citation Key Alias: lens.org/016-284-901-764-293 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Brain; Child Language; Child; Preschool; Discrimination (Psychology); Electroencephalography; Evoked Potentials; Female; Humans; Language Tests; Male; Memory; Short-Term; Pattern Recognition; Physiological; Phonetics; Reaction Time; Regression Analysis; Signal Processing; Computer-Assisted; Speech Perception; adult; brain; child; clinical article; dept.psy; electroencephalography; event related potential; evoked response; female; human; language ability; language development; language test; male; pattern recognition; perception; perceptive discrimination; phonetics; physiology; preschool child; reaction time; regression analysis; short term memory; signal processing; speech perception; stimulus; working memory; young adult; ⚠️ Invalid DOI

EdPsych modules - Durwin, Cheryl Cisero; Reese-Weber, Marla J. (SAGE Publications, Inc, 2017)
Now with SAGE Publications, Cheryl Cisero Durwin and Marla Reese-Weber’s EdPsych Modules uses an innovative implementation of case studies and a modular format to address the challenge of effectively connecting theory and research to practice. Each module is a succinct, stand-alone topic that represents every subject found in traditional chapter texts and can be used in any order for maximum flexibility in organizing your course. Each of the book’s eight units of modules begins with a set of four case studies–early childhood, elementary, middle school, and secondary–and ends with "Assess" and "Reflect and Evaluate" questions and activities to encourage comprehension and application of the research and theories presented. The case approach and the extensive pedagogy that support it allows students to constantly see the applications of the theories and research that they are studying in the text.
Keywords: dept.psy

The development of gaze to a speaking face. - Irwin, Julia; Brancazio, Lawrence; Volpe, Nicole (The Journal of the Acoustical Society of America, 2017)
When a speaker talks, the visible consequences of what they are saying can be seen. Listeners are influenced by this visible speech both in a noisy listening environment and even when auditory speech can easily be heard. While visible influence on heard speech has been reported to increase from early to late childhood, little is known about the mechanism that underlies this developmental trend. One possible account of developmental differences is that looking behavior to the face of a speaker changes with age. To examine this possibility, the gaze to a speaking face was examined in children from 5 to 10 yrs of age and adults. Participants viewed a speaker's face in a range of conditions that elicit looking: in a visual only (speech reading) condition, in the presence of auditory noise (speech in noise) condition, and in an audiovisual mismatch (McGurk) condition. Results indicate an increase in gaze on the face, and specifically, to the mouth of a speaker between the ages of 5 and 10 for all conditions. This change in looking behavior may help account for previous findings in the literature showing that visual influence on heard speech increases with development.
3 citations (Crossref) [2023-10-31] Place: United States Irwin, Julia. Haskins Laboratories, 300 George Street, New Haven, Connecticut 06511, USA. Brancazio, Lawrence. Southern Connecticut State University, 501 Crescent Street, New Haven, Connecticut 06515, USA. Volpe, Nicole. Southern Connecticut State University, 501 Crescent Street, New Haven, Connecticut 06515, USA.
Keywords: *Facial Expression; *Fixation; Ocular; *Speech Acoustics; *Speech Perception; *Visual Perception; *Voice Quality; Acoustic Stimulation; Acoustics; Age Factors; Audiometry; Speech; Child; Child; Preschool; Cues; Early-to-late; Facial Expression; Female; Fixation; Ocular; Humans; Male; Noise; Noise/ae [Adverse Effects]; Perceptual Masking; Photic Stimulation; Physics; Speech; Speech Acoustics; Speech Perception; Speech in noise; Speech reading; Video Recording; Visible speech; Visual Perception; Voice Quality; Young Adult; age; association; auditory stimulation; child; dept.hls; dept.psy; eye fixation; facial expression; female; human; male; masking; noise; photostimulation; preschool child; speech; speech audiometry; speech perception; videorecording; vision; voice; young adult

Strain-specific programming of prenatal ethanol exposure across generations. - Popoola, Daniel O; Nizhnikov, Michael E; Cameron, Nicole M (Alcohol (Fayetteville, N.Y.), 2017)
Behavioral consequences of prenatal alcohol exposure (PAE) can be transmitted from in utero-exposed F1 generation to their F2 offspring. This type of transmission is modulated by genetic and epigenetic mechanisms. This study investigated the intergenerational consequences of prenatal exposure to a low ethanol dose (1 g/kg) during gestational days 17-20, on ethanol-induced hypnosis in adolescent male F1 and F2 generations, in two strains of rats. Adolescent Long-Evans and Sprague-Dawley male rats were tested for sensitivity to ethanol-induced hypnosis at a 3.5-g/kg or 4.5-g/kg ethanol dose using the loss of righting reflex (LORR) paradigm. We hypothesized that PAE would attenuate sensitivity to ethanol-induced hypnosis in the ethanol-exposed animals in these two strains and in both generations. Interestingly, we only found this effect in Sprague-Dawley rats. Lastly, we investigated PAE related changes in expression of GABAA receptor alpha1, alpha4, and delta subunits in the cerebral cortex of the PAE sensitive Sprague-Dawley strain. We hypothesized a reduction in the cerebral cortex GABAA receptor subunits' expression in the F1 and F2 PAE groups compared to control animals. GABAA receptor alpha1, alpha4, and delta subunits protein expressions were quantified in the cerebral cortex of F1 and F2 male adolescents by western blotting. PAE did not alter cerebral cortical GABAA receptor subunit expressions in the F1 generation, but it decreased GABAA receptor alpha4 and delta subunits' expressions in the F2 generation, and had a tendency to decrease alpha1 subunit expression. We also found correlations between some of the subunits in both generations. These strain-dependent vulnerabilities to ethanol sensitivity, and intergenerational PAE-mediated changes in sensitivity to alcohol indicate that genetic and epigenetic factors interact to determine the outcomes of PAE animals and their offspring. Copyright © 2017 Elsevier Inc. All rights reserved.
9 citations (Crossref) [2023-10-31] Place: United States Popoola, Daniel O. Psychology Department, Center for Developmental and Behavioral Neuroscience, Developmental Exposure Alcohol Research Center, Binghamton University- SUNY, 4400 Vestal Parkway East, Binghamton, NY 13902, USA. Nizhnikov, Michael E. Southern Connecticut State University, 501 Crescent Street, New Haven, CT, 06515-1355, USA. Cameron, Nicole M. Psychology Department, Center for Developmental and Behavioral Neuroscience, Developmental Exposure Alcohol Research Center, Binghamton University- SUNY, 4400 Vestal Parkway East, Binghamton, NY 13902, USA. Electronic address: ncameron@binghamton.edu.
Keywords: *Alcohol Drinking/ae [Adverse Effects]; *Behavior; Animal/de [Drug Effects]; *Cerebral Cortex/de [Drug Effects]; *Ethanol/to [Toxicity]; *Prenatal Exposure Delayed Effects; *Receptors; GABA-A/de [Drug Effects]; 4 aminobutyric acid A receptor; 4 aminobutyric acid A receptor alpha1; 4 aminobutyric acid A receptor alpha4; Age Factors; Alcohol Drinking; Alcohol Drinking/ge [Genetics]; Alcohol Drinking/me [Metabolism]; Alcohol Drinking/px [Psychology]; Animals; Article; Behavior; Animal; Blood Alcohol Content; Cerebral Cortex; Cerebral Cortex/me [Metabolism]; Cerebral Cortex/pa [Pathology]; Dose-Response Relationship; Drug; Epigenesis; Genetic; Epigenesis; Genetic/de [Drug Effects]; Ethanol; Ethanol/bl [Blood]; Female; Gestational Age; Long Evans rat; Male; Maternal Exposure; Pregnancy; Prenatal Exposure Delayed Effects; Rats; Long-Evans; Rats; Sprague-Dawley; Reaction Time; Receptors; GABA-A; Receptors; GABA-A/ge [Genetics]; Receptors; GABA-A/me [Metabolism]; Reflex; Righting; Reflex; Righting/de [Drug Effects]; Species Specificity; Sprague Dawley rat; Time Factors; Western blotting; adolescent; adult; age; alcohol; alcohol blood level; alcohol consumption; animal; animal behavior; animal experiment; animal model; animal tissue; blood; brain cortex; comparative study; controlled study; correlational study; dept.psy; dose response; drinking behavior; drug effects; epigenetics; female; genetic epigenesis; genetics; gestation period; gestational age; hemoglobin delta chain; heredity; hypnosis; male; maternal exposure; metabolism; nonhuman; outcome assessment; pathology; peer-reviewed; pregnancy; prenatal exposure; progeny; protein expression; psychology; rat

Audiovisual speech perception: A new approach and implications for clinical populations - Irwin, Julia; DiBlasi, Lori (Language and Linguistics Compass, 2017)
This selected overview of audiovisual (AV) speech perception examines the influence of visible articulatory information on what is heard. Thought to be a cross-cultural phenomenon that emerges early in typical language development, variables that influence AV speech perception include properties of the visual and the auditory signal, attentional demands, and individual differences. A brief review of the existing neurobiological evidence on how visual information influences heard speech indicates potential loci, timing, and facilitatory effects of AV over auditory only speech. The current literature on AV speech in certain clinical populations (individuals with an autism spectrum disorder, developmental language disorder, or hearing loss) reveals differences in processing that may inform interventions. Finally, a new method of assessing AV speech that does not require obvious cross-category mismatch or auditory noise was presented as a novel approach for investigators.
9 citations (Crossref) [2023-10-31]
Keywords: dept.psy

Teaching and learning guide for audiovisual speech perception: A new approach and implications for clinical populations. - Irwin, Julia; Turcios, Jacqueline (Language and linguistics compass, 2017)
0 citations (Crossref) [2023-10-31] Place: England Irwin, Julia. Haskins Laboratories, New Haven, CT, USA. Irwin, Julia. Southern Connecticut State University, New Haven, CT, USA. Turcios, Jacqueline. Haskins Laboratories, New Haven, CT, USA. Turcios, Jacqueline. Southern Connecticut State University, New Haven, CT, USA.
Keywords: dept.psy